Method for producing multi-junction device
By using a protic solvent/organic amine solvent system with high volatile, low boiling point and solution deposition method, the problem of building multi-junction all-perovskite solar cells is solved, and high-efficiency solar energy with low cost and easy manufacturing is achieved Battery.
Patent Information
- Application Number
- CN201980084620.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-10-22
- Filing Date
- 2019-10-18
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2039-10-18
AI Technical Summary
The prior art is difficult to construct efficient multijunction all-perovskite solar cells through full solution processing, and traditional methods require complex processing techniques such as sputtering coating and lamination.
Using a highly volatile, low boiling point aprotic solvent/organic amine solvent system, a crystalline A/M/X material layer is formed by solution deposition, and a charge composite layer is arranged between the photoactive regions to achieve multiple full solution processing Junction solar cells.
It realizes a low-cost, easy-to-manufacturing all-perovskite multijunction solar cell without using complex processing techniques, improving the reproducibility and efficiency of the device.
Smart Images

Figure CN113228323B_ABST
Abstract
Description
Technical Field
[0001] The present invention provides a method for producing a multi-junction device comprising a crystalline A / M / X material layer. A multi-junction device obtainable or obtained by the method of the present invention is also provided; a multi-junction device comprising at least two photoactive regions, wherein at least one photoactive region comprises a crystalline A / M / X material layer; a multi-junction device comprising at least three photoactive regions, wherein each photoactive region comprises a crystalline A / M / X material layer. Background Art
[0002] When the first report of perovskite solar cells was published in 2009, the conversion efficiency of sunlight to electricity was 3%. By 2012, perovskite photovoltaic devices with conversion efficiencies of 9.2% and 10.9% had been achieved. Since then, research in the field of perovskite photovoltaic devices and photovoltaic devices based on other A / M / X materials has rapidly increased, with these materials showing the promise of completely changing the energy landscape. Since then, perovskite-based photovoltaic devices have achieved certified efficiencies of over 23%.
[0003] In addition to the remarkable high energy conversion efficiency, one of the most attractive features of A / M / X materials is that the high-quality films of this material can be manufactured relatively simply. Perovskite films can be manufactured by a variety of methods, including various combinations of one-step spin coating, vapor deposition and dip coating and these three approaches. However, one-step spin coating is still the simplest and fastest method, and has the additional advantage of not needing to use particularly expensive equipment. Many variations of this method have been developed, such as including an additional step in the form of anti-solvent quenching. It can be expected that the spin coating method developed in the laboratory will be slightly modified to form a solution-processed manufacturing method, such as inkjet printing, spraying, slit dye coating, blade coating and gravure printing.
[0004] Despite the importance of perovskite solar cells in photovoltaic research, there are still some concerns about the viability of this material in the market. One of the concerns is the stability of the material and the anomalous hysteresis that is often observed in the JV characteristics of these devices. It has been shown that this hysteresis is due to ion movement, and many attempts have been made to mitigate this effect. The so-called reverse positive-intrinsic-negative (pin) structure has been shown to exhibit little or even negligible hysteresis, while for the regular negative-intrinsic-positive (nip) structure, the TiO2, which is usually used as an n-type charge collection layer, is replaced with an organic electron acceptor such as C60 or phenyl-C61-butyric acid methyl ester (PCBM) or including a thin layer of such material on top of the TiO2 layer has been very successful in reducing hysteresis, and this can significantly increase the steady-state power output of the device.
[0005] To date, most reports on perovskite films made by solution methods have used polar aprotic solvents with high boiling points (see, for example, Eperon et al, Morphological Control for High Performance, Solution-Processed Planar Heterojunction Perovskite Solar Cells, Adv. Funct. Mater. 2013). The most commonly used solvent is dimethylformamide (DMF), and other solvents include dimethyl sulfoxide (DMSO), γ-butyrolactone, and dimethylacetamide (DMA). In this case, the choice of solvent is limited by the fact that lead halide salts tend to be sparingly soluble or completely insoluble in most solvents commonly used in the processing of organic semiconductor and dye-sensitized solar cell materials. One of the disadvantages of using solvents such as these is that the film needs to be heated to a relatively high temperature (≥100°C) to induce crystallization of the perovskite or A / M / X material film. This can be slightly avoided by using the so-called antisolvent quenching method, which is to soak in the antisolvent at a specified time during spin coating, thereby causing immediate crystallization of the perovskite material. However, this may complicate the process by requiring an additional antisolvent quenching step.
[0006] As discussed in WO 2017 / 153752, there are several problems associated with existing solution-based methods for forming films of A / M / X materials. Currently used solvents (such as DMF, DMSO, γ-butyrolactone and DMA) are selected because of their ability to dissolve precursor compounds of A / M / X materials, especially metal halide precursors. However, these solvents have high boiling points, increasing the energy requirements or complexity of solution processing. They also tend to remove pre-existing organic layers during device production. These solvents are known to be toxic and correspondingly difficult to handle, and therefore may not be suitable for high-volume manufacturing due to toxicological considerations. Finally, these solvents pose problems for atmospheric purification units and are therefore challenging to adopt in manufacturing.
[0007] Another consideration is the solubility of other components of multijunction devices, such as organic electron accepting layers in photovoltaic devices, in high boiling point solvents, such as DMF, the most commonly used perovskite solvent. Both C60 and PCBM are slightly soluble in DMF. This can cause two problems when depositing the perovskite layer: (i) in the worst case, the electron selective contact is almost completely washed away; or (ii) in the best case, pinholes are formed, forming shunt channels. Even if partial washing away of the electron selective contact occurs only to a small extent, this can cause another problem: irreproducibility of device performance due to the constant variation in the thickness and uniformity of the n-type acceptor.
[0008] Multi-junction device architectures can increase the energy conversion efficiency of photovoltaic cells beyond the single-junction thermodynamic limit that most current commercial cells operate in. Traditionally, monolithic tandem solar cells with solution-processed perovskite layers must retain the combination of a silicon PV cell and a single perovskite solar cell junction.
[0009] Metal halide perovskite semiconductors exhibit high performance when integrated into optoelectronic devices such as light emitting diodes (LEDs), photodetectors, lasers, and solar cells. These perovskites typically have a general chemical formula of ABX3, so that their band gaps can be adjusted by replacing their chemical components, namely A-site cations (methylammonium ions, formamidinium ions, cesium ions), B-site metal cations (lead ions or tin ions), or X-site anions (iodine ions, bromide ions, chloride ions). This enables halide perovskite semiconductors to be tuned to absorb specific regions of the solar spectrum and used in multi-junction applications with the ability to exceed the Shockley-Queisser and Tiedje-Yablonovitch thermodynamic efficiency limits. By reducing the difference between the photon energy and the electronic band gap energy, the heat loss of charge carriers can be minimized, thereby increasing the maximum achievable energy conversion efficiency (PCE). In order to reduce the conversion of photon energy to heat, a variety of absorber materials with wide band gap ranges are required. Recently, high-efficiency solar cells using wide-bandgap perovskites have been prepared by partially replacing organic A-site cations with cesium ions (Cs) to improve the structural, thermal, and photostability of perovskites. In addition, narrow-bandgap materials have also been explored by changing the B-site cations, where partial replacement of lead seeds (Pb) with tin ions (Sn) results in abnormal bandgap bending behavior, resulting in a bandgap close to 1.2 eV.
[0010] Considering the potential advantages offered by the above-mentioned perovskite semiconductors, especially the ability to change the chemical composition to tune the band gap as desired, it is highly desirable to be able to construct all-perovskite multi-junction solar cells.
[0011] Recent interest in all-perovskite multijunction solar cells has shown that these devices present challenges to produce, especially via solution-based methods. This is partly due to the inability to easily use solvents such as DMF and DMSO to build multijunction solar cells one on top of the other. Both DMF and DMSO are strong coordinating solvents used in dissolving perovskite salts. These solvents, which are used to process uniform and high-quality perovskite films, can easily penetrate the layers being processed, which results in washing away or chemically destroying any perovskite layers that have been processed underneath.
[0012] Perovskite solar cells that have demonstrated record efficiencies of 23% in single-junction devices have been processed via solution-based fabrication methods. The ability to prepare high-quality absorber materials via solution-based processes coupled with their outstanding optoelectronic performance has enabled the rapid rise of perovskite solar cells. In recent years, major breakthroughs have been made in four-terminal (4T) and two-terminal (2T) silicon perovskites, Cu(In,Ga)Se2 perovskites (CIGS), Cu2ZnSn(S,Se)4 perovskites (CZTSSe), and perovskite-perovskite tandem cells. Tandem solar cells require semi-transparent electrodes and / or composite layers between each subcell, which can be prepared using a variety of materials and processing methods. These highly conductive transparent layers have been prepared using silver nanowires (Ag-NWs), N4,N4,N4",N4"-tetrakis([1,1'-biphenyl]-4-yl)-[1,1':4',1"-triphenyl]-4,4"-diamine doped 2,2'-(perfluoronaphthalene-2,6-dimethylene)dimalononitrile (TaTm:F6-TCNNQ), poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), aluminum-doped zinc oxide (AZO), and most notably indium tin oxide (ITO). These materials can also be processed using different deposition techniques such as spraying, film transfer lamination, vacuum deposition, and sputter coating. Sputtered ITO has gained considerable attention due to its high optical transparency throughout the visible and near-infrared (NIR) light region coupled with low resistivity. Due to its dense and compact nature, sputtered ITO can act as a physical barrier to solvents used to process subsequent material layers. These solvents will quickly redissolve any underlying perovskite layers unless they are protected by a dense, pinhole-free free layer, such as indium tin oxide (ITO).
[0013] As recently demonstrated, monolithic all-perovskite tandem cells with power conversion efficiencies (PCEs) exceeding 17% can be prepared using dense sputtered ITO layers. These sputter-coated TCOs require high vacuum deposition systems and dense buffer layers composed of nanoparticles (NPs) or atomic layer deposition (ALD) layers to protect the organic and perovskite layers from sputtering damage. In addition, the lower refractive index of ITO compared to the perovskite absorber layer increases significant internal reflection losses, limiting the maximum feasible power conversion efficiency. So far, the redissolution problem has prevented any experimental realization of all solution-processed multi-junction perovskite solar cells without the use of sputter-coated ITO or other more complex processing techniques.
[0014] To date, it has not been possible to construct multijunction all-perovskite solar cells entirely by solution processing. In an attempt to protect the first perovskite layer and allow the preparation of all-perovskite solar cells, a number of strategies have been employed as described below.
[0015] In Eperon et al. (Perovskite-perovskite tandem photovoltaics with optimized bandgaps, Science, 2016), in order to protect the first perovskite layer below from damage by the solvent used for the deposition of the second perovskite layer, the composite layer used includes a tin oxide sputtering layer coated with indium tin oxide. The composite layer provides a physical barrier between the perovskite layers that the solvent (such as DMF / DMSO) cannot pass through. However, this requires more complex processing techniques, such as sputtering coating, which leads to a more complex, lengthy and expensive manufacturing process.
[0016] In Heo et al. (CH3NH3PbBr3-CH3NH3PbI3 Perovskite-Perovskite Tandem SolarCells with Exceeding 2.2V Open Circuit Voltage, Adv. Mater. 2016, 28, 5121-5125), the problem of solvent damage to the underlying perovskite layer is avoided by making the top and bottom of the solar cell separately and then laminating them together. A thick hole transport layer is required to maintain adhesion between the front and back cells. The PCE of these solar cells is about 10.8%. The process requires a series of more complex manufacturing steps, including lamination, and is therefore not entirely solvent-based.
[0017] In Sheng et al., Monolithic Wide Band Gap Perovskite / Perovskite TandemSolar Cells with Organic Recombination Layers, J.Phys.Chem.C 2017, 121, 27256-27262, a sequential vapor solution treatment method was used to avoid solution treatment of the second perovskite layer with DMF. The resulting tandem solar cell had a PCE of 5.9%. This method is not well suited for large-scale printing technology because it requires thermal evaporation of the precursor.
[0018] In Jiang et al. A two-terminal perovskite / perovskite tandem solar cell J. Mater. Chem 2016, 4, 1208-1213, an anti-solvent quenching technique is used to deposit the perovskite layer, and a film transfer-lamination technique is used to place the composite layer on the bottom cell. These more complex techniques also hinder the large-scale application of this method.
[0019] None of these strategies provides a simple all-solution method for preparing multijunction devices. Summary of the invention
[0020] The present invention enables the construction of A / M / X multi-junction devices without having to employ complex processing techniques such as sputter coating, lamination or vapor deposition, thereby achieving an all-solution approach to multi-junction devices, thereby allowing such devices to be manufactured at low cost and easily using conventional printing techniques, such as solution-processed manufacturing methods, such as inkjet printing, spray coating, slot dye coating, doctor blade coating and gravure printing and spin coating. In particular, the present invention provides both a solution-processed perovskite layer and a solution-processed charge recombination layer including a tunable junction.
[0021] By employing a highly volatile, low boiling aprotic solvent / organic amine type solvent system, it has been shown that perovskite junctions can be stacked on top of each other to form an all-solution processed all-perovskite multi-junction solar cell. The solvation strength of this solvent system can be tuned by varying the amount of organic amine present. This means that the solvent used has the solvation strength required to dissolve the A / M / X precursor materials, but with a very low minimum excess of organic amine, eliminating the risk of damaging the layers below in the device. As a result, it has been found that the solvent used does not wash away the existing organic layers or the underlying perovskite layers during the production of the multi-junction device. This improves the reproducibility and efficiency of the devices produced.
[0022] The inventors have developed a recombination layer that can be arranged between various photoactive layers using solution-based techniques. The charge recombination layer described herein can be deposited using a solution-based method. This means that complex techniques such as sputter coating, lamination or vacuum deposition are not required, making the production of multi-junction devices simpler. In addition, this also means that thin (<100 nm) charge recombination layers can be manufactured, so that internal reflection losses can be reduced and energy conversion efficiency can be improved.
[0023] This fully solution-processed architecture has the potential to be applied to the fabrication of large-area films on rigid and flexible substrates using deposition techniques such as roll-to-roll (R2R) processing, doctor blade coating, slot dye coating, gravure printing or inkjet printing. Thus, the present invention provides a route to fully solution-processed multijunction solar cells. These findings open up new possibilities for large-scale, low-cost, printable perovskite multijunction solar cells.
[0024] Thus, the present invention provides a method for producing a multi-junction device comprising a layer of crystalline A / M / X material comprising the formula [A] a [M] b [X] c A compound of the invention, wherein: [A] comprises one or more A cations; [M] comprises one or more M cations, the M cations being metal or metalloid cations; [X] comprises one or more X anions; a is a number from 1 to 6; b is a number from 1 to 6; and c is a number from 1 to 18; and the method comprises forming the crystalline A / M / X material layer by disposing a film-forming solution on a substrate, wherein the film-forming solution comprises:
[0025] (a) one or more M cations; and
[0026] (b) a solvent;
[0027] The solvent contains
[0028] (i) an aprotic solvent; and
[0029] (ii) Organic amines
[0030] Furthermore, the substrate comprises: a photoactive region containing a photoactive material; and a charge recombination layer arranged on the photoactive region by solution deposition.
[0031] The invention also provides a multi-junction device obtainable or obtained by a method of the invention as defined above.
[0032] The present invention also provides a multi-junction device, comprising:
[0033] (a) at least two photoactive regions, wherein at least one photoactive region comprises a layer of crystalline A / M / X material, the crystalline A / M / X material comprising the formula [A] a [M] b [X] cA compound wherein: [A] comprises one or more A cations; [M] comprises one or more M cations, the M cations being metal or metalloid cations; [X] comprises one or more X anions; a is a number from 1 to 6; b is a number from 1 to 6; and c is a number from 1 to 18; and
[0034] (b) A charge recombination layer comprising nanoparticles of a transparent conductive oxide.
[0035] Compared to dense sputtered ITO layers which introduce significant internal reflection losses due to the lower refractive index of ITO than the A / M / X absorbing layers, the nanoparticles produce discontinuous layers that are not only solution processable but also enable light to scatter through any subsequent light absorbing layers, thereby increasing the light absorption of the device.
[0036] The present invention also provides a multi-junction device, comprising:
[0037] (a) at least two photoactive regions, wherein at least one photoactive region comprises a layer of crystalline A / M / X material, the crystalline A / M / X material comprising the formula [A] a [M] b [X] c A compound wherein: [A] comprises one or more A cations; [M] comprises one or more M cations, the M cations being metal or metalloid cations; [X] comprises one or more X anions; a is a number from 1 to 6; b is a number from 1 to 6; and c is a number from 1 to 18; and
[0038] (b) A charge recombination layer comprising a conductive polymer.
[0039] The present invention also provides a multi-junction device, comprising
[0040] (a) at least three photoactive regions, wherein each photoactive region comprises a layer of crystalline A / M / X material, the crystalline A / M / X material comprising the formula [A] a [M] b [X] c A compound wherein: [A] comprises one or more A cations; [M] comprises one or more M cations, the M cations being metal or metalloid cations; [X] comprises one or more X anions; a is a number from 1 to 6; b is a number from 1 to 6; and c is a number from 1 to 18; and
[0041] (b) at least one charge recombination layer disposed between the photoactive regions.
[0042] The present invention can also be used advantageously to produce multi-junction light emitting devices, wherein different bandgap light emitting diodes of the multiple junctions produce a combined white light emission. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figures 1A to 1E shows a two-terminal (2T) FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 (where MA = methylammonium ion, CH3NH3 + ) Results for tandem perovskite solar cells. Figure 1A Scanning electron microscope (SEM) images of top views of MAPbI3 thin films deposited on top of the top cell (TC) and the interlayer, prepared from an acetonitrile (CH3CN) / methylamine (CH3NH2) (ACN / MA) solvent system with a relative molar excess of PbI2 ranging from 6% to 6% relative molar excess of MAI relative to a stoichiometric molar ratio of MAI:PbI2 of 100:100. Figure 1B Schematic diagram showing a fully solution-processed perovskite / perovskite two-terminal (2T) tandem perovskite solar cell. The incident light will come from below the device. Figure 1C Shown is an SEM cross section of a 2T perovskite / perovskite tandem cell. Figure 1D The optimal FA measured at a scan rate of 0.25 V / s is shown. 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 tandem heterojunction solar cell JV characteristics, where the applied mismatch factor is 1.004. Figure 1E The external quantum efficiency (EQE) spectrum of each subcell is shown, as well as the integrated current density of the tandem perovskite solar cell.
[0044] FIG. 2A to FIG. 2D The ACN processed MAPb 0.75 Sn 0.25 I3 perovskite materials, the effect of changing the composition of A and B site cations. Figure 2A ) shows the results of Kelvin probe measurements of varying the stoichiometry of the A and B sites. Figure 2B ) shows normalized time-resolved photoluminescence (PL) measurements at the peak emission wavelength for varying A to B site stoichiometry. Figure 2C ) shows the effect of A and B site stoichiometry on transient photocurrent. Figure 2D The best MAPb measured at a scan rate of 0.25 V / s is shown. 0.75 Sn 0.25 I3 J-V characteristics of a single-junction heterojunction solar cell with 15% excess metal ions.
[0045] FIG. 3A to FIG. 3D Shows FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 / MAPb 0.75 Sn 0.25 I3 triple-junction perovskite solar cell. Figure 3A is a schematic diagram showing an all-solution processed triple-junction two-terminal (2T) perovskite solar cell. The incident light will come from below the device. Figure 3B Shown is an SEM cross-section of a triple-junction 2T all-perovskite stack. Figure 3C The optimal FA prepared was measured at a scan rate of 0.25 V / s. 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 / MAPb 0.75 Sn 0.25 J-V characteristics of an I3 triple heterojunction solar cell with an applied mismatch factor of 1.323. Figure 3D The open circuit voltage (Voc) of a triple-heterojunction perovskite solar cell measured over a period of 60 s is shown.
[0046] 4A to 4F Optical and electrical modeling of multi-junction perovskite solar cells is shown. Figure 4A shows the calculated JV characteristics, and Figure 4B The FA of the full solution process is shown 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 tandem solar cell with single junction experimental data and the best ACN / MAMAPbI3 single junction cell. Figure 4C shows the calculated JV characteristics, and Figure 4D Shows FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 simulated EQE spectrum of a tandem solar cell assuming that the tandem solar cell has optimal layer thicknesses, an intermediate layer below 50 nm, a MgF2 antireflection coating and enhanced top cell performance. Figure 4E shows the JV characteristics, and Figure 4F Shows FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 / FA 0.6 MA0.4 Pb 0.4 Sn 0.6 Simulated EQE spectra of the I3 triple-junction architecture assuming optimized layer thicknesses, an interlayer below 50 nm, a MgF2 antireflection coating, and enhanced top cell performance.
[0047] FIG. 5A to FIG. 5B FA with 2% potassium supplementation is shown 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3Optical characterization of perovskite materials. Figure 5A shows the FA measured with an integrating sphere 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3’s absorption spectrum. Figure 5B Shows FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 Tauc plot of perovskite assuming direct bandgap material and fitting the optical bandgap from the intercept.
[0048] Figure 6 Shows FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 Top view SEM image of the perovskite film.
[0049] Fig. 7A and Figure 7B A 2 mol% potassium (K + ) Additives SnO2 / PCBM / FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / Current-voltage characteristics of spiro-OMeTAD perovskite solar cells. Fig. 7A The results show that the simulated air mass (AM) is 1.5, 100 mW cm -2 Forward bias of the short-circuit current-voltage curve measured under sunlight using a scan rate of 0.25 V / s. The inset shows the photocurrent density and energy conversion efficiency measured over a period of 60 s at the maximum energy point. Figure 7B Shows FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3Stable open-circuit voltage (Voc) of heterojunction perovskite solar cells.
[0050] FIG. 8A to FIG. 8D The effect of varying the composition of the A and B site cations in the ACN / MA solvent processed MAPbI3 perovskite absorber layer bonded to a FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 ) in an all-perovskite tandem solar cell with a MAPbI3 front cell and a MAPbI3 back cell, where A) energy conversion efficiency, B) fill factor, C) short-circuit current density, and D) open-circuit voltage.
[0051] Fig. 9 shows the optimal FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 double-junction solar cell measured at the maximum energy point over a period of 90 s. A mismatch factor of 1.004 has been applied to the PCE.
[0052] Fig.10 Table showing mismatch factors calculated for tandem and triple junction perovskite solar cells. The following perovskite material FAs were calculated 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3. MAPbI3 and FA 0.83 Cs 0.17 Pb 0.5 Sn 0.5 Mismatch factor of I3. The spectra and calibrations for both measurements are different because KG2 and KG5 filters were used to attenuate and eliminate high intensity spikes in the infrared emission of the xenon arc solar simulator.
[0053] Fig.11A and Fig. 11B Shown is the measured solar simulator spectrum compared to the AM1.5G spectrum. Fig.11A For measuring FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 Xenon lamp spectrum of the )3 / MAPbI3 tandem solar cell, where the intensity is set by a KG5 filtered Si reference cell. Fig. 11B shows the method for measuring FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 / MAPb 0.75 Sn 0.25Xenon lamp spectrum of an I3 triple-junction solar cell, where the intensity is set by a KG2-filtered reference cell.
[0054] Fig. 12A and Fig. 12B The FA with the highest open circuit voltage is shown 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 device performance of tandem solar cells. Fig. 12A The results show that the simulated air mass (AM) is 1.5, 100 mW cm -2 Current-voltage characteristics measured at a scan rate of 0.25 V / s under sunlight. Fig. 12B The photocurrent density and energy conversion efficiency measured at the maximum energy point over a period of 60 s are shown. A mismatch factor of 1.004 has been applied to the PCE.
[0055] Fig.13A and Fig. 13B MAPb is shown 0.75 Sn 0.25 Characterization of I3 perovskite materials. Fig.13A The FTO / SnO2 / PC measured using a 50Ω resistor load is shown. 61 BM / MAPb 0.75 Sn 0.75 EQE spectra of the I3 / spiro(TFSI)2 solar cell architecture. Fig. 13B MAPb is shown 0.75 Sn 0.25 Tauc plot of I3 perovskite material, assuming a direct bandgap material.
[0056] FIG. 14A to FIG. 14D Shows changes in ACN / MAMAPb 0.75 Sn 0.25 Effect of the composition of A and B site cations of I3 perovskite single-junction solar cells on A) energy conversion efficiency, B) fill factor, C) short-circuit current density, and D) open-circuit voltage.
[0057] Fig.15A and Fig. 15B The FA with the highest open circuit voltage is shown 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 / MAPb 0.75 Sn 0.25 Device performance of I3 triple-junction solar cells. Fig.15A The results show that the simulated air mass (AM) is 1.5, 100mWcm -2Current-voltage characteristics measured at a scan rate of 0.25 V / s under sunlight. Fig. 15B The photocurrent density and energy conversion efficiency measured at the maximum energy point over a period of 60 s are shown. A mismatch factor of 1.323 has been applied to the PCE.
[0058] FIG. 16A to FIG. 16C The optical properties of the composite interlayer and the hole and electron accepting layers are shown. Fig.16A The results show the relationship between the performance of glass, indium tin oxide nanoparticles (ITO NPs), phenyl-C61-butyric acid methyl ester (PC 61 BM), phenyl-C61-butyric acid methyl ester (PC 61 BM), poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), (2,2',7,7'-tetrakis(N,N'-di-p-methoxyaniline)-9,9'-spirobifluorene) (spiro-OMeTAD). Fig. 16B Transmittance measurements are shown. Fig. 16C Reflectivity measurements are shown.
[0059] 17A to 17D Shown using FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 double junction solar cell light filtering FA 0.83 Cs 0.17 Pb 0.5 Sn 0.5 Architecture and device characterization of I3. Fig.17A is a graph showing the fully solution processed perovskite / perovskite two-terminal (2T) FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 tandem perovskite solar cells for FA 0.83 Cs 0.17 Pb 0.5 Sn 0.5 Schematic diagram of I3 filtering. Fig. 17B Shown using FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / FA of MAPbI3 double junction solar cell after light filtering 0.83 Cs 0.17 Pb 0.5 Sn 0.5 EQE spectrum of I3 (solid line), and current density of tandem perovskite solar cells. Also shown is the FA with opaque electrodes. 0.83Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 tandem perovskite solar cell’s EQE spectrum of each sub-cell, and the integrated current density of the tandem perovskite solar cell. Fig. 17C The unfiltered and as-prepared FA measured at a scan rate of 0.25 V / s are shown. 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 optimal FA for double-junction solar cells 0.83 Cs 0.17 Pb 0.5 Sn 0.5 JV characteristics of I3. Fig.17D The unfiltered and filtered FA are shown. 0.83 Cs 0.17 Pb 0.5 Sn 0.5 Photocurrent density and energy point conversion efficiency measured for an I3 solar cell at the maximum energy point over a 60 s period. A mismatch factor of 1.323 has been applied to the PCE. DETAILED DESCRIPTION
[0060] definition
[0061] As used herein, the term "crystallization" means a crystalline compound, which is a compound with an extended 3D crystal structure. Crystalline compounds are typically in the form of crystals, or in the case of polycrystalline compounds, in the form of microcrystals (i.e., multiple crystals with a particle size less than or equal to 1 μm). Crystals often form layers together. Crystals of crystalline materials can be of any size. When crystals have a size in the range of 1 nm to 1000 nm in one or more dimensions, they can be referred to as nanocrystals.
[0062] As used herein, the terms "organic compound" and "organic solvent" have typical meanings in the art and will be easily understood by those skilled in the art.
[0063] As used herein, the term "crystalline A / M / X material" refers to a material having a crystal structure that includes one or more A cations, one or more M cations, and one or more X anions. The A ions and M ions are cations. The X ions are anions. The A / M / X material typically does not contain any other type of ions.
[0064] As used herein, the term "perovskite" refers to a material having a three-dimensional crystal structure related to the three-dimensional crystal structure of CaTiO3, or a material including a material layer, wherein the layer has a structure related to the CaTiO3 structure. The structure of CaTiO3 can be represented by the formula ABX3, wherein A and B are cations of different sizes, and X is an anion. In the unit cell, the A cation is at (0,0,0), the B cation is at (1 / 2,1 / 2,1 / 2), and the X anion is at (1 / 2,1 / 2,0). The A cation is generally larger than the B cation. It will be appreciated by those skilled in the art that when A, B, and X vary, different ion sizes may cause the structure of the perovskite material to be distorted from the structure adopted by CaTiO3 to a distorted structure with lower symmetry. If the material includes a layer having a structure related to the CaTiO3 structure, the symmetry will also be lower. Materials including a perovskite material layer are well known. For example, a material structure using a K2NiF4-type structure includes a perovskite material layer. The skilled person will appreciate that the perovskite material can be represented by the formula [A][B][X]3, wherein [A] is at least one cation, [B] is at least one cation, and [X] is at least one anion. When the perovskite contains more than one A cation, different A cations may be distributed on the A site in an ordered or disordered manner. When the perovskite contains more than one B cation, different B cations may be distributed on the B site in an ordered or disordered manner. When the perovskite contains more than one X anion, different X anions may be distributed on the X site in an ordered or disordered manner. The symmetry of a perovskite containing more than one A cation, more than one B cation, or more than one X cation will be lower than the symmetry of CaTiO3. For layered perovskites, the stoichiometry between A, B, and X ions can vary. For example, if the ionic radius of the A cation is too large to fit into a 3D perovskite structure, a [A]2[B][X]4 structure may be employed. The term "perovskite" also includes A / M / X materials that employ a Ruddleson-Popper phase. The Ruddleson-Popper phase refers to a perovskite with a mixture of layered and 3D components. This type of perovskite can be A n- 1A'2M n X 3n+1 The form of a crystal structure in which A and A' are different cations and n is an integer from 1 to 8 or from 2 to 6. The term "mixed 2D and 3D" perovskite is used to refer to a perovskite in which both AMX3 and A' are present. n-1 A'2M n X 3n+1 The perovskite film has regions or domains of the perovskite phase.
[0065] As used herein, the term "metal halide perovskite" refers to a perovskite comprising at least one metal cation and at least one halide anion in its formula.
[0066] As used herein, the term "mixed halide perovskite" refers to a perovskite or mixed perovskite containing at least two types of halide anions.
[0067] As used herein, the term "mixed-cation perovskite" refers to a perovskite or mixed perovskite containing at least two types of A cations.
[0068] As used herein, the term "mixed-metal perovskite" refers to a perovskite or mixed perovskite containing at least two types of metal M cations.
[0069] As used herein, the term "organic-inorganic metal halide perovskite" refers to a metal halide perovskite comprising at least one organic cation in its formula.
[0070] As used herein, the term "monovalent cation" refers to any cation having a single positive charge, i.e., a cation of formula A + A cation, wherein A is any moiety, such as a metal atom or an organic moiety. As used herein, the term "divalent cation" refers to any cation having a double positive charge, i.e., formula A 2+ A is any moiety, such as a metal atom or an organic moiety. As used herein, the term "trivalent cation" refers to any cation having three positive charges, i.e., formula A 3+ A cation, wherein A is any moiety, such as a metal atom or an organic moiety. As used herein, the term "tetravalent cation" refers to any cation having four positive charges, i.e., formula A 4+ A cation wherein A is any moiety, such as a metal atom.
[0071] As used herein, the term "alkyl" refers to a straight or branched chain saturated hydrocarbon group. 1-20 Alkyl, C 1-14 Alkyl, C 1-10 Alkyl, C 1-6 Alkyl or C 1-4 Alkyl. C 1-10 Examples of alkyl groups are methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl or decyl. 1-6 Examples of alkyl groups are methyl, ethyl, propyl, butyl, pentyl or hexyl. 1-4 Examples of alkylalkyl are methyl, ethyl, isopropyl, n-propyl, tert-butyl, sec-butyl or n-butyl. As used herein, if the term "alkyl" is used anywhere herein without a prefix specifying the number of carbon atoms, it has 1 to 6 carbons (and this also applies to any other organic group mentioned herein).
[0072] As used herein, the term "cycloalkyl" refers to a saturated or partially unsaturated cyclic hydrocarbon group. 3-10 Cycloalkyl, C 3-8 Cycloalkyl or C 3-6 Cycloalkyl. 3-8 Examples of cycloalkyl groups include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cyclohexenyl, cyclohexa-1,3-dienyl, cycloheptyl, and cyclooctyl. 3-6 Examples of cycloalkyl groups include cyclopropyl, cyclobutyl, cyclopentyl and cyclohexyl.
[0073] As used herein, the term "alkenyl" refers to a straight or branched chain hydrocarbon group containing one or more double bonds. 2-20 Alkenyl, C 2-14 Alkenyl, C 2-10 Alkenyl, C 2-6 Alkenyl or C 2-4 Alkenyl. C 2-10 Examples of alkenyl are ethenyl (vinyl), propenyl, butenyl, pentenyl, hexenyl, heptenyl, octenyl, nonenyl or decenyl. 2-6 Examples of alkenyl are ethenyl, propenyl, butenyl, pentenyl or hexenyl. 2-4 Examples of alkenyl groups are ethenyl, isopropenyl, n-propenyl, sec-butenyl or n-butenyl.Alkenyl groups typically contain one or two double bonds.
[0074] As used herein, the term "alkynyl" refers to a straight or branched chain hydrocarbon group containing one or more triple bonds. Alkyl groups can be C 2-20 Alkynyl, C 2-14 Alkynyl, C 2-10 Alkynyl, C 2-6 Alkynyl or C 2-4 Alkynyl. C 2-20 Examples of alkynyl are ethynyl, propynyl, butynyl, pentynyl, hexynyl, heptynyl, octynyl, nonynyl or decynyl. 1-6 Examples of alkynyl groups are ethynyl, propynyl, butynyl, pentynyl or hexynyl.Alkynyl groups typically contain one or two triple bonds.
[0075] As used herein, the term "aryl" refers to a monocyclic, bicyclic or polycyclic aromatic ring containing 6 to 14 carbon atoms, typically 6 to 10 carbon atoms in the ring portion. Examples include phenyl, naphthyl, indenyl, indanyl, anthracenyl and pyrenyl. As used herein, the term "aryl" includes heteroaryl.
[0076] As used herein, the term "heteroaryl" refers to a monocyclic or bicyclic heteroaromatic ring containing one or more heteroatoms, typically containing 6 to 10 atoms in the ring portion. Heteroaryl is typically a 5- or 6-membered ring containing at least one heteroatom selected from O, S, N, P, Se, and Si. It can contain, for example, one, two, or three heteroatoms. Examples of heteroaryl include pyridyl, pyrazinyl, pyrimidinyl, pyridazinyl, furanyl, thienyl, pyrazolidinyl, pyrrolyl, oxazolyl, oxadiazolyl, isoxazolyl, thiadiazolyl, thiazolyl, isothiazolyl, imidazolyl, pyrazolyl, quinolyl, and isoquinolyl.
[0077] As used herein in the context of a substituted organic group, the term "substituted" refers to an organic group bearing one or more substituents selected from the group consisting of: 1-10 alkyl, aryl (as defined herein), cyano, amino, nitro, C 1-10 Alkylamino, di(C 1-10 ) alkylamino, arylamino, diarylamino, aryl (C 1-10 ) alkylamino, amide, acylamide, hydroxy, oxo, halo, carboxyl, ester, acyl, acyloxy, C 1-10 Alkoxy, aryloxy, halogenated (C 1-10 ) alkyl, sulfonic acid, thiol, C 1-10 Alkylthio, arylthio, sulfonyl, phosphate, phosphate ester, phosphonic acid and phosphonate. Examples of substituted alkyl groups include haloalkyl, perhaloalkyl, hydroxyalkyl, aminoalkyl, alkoxyalkyl and alkaryl. When a group is substituted, it can have 1, 2 or 3 substituents. For example, a substituted group can have 1 or 2 substituents.
[0078] As used herein, the term "halide" refers to a singly charged anion of an element in Group VIII of the Periodic Table of the Elements."Halide" includes fluoride, chloride, bromide, and iodide.
[0079] As used herein, the term "halogen" refers to a halogen atom. Exemplary halogens include fluorine, chlorine, bromine and iodine.
[0080] As used herein, an amino group is a group of formula -NR2, wherein each R is a substituent. R is typically selected from hydrogen, alkyl, alkenyl, cycloalkyl, or aryl, wherein alkyl, alkenyl, cycloalkyl, and aryl are each as defined herein. Typically, each R is selected from hydrogen, C 1-10 Alkyl, C 2-10 Alkenyl and C 3-10 Preferably, each R is selected from hydrogen, C 1-6 Alkyl, C 2-6 Alkenyl and C 3-6 More preferably, each R is selected from hydrogen and C 1-6 alkyl.
[0081] Typical amino groups are alkylamino groups, which are groups of the formula -NR2, wherein at least one R is an alkyl group as defined herein. 1-6 An alkylamino group is one in which at least one R is C 1-6 An alkylamino group of an alkyl group.
[0082] As used herein, an imino group is a group of formula R2C=N- or -C(R)=NR, wherein each R is a substituent. That is, an imino group is a group comprising a C=N moiety having a radical moiety attached to the N atom of the C=N bond or to a C atom therein. R is as defined herein: that is, R is typically selected from hydrogen, alkyl, alkenyl, cycloalkyl, or aryl, wherein alkyl, alkenyl, cycloalkyl, and aryl are each as defined herein. Typically, each R is selected from hydrogen, C 1-10 Alkyl, C 2-10 Alkenyl and C 3-10 Preferably, each R is selected from hydrogen, C 1-6 Alkyl, C 2-6 Alkenyl and C 3-6 More preferably, each R is selected from hydrogen and C 1-6 alkyl.
[0083] A typical imine group is an alkylimine group, which is a group of the formula R2C=N- or -C(R)=NR, wherein at least one R is an alkyl group as defined herein. 1-6 Alkylimino is an alkylimino group wherein the R substituent contains 1 to 6 carbon atoms.
[0084] As used herein, the term "ester" denotes an organic compound of the formula alkyl-C(=O)-O-alkyl, wherein the alkyl groups are the same or different and are as defined herein. The alkyl groups may be optionally substituted.
[0085] As used herein, the term "ether" refers to an oxygen atom substituted with two alkyl groups as defined herein. The alkyl groups may be optionally substituted and may be the same or different.
[0086] As used herein, the term "ammonium ion" refers to an organic cation containing quaternary nitrogen. The ammonium cation is a cation of the formula R 1 R 2 R 3 R 4 N + The cation R 1 , R 2 , R 3 and R 4 is a substituent. 1 , R 2 , R3 and R 4 Each of R is typically independently selected from hydrogen or optionally substituted alkyl, alkenyl, aryl, cycloalkyl, cycloalkenyl and amino; the optional substituents are preferably amino or imino substituents. Typically, R 1 , R 2 , R 3 and R 4 are each independently selected from hydrogen, and optionally substituted C 1-10 Alkyl, C 2-10 Alkenyl, C 3-10 Cycloalkyl, C 3-10 Cycloalkenyl, C 6-12 Aryl and C 1-6 amino; where present, the optional substituent is preferably an amino group; particularly preferably C 1-6 Preferably, R 1 , R 2 , R 3 and R 4 Each of which is independently selected from hydrogen and unsubstituted C 1-10 Alkyl, C 2-10 Alkenyl, C 3-10 Cycloalkyl, C 3-10 Cycloalkenyl, C 6-12 Aryl and C 1-6 In a particularly preferred embodiment, R 1 , R 2 , R 3 and R 4 are independently selected from hydrogen, C 1-10 Alkyl and C 2-10 Alkenyl and C 1-6 More preferably, R 1 , R 2 , R 3 and R 4 are independently selected from hydrogen, C 1-6 Alkyl, C 2-6 Alkenyl and C 1-6 Amino.
[0087] As used herein, the term "iminium" refers to an iminium ion of the formula (R 1 R 2 C=NR 3 R 4 ) + An organic cation, where R 1 , R 2 , R 3 and R 4 As defined above for the ammonium cation. Therefore, in a particularly preferred embodiment of the iminium cation, R 1 , R2 , R 3 and R 4 are independently selected from hydrogen, C 1-10 Alkyl, C 2-10 Alkenyl and C 1-6 In another preferred embodiment of the iminium cation, R 1 , R 2 , R 3 and R 4 are independently selected from hydrogen, C 1-6 Alkyl, C 2-6 Alkenyl and C 1-6 Typically, the iminium cation is a carboxamidinium ion, i.e., R 1 is NH2, and R 2 , R 3 and R 4 All are H.
[0088] As used herein, the term "multi-junction device" refers to a single device that includes two or more optoelectronic devices that are electrically connected in series and sequentially positioned on top of each other. The optoelectronic device may include a perovskite absorber layer sandwiched between hole and electron accepting layers. The charge recombination layer may be a tunnel junction, separating each optoelectronic device within the multi-junction device, in which each optoelectronic device is stacked on top of each other. Typically, the band gaps of the optoelectronic semiconductors in the multi-junction device will be different from each other.
[0089] Examples of multi-junction devices include photovoltaic devices, solar cells, photovoltaic diodes, photodetectors, photodiodes, photoelectric sensors, color display devices, light emitting transistors, photosensitive transistors, phototransistors, solid-state triodes, light emitting devices, lasers or light emitting diodes. The terms "solar cell" and "photovoltaic diode" are used interchangeably herein. As used herein, the term "photovoltaic device" refers to a device that emits (source), controls or detects light. Light is understood to include any electromagnetic radiation. Examples of optoelectronic devices include photovoltaic devices, photodiodes (including solar cells), phototransistors, photomultiplier tubes, photoresistors and light emitting diodes.
[0090] The term "consisting essentially of" refers to a composition comprising the component it consists essentially of as well as other components, provided that the other components do not materially affect the basic characteristics of the composition. Typically, a composition consisting essentially of certain components will contain greater than or equal to 95 wt% of those components or greater than or equal to 99 wt% of those components.
[0091] As used herein, the term "arranged on" or "arranged on" means that one component is provided or placed on another component. The first component may be directly provided or placed on the second component, or there may be a third component interposed between the first and second components. For example, if the first layer is arranged on the second layer, this includes the case where there is an intermediate third layer between the first and second layers. Generally, "arranged on" means that one component is directly placed on another component.
[0092] As used herein, the term "layer" refers to any structure that is substantially layered in form (e.g., substantially extending in two perpendicular directions, but whose extension in a third perpendicular direction is limited). A layer may have a thickness that varies with the extent of the layer. Typically, a layer has an approximately constant thickness. As used herein, the "thickness" of a layer refers to the average thickness of the layer. The thickness of a layer can be easily measured, for example, by measuring a cross section of a film using a microscope such as an electron microscope, or by surface profile measurement, for example, using a stylus profilometer.
[0093] As used herein, the term "band gap" refers to the energy difference between the top of the valence band and the bottom of the conduction band in a material. Of course, technicians can easily use well-known methods to measure the band gap of semiconductors (including the band gap of perovskites), which does not require too much experimentation. For example, the band gap of a semiconductor can be estimated by constructing a photovoltaic diode or a solar cell from a semiconductor and determining the photovoltaic action spectrum. Alternatively, the band gap can be estimated by measuring the light absorption spectrum via transmission spectrum photometry or photothermal deflection spectroscopy. The band gap can be determined by making a Tauc diagram, as described in Tauc, J., Grigorovici, R. & Vancu, a. Optical Properties and Electronic Structure of Amorphous Germanium. Phys. Status Solidi 15, 627-637 (1966), in which the square of the product of the absorption coefficient multiplied by the photon energy is plotted on the Y axis relative to the photon energy on the x-axis, where the absorption edge and the straight line intercept of the x-axis give the optical band gap of the semiconductor. Alternatively, the optical band gap can be estimated by the starting value of the incident photon to electron conversion efficiency, as described in [Barkhouse DAR, Gunawan O, Gokmen T, Todorov TK, Mitzi DB. Device characteristics of a 10.1% hydrazine processed Cu2ZnSn(Se,S)4 solar cell. Progress in Photovoltaics: Research and Applications 2012; published online DOI: 10.1002 / pip.1160.].
[0094] As used herein, the term "semiconductor" or "semiconductor material" refers to a material whose electrical conductivity is between that of a conductor and an insulator. The semiconductor may be a negative (n) type semiconductor, a positive (p) type semiconductor, or an intrinsic (i) semiconductor. The semiconductor may have a band gap (measured at 300K) of 0.5 eV to 3.5 eV, such as 0.5 eV to 2.5 eV or 1.0 to 2.0 eV.
[0095] As used herein, the term "n-type region" refers to a region of one or more electron transport (i.e., n-type) materials. Similarly, the term "n-type layer" refers to a layer of electron transport (i.e., n-type) material. The electron transport (i.e., n-type) material can be a single electron transport compound or elemental material, or a mixture of two or more electron transport compounds or elemental materials. The electron transport compound or elemental material can be undoped or doped with one or more doping elements.
[0096] As used herein, the term "p-type region" refers to a region of one or more hole transport (i.e., p-type) materials. Similarly, the term "p-type layer" refers to a layer of hole transport (i.e., p-type) materials. The hole transport (i.e., p-type) material can be a single hole transport compound or elemental material, or a mixture of two or more hole transport compounds or elemental materials. The hole transport compound or elemental material can be undoped or doped with one or more doping elements.
[0097] As used herein, the term "electrode material" refers to any material suitable for use in an electrode. The electrode material will have a high electrical conductivity. As used herein, the term "electrode" refers to a region or layer consisting of or consisting essentially of an electrode material.
[0098] As used herein, the term "nanoparticle" refers to a microscopic particle whose size is usually measured in nanometers (nm). Nanoparticles usually have a particle size of 0.1nm to 500nm, such as 0.5nm to 500nm. Nanoparticles can, for example, be particles having a size of 0.1nm to 300nm, or such as 0.5nm to 300nm. Typically, nanoparticles have a particle size of 0.1nm to 100nm, such as 0.5nm to 100nm. The nanoparticle can have a high sphericity, that is, it can be substantially spherical or spherical. Nanoparticles with high sphericity can, for example, have a sphericity of 0.8 to 1.0. Sphericity can be measured according to the particle size. , where Vp is the volume of the particle and Ap is the area of the particle. A perfectly spherical particle has a sphericity of 1.0. All other particles have a sphericity less than 1.0. The nanoparticle may alternatively be non-spherical. It may, for example, be oblate or prolate ellipsoidal, and it may have a smooth surface. Alternatively, the non-spherical nanoparticle may be plate-like, needle-like, tubular, or have an irregular shape.
[0099] method
[0100] The present invention provides a method for producing a multi-junction device comprising a crystalline A / M / X material layer, wherein the crystalline A / M / X material comprises a formula [A] a [M] b [X] c A compound of the invention, wherein: [A] comprises one or more A cations; [M] comprises one or more M cations, the M cations being metal or metalloid cations; [X] comprises one or more X anions; a is a number from 1 to 6; b is a number from 1 to 6; and c is a number from 1 to 18; and the method comprises forming the crystalline A / M / X material layer by disposing a film-forming solution on a substrate, wherein the film-forming solution comprises:
[0101] (a) one or more M cations; and
[0102] (b) a solvent;
[0103] The solvent contains
[0104] (i) an aprotic solvent; and
[0105] (ii) Organic amines
[0106] Furthermore, the substrate comprises: a photoactive region comprising a photoactive material; and a charge recombination layer disposed on the photoactive region by solution deposition.
[0107] Typically, the method involves disposing a film-forming solution on the charge recombination layer. Thus, typically, the substrate comprises the following layers in the following order:
[0108] Charge recombination layer;
[0109] Photoactive region.
[0110] Thus, in general, a multi-junction device produced according to the present invention comprises the following layers in the following order:
[0111] Crystalline A / M / X material layer;
[0112] Charge recombination layer;
[0113] Photoactive region.
[0114] The photoactive material in the substrate is soluble in dimethylformamide (DMF). Typically, at least one component of the charge recombination layer in the substrate is soluble in dimethylformamide (DMF). For example, the photoactive material in the substrate and at least one component of the charge recombination layer in the substrate are both soluble in dimethylformamide (DMF). Typically, the photoactive material in the substrate is soluble in dimethylformamide (DMF), dimethyl sulfoxide (DMSO), or mixtures thereof. Typically, at least one component of the charge recombination layer in the substrate is soluble in dimethylformamide (DMF), dimethyl sulfoxide (DMSO), or mixtures thereof. For example, the photoactive material in the substrate and at least one component of the charge recombination layer in the substrate are both soluble in dimethylformamide (DMF), dimethyl sulfoxide (DMSO), or mixtures thereof.
[0115] The photoactive material in the substrate and the charge recombination layer in the substrate are both soluble in dimethylformamide (DMF). Generally, the photoactive material in the substrate and the charge recombination layer in the substrate are both soluble in dimethylformamide (DMF), dimethyl sulfoxide (DMSO), or a mixture thereof.
[0116] Aprotic solvents
[0117] Typically, the aprotic solvent does not include dimethylformamide (DMF). Preferably, the aprotic solvent does not include dimethylformamide, dimethyl sulfoxide (DMSO), or a mixture thereof.
[0118] The aprotic solvent can be a polar aprotic solvent. Such solvents are known to the skilled person. For example, the aprotic solvent can include a compound selected from the group consisting of chlorobenzene, acetone, butanone, methyl ethyl ketone, acetonitrile, propionitrile, or a mixture thereof.
[0119] The aprotic solvent may be a non-polar aprotic solvent. Such solvents are known to the skilled person. For example, the aprotic solvent may include toluene.
[0120] Typically, the aprotic solvent comprises a compound selected from the group consisting of chlorobenzene, acetone, butanone, methyl ethyl ketone, acetonitrile, propionitrile, toluene, or a mixture thereof. Preferably, the aprotic solvent comprises acetonitrile. For example, greater than or equal to 80 vol% of the aprotic solvent may be acetonitrile.
[0121] Organic amine
[0122] Typically, the organic amine is an unsubstituted or substituted alkyl amine, or an unsubstituted or substituted aryl amine.
[0123] Alkylamines are organic compounds containing an alkyl group and an amine group, wherein the amine group can be a primary, secondary or tertiary amine group. Alkylamine compounds can be: primary amine R A NH2, where R A is an alkyl group which may be substituted or unsubstituted; or a secondary amine R A 2NH, where each R A is an alkyl group which may be substituted or unsubstituted; or a tertiary amine R A 3N, where each R A is an alkyl group which may be substituted or unsubstituted. Typically, the alkylamine is a primary alkylamine.
[0124] Typically, the organic amine is unsubstituted or substituted (C 1-10 For example, the alkylamine compound can be a primary amine R A NH2, where R A is unsubstituted or substituted C 1-10 Alkyl, unsubstituted or substituted C 1-8 Alkyl, such as unsubstituted or substituted C 1-6 Alkyl. For example, R A It may be methyl, ethyl, propyl, isopropyl, butyl (ie, n-butyl), pentyl (n-pentyl) or hexyl (n-hexyl).
[0125] Preferably, the organic amine is unsubstituted (C 1-10Alkyl)amine or substituted with phenyl (C 1-10 For example, the organic amine may be an unsubstituted (C 1-8 Alkyl) amines, such as unsubstituted (C 1-6 The organic amine may be a (C alkyl) amine substituted with a phenyl group, such as methylamine, ethylamine, propylamine, butylamine or pentylamine, or hexylamine. 1-8 Alkyl) amines, such as (C 1-6 alkyl)amines, such as benzylamine or phenethylamine.
[0126] Therefore, the organic amine can be methylamine, ethylamine, propylamine, butylamine or pentylamine, hexylamine, benzylamine or phenylethylamine, or a mixture thereof. For example, the organic amine can be methylamine, propylamine or butylamine. Preferably, the organic amine is methylamine.
[0127] The solvent may contain two or more organic amine compounds as defined herein. For example, the solvent may contain methylamine, butylamine, phenylethylamine, hexylamine, octylamine, octadecylamine, alkylamine, naphthylamine and benzylamine, methoxy polyethylene glycol amine.
[0128] Arylamines are organic compounds containing an aryl group and an amine group. Typically, arylamines are derived from the replacement of one or more hydrogen atoms in ammonia with an aryl group.
[0129] The arylamine may comprise an amine group, wherein the amine group may be a primary, secondary or tertiary amine group. The arylamine compound may be a primary amine R B NH2, where R B is an aryl group which may be substituted or unsubstituted. For example, R B can be selected from phenyl, naphthyl, indenyl, indanyl, anthracenyl and pyrenyl. B It is phenyl, so the arylamine can be aniline (phenylamine / aniline).
[0130] The arylamine may be a secondary amine, for example, of formula R B R A NH secondary amine, where R A is an alkyl group as described herein, and R B is an aryl group as described herein. The arylamine may be a tertiary amine, for example, of formula R B R A 2N tertiary amine, where each R A is an alkyl group as described above, and R B is an aryl group as described above.
[0131] Typically, the solvent in the method of the present invention is produced by adding an organic amine in the form of a gaseous organic amine, a liquid organic amine or an organic amine solution to an aprotic solvent. Therefore, the method may further include a step of producing the solvent by adding the organic amine to the aprotic solvent. The gaseous organic amine may be added to the solvent by bubbling the organic amine through the solvent.
[0132] The amount of organic amine in the solvent can be varied as desired. Typically, the amount of organic amine present in the solvent should be sufficient to completely solvate the M cation. When A cations and X anions are also present in the film-forming solution, the amount of organic amine present in the solvent may be sufficient to completely solvate the M cations, A cations and X anions. Therefore, the solvent typically contains an amount of organic amine sufficient to maintain the film-forming solution at its critical solution point. Preferably, only a small amount of excess organic amine is present in the solvent, i.e., typically only amine sufficient to dissolve the components should be present. Typically, the volume percentage of amine in the solvent is less than or equal to 50%, more typically less than 25%, for example less than 10%.
[0133] It is desirable that there is a film-forming solution in which a minimum amount of organic amine is used to solvate the M cations, and optionally any A cations and X anions that may be present. Such a solution enables the M cations, and optionally any A cations and X anions, to be deposited uniformly on the substrate without dissolving underlying layers, such as the charge recombination layer, the photoactive region, or any charge transport layer (if present).
[0134] Typically, the film-forming solution is prepared by a method comprising the following steps:
[0135] preparing a solution in which the M cation and optionally any A cations and X anions that may be present are completely solvated by an excess of an organic amine in an aprotic solvent;
[0136] · preparing a dispersion of a compound comprising an M cation and optionally a compound or compounds comprising an A cation and an X anion in an aprotic solvent free of an organic amine;
[0137] • The solution is added to the dispersion until the undissolved compound in the dispersion is completely dissolved, thereby producing a film-forming solution for use in the method of the present invention.
[0138] As the skilled person will appreciate, the solubility of the M cation and optionally any A cations and X anions present will vary depending on the concentration and nature of the ions. The above method enables the amount of organic amine to be adjusted so that all ions are fully solvated using the appropriate amount with minimal excess.
[0139] Typically, a solution in which the M cation and optionally any A cations and X anions that may be present are completely solvated by an excess of an organic amine is prepared by a process comprising the following steps:
[0140] preparing a dispersion of a compound comprising an M cation and optionally a compound or compounds comprising an A cation and an X anion, the dispersion being free of an organic amine;
[0141] • Adding an organic amine to the dispersion until the compound comprising the M cation and optionally the compound or compounds comprising the A cation and the X anion are dissolved, typically by bubbling a gaseous organic amine through the dispersion.
[0142] Typically, the film-forming solution is disposed on the substrate by a solution phase deposition method, such as gravure coating, slot dye coating, screen printing, inkjet printing, blade coating, spray coating, roll-to-roll (R2R) processing, or spin coating. Typically, disposing the film-forming composition on the substrate includes the step of spin coating the film-forming solution on the substrate.
[0143] Typically, spin coating is performed at a speed of at least 1000RPM, such as at least 2000RPM, at least 3000RPM or at least 4000RPM, such as 1000RPM to 10000RPM, 2000RPM to 8000RPM, 2500RPM to 7500RPM, preferably about 5000RPM. Typically, spin coating is performed for at least one second, at least 5 seconds or at least 10 seconds, such as 1 second to 1 minute, 10 seconds to 30 seconds, preferably about 20 seconds.
[0144] Typically, the method further comprises removing the solvent to form a layer comprising a crystalline A / M / X material. Removing the solvent may comprise heating the solvent, or evaporating the solvent.
[0145] The solvent is usually removed by heating the substrate treated with the film-forming solution. For example, the substrate treated with the film-forming solution can be heated to a temperature of 30° C. to 400° C., such as 50° C. to 200° C. Preferably, the substrate treated with the film-forming solution is heated to a temperature of 50° C. to 200° C. and maintained for 5 minutes to 200 minutes, preferably 10 minutes to 100 minutes.
[0146] Post-processing
[0147] The method of the present invention may include an additional step of arranging a composition comprising one or more A cations and optionally one or more X anions on a substrate. The film-forming solution used in the method of the present invention may not contain any A cations and / or X anions. In this case, the A cations and / or X anions may be added to the substrate in a separate step so that a crystalline A / M / X material is formed on the substrate. Alternatively, the film-forming solution used in the method of the present invention may contain A cations and / or X anions, and the further step of arranging a composition comprising one or more A cations and optionally one or more X anions on a substrate is performed as a post-treatment step on a layer of crystalline A / M / X material.
[0148] Typically, the composition comprising one or more A cations and optionally one or more X anions is a solution. Therefore, the method of the present invention may further include the step of arranging the solution comprising one or more A cations and optionally one or more X anions on a substrate. The method of the present invention may further include the step of arranging the composition comprising one or more A cations and one or more X anions, for example, a solution comprising one or more A cations and one or more X anions, on a substrate.
[0149] A solution comprising one or more A cations and one or more X anions can be formed by dissolving one or more compounds of formula AX in a solvent, wherein A and X are as defined herein. The solvent can be different or the same as the solvent in the film-forming solution. Typically, the solvent is different from the solvent in the film-forming solution. Therefore, the solvent can be a solvent orthogonal to the solvent in the film-forming solution. Importantly, the solvent should not dissolve the perovskite film below. For example, the solvent can be isopropanol (2-propanol), ethanol (EtOH), methanol (MeOH) and butanol. The solvent can be toluene. The solvent can also be a mixture of solvents, such as a mixture of the above-mentioned alcohol and a non-protonic solvent such as toluene, anisole, chlorobenzene.
[0150] Typically, a solution comprising one or more A cations and one or more X anions is spin coated on the substrate. Typically, the spin coating is performed at a speed of at least 1000 RPM, such as at least 2000 RPM, at least 3000 RPM or at least 4000 RPM, such as 1000 RPM to 10000 RPM, at 4000 RPM to 8000 RPM, preferably about 6000 RPM. Typically, the spin coating is performed for at least one second, at least 5 seconds or at least 10 seconds, such as 1 second to 1 minute, 10 seconds to 30 seconds, preferably about 20 seconds.
[0151] Typically, the solvent is removed by heating the substrate treated with the film-forming solution. For example, the substrate treated with the film-forming solution may be heated to a temperature of 30° C. to 400° C., such as 50° C. to 200° C. Preferably, the substrate treated with the film-forming solution is heated to a temperature of 50° C. to 200° C. and maintained for 5 minutes to 200 minutes, preferably 10 minutes to 100 minutes.
[0152] Formula [A] a [M] b [X] c Compounds
[0153] The method of the present invention produces a multi-junction device comprising a layer of crystalline A / M / X material, wherein the crystalline A / M / X material comprises the formula [A] a [M] b [X] c A compound of the invention wherein: [A] comprises one or more A cations; [M] comprises one or more M cations, said M cations being metal or metalloid cations; [X] comprises one or more X anions; a is a number from 1 to 6; b is a number from 1 to 6; and c is a number from 1 to 18. a is typically a number from 1 to 4, b is typically a number from 1 to 3, and c is typically a number from 1 to 8.
[0154] Each of a, b and c may or may not be an integer. For example, a, b or c may not be an integer, in which case the compound adopts a structure with a vacancy so that the lattice is not completely filled. The method of the present invention provides good control of the product stoichiometry, and is therefore very suitable for forming a structure in which a, b or c is not an integer (for example, a structure with a vacancy at one or more sites in the A, M or X sites). Therefore, in some embodiments, one or more of a, b and c are non-integer values. For example, one of a, b and c may be a non-integer value. In one embodiment, a is a non-integer value. In another embodiment, b is a non-integer value. In yet another embodiment, c is a non-integer value.
[0155] In other embodiments, each of a, b, and c is an integer value. Thus, in some embodiments, a is an integer from 1 to 6; b is an integer from 1 to 6; and c is an integer from 1 to 18. a is typically an integer from 1 to 4, b is typically an integer from 1 to 3, and c is typically an integer from 1 to 8.
[0156] In formula [A] a [M] b [X] c Compounds of
[0157] [A] comprises one or more A cations, which may be, for example, selected from alkali metal cations or organic monovalent cations;
[0158] [M] includes one or more M cations, wherein the M cation is selected from Pd 4+ , W 4+ 、Re 4+ , Os 4+ , Ir 4+ , Pt 4+ Sn 4+ , Pb 4+ ,Ge 4+ 、Te 4+ 、Bi 3+ , Sb 3+ , Ca 2+ , Sr 2+ 、Cd 2+ , Cu 2+ 、Ni 2+ , Mn 2+ , Fe 2+ 、Co 2+ , Pd 2+ ,Ge 2+ Sn 2+ , Pb 2 + , Yb 2+ and Eu 2+ A metal or metalloid cation, preferably Sn 2+ , Pb 2+ , Cu 2+ ,Ge 2+ , and Ni 2+ ; Pb is particularly preferred 2+ and Sn 2+ ;
[0159] [X] includes one or more X anions, wherein the X anions are selected from halide anions (e.g., Cl – Br – , and I - ), O 2– , S 2– 、Se 2– , and Te 2– ;
[0160] a is a number from 1 to 4;
[0161] b is a number from 1 to 3; and
[0162] c is a number between 1 and 8.
[0163] Preferably, formula [A] a [M] b [X] c The compound includes perovskite. Formula [A] a [M] b[X] c The compounds typically include metal halide perovskites.
[0164] [M] cation
[0165] [M] includes one or more M cations, the M cations being metal or metalloid cations. [M] may include two or more different M cations. [M] may include one or more monovalent cations, one or more divalent cations, one or more trivalent cations, or one or more tetravalent ions.
[0166] Typically, the one or more M cations are selected from Ca 2+ , Sr 2+ 、Cd 2+ , Cu 2+ 、Ni 2+ , Mn 2+ , Fe 2+ 、Co 2+ , Pd 2+ ,Ge 2+ Sn 2+ , Pb 2+ , Yb 2+ 、Eu 2+ 、Bi 3+ , Sb 3+ , Pd 4+ , W 4+ 、Re 4+ , Os 4+ , Ir 4+ , Pt 4+ Sn 4+ , Pb 4+ ,Ge 4+ or Te 4+ Preferably, one or more M cations are selected from Cu 2+ , Pb 2+ ,Ge 2+ or Sn 2+ .
[0167] Typically, [M] comprises one or more metal or metalloid divalent cations. For example, each M cation may be selected from Ca 2+ , Sr 2+ 、Cd 2+ , Cu 2+ 、Ni 2+ , Mn 2+ , Fe 2+ 、Co 2+ , Pd 2+ ,Ge 2+ Sn 2+ , Pb 2+ , Yb 2+ and Eu2+ , preferably Sn 2+ , Pb 2+ , Cu 2 + ,Ge 2+ and Ni 2+ ; Pb is preferred 2+ and Sn 2+ In some embodiments, [M] comprises two different M cations, typically wherein the cations are and Sn 2+ Pb 2+ .
[0168] The membrane-forming solution used in the method of the present invention comprises: (a) one or more M cations described herein; and (b) a solvent described herein. The method of the present invention may include the step of forming the membrane-forming solution by dissolving at least one M precursor in the solvent. As discussed in more detail below, the M precursor is a compound comprising one or more M cations present in [M]. When [M] (i.e., formula [A] a [M] b [X] c When [M] in the compound comprises only one type of M cation, only one M precursor is required in the method of the present invention.
[0169] The M precursor generally comprises one or more counter anions. Thus, typically, the film-forming solution comprises one or more counter anions. Many such counter anions are known to the technician. One or more M cations and one or more counter anions can be derived from a first precursor compound that is dissolved in a solvent as described herein to form a film-forming solution.
[0170] The counter anion can be a halide anion, a thiocyanate anion (SCN – ), tetrafluoroborate anion (BF4 – ) or an organic anion. Preferably, the counter anion described herein is a halide anion or an organic anion. The membrane-forming solution may contain two or more counter anions, such as two or more halide anions.
[0171] Typically, the counter anion is of the formula RCOO – ,ROCOO – 、RSO3 – 、ROP(O)(OH)O – or an anion of RO, wherein R is H, substituted or unsubstituted C 1-10 Alkyl, substituted or unsubstituted C 2-10 Alkenyl, substituted or unsubstituted C 2-10 Alkynyl, substituted or unsubstituted C 3-10 Cycloalkyl, substituted or unsubstituted C3-10 For example, R can be H, substituted or unsubstituted C 1-10 Alkyl, substituted or unsubstituted C 3-10 Typically, R is H, substituted or unsubstituted C 1-6 For example, R can be H, unsubstituted C 1-6 Thus, R can be selected from H, methyl, ethyl, propyl, butyl, pentyl, hexyl, cyclopentyl, cyclohexyl and phenyl.
[0172] Typically, the counter anion(s) are selected from halide anions (e.g., F – , Cl – Br – and I – ) Japanese RCOO – Anions wherein R is H or methyl.
[0173] Typically, the counter anion is F – , Cl – Br – ,I – , formate ion or acetate ion. Preferably, the counter anion is Cl – Br – ,I – or F – More preferably, the counter anion is Cl – Br – or I – .
[0174] Typically, the M precursor is a compound of formula MY2, MY3 or MY4, wherein M is a metal or metalloid cation as described herein, and Y is the counter anion.
[0175] Thus, the M precursor may be a compound of formula MY2, wherein M is Ca 2+ , Sr 2+ 、Cd 2+ , Cu 2+ 、Ni 2+ , Mn 2+ , Fe 2+ 、Co 2+ , Pd 2+ ,Ge 2+ Sn 2+ , Pb 2+ , Yb 2+ or Eu 2+ , and Y is F – , Cl – Br – ,I– , formate ion or acetate ion. Preferably, M is Cu 2+ , Pb 2+ ,Ge 2+ or Sn 2+ , and Y is Cl – Br – ,I – , formate ion or acetate ion, preferably Cl – Br – or I – .
[0176] Typically, the M precursor is lead (II) acetate, lead (II) formate, lead (II) fluoride, lead (II) chloride, lead (II) bromide, lead (II) iodide, tin (II) acetate, tin (II) formate, tin (II) fluoride, tin (II) chloride, tin (II) bromide, tin (II) iodide, germanium (II) acetate, germanium (II) formate, germanium (II) fluoride, germanium (II) chloride, germanium (II) bromide or germanium (II) iodide. In some cases, the first precursor compound comprises lead (II) acetate. In some cases, the first precursor compound comprises lead (II) iodide.
[0177] The M precursor is typically a compound of formula MY2. Preferably, the M precursor is a compound of formula SnI2, SnBr2, SnCl2, PbI2, PbBr2 or PbCl2.
[0178] The M precursor may be a compound of formula MY3, wherein M is Bi 3+ or Sb 3+ , and Y is F – , Cl – Br – ,I – 、SCN – 、BF4 – , formate ion or acetate ion. Preferably, M is Bi 3+ , and Y is Cl – Br – -or I – In this case, the A / M / X material typically comprises a bismuth or antimony halide metal salt.
[0179] The M precursor may be a compound of formula MY4, wherein M is Pd 4+ , W 4+ 、Re 4+ , Os 4+ , Ir 4+ , Pt 4+ Sn 4+ , Pb 4+ ,Ge 4+ or Te4+ , and Y is F – , Cl – Br – ,I – 、SCN – 、BF4 – , formate ion or acetate ion. Preferably, M is Sn 4+ , Pd 4+ Or Ge 4+ , and Y is Cl – Br – -or I – In this case, the A / M / X material typically comprises a metal hexahalide salt.
[0180] Typically, the total concentration of [M] cations in the membrane-forming solution is 0.01M to 10M, such as 0.1M to 5M, 0.25M to 2.5M, 0.5M to 1.5M, preferably 0.75M to 1.25M.
[0181] [A] cation and [X] anion
[0182] Typically, the one or more A cations are monovalent cations. [A] typically includes one or more A cations that can be organic and / or inorganic monovalent cations. For example, [A] can include at least two A cations that can be organic and / or inorganic monovalent cations. Thus, the formula [A] a [M] b [X] c The compound may be a mixed cation perovskite. [A] may include at least one A cation that is an organic cation and at least one A cation that is an inorganic cation. [A] may include at least two A cations that are both organic cations. [A] may include at least two A cations that are both inorganic cations.
[0183] When the A species is an inorganic monovalent cation, A is typically an alkali metal monovalent cation (i.e., a monovalent cation of a metal found in Group 1 of the Periodic Table of Elements), such as Li + 、Na + , K + , Rb + , Cs + , for example Cs + or Rb + Typically, [A] comprises at least one organic monovalent cation. When the A species is an organic monovalent cation, A is typically an ammonium cation, such as a methylammonium ion; or an iminium cation, such as a formamidine ion.
[0184] Each A cation may be selected from: alkali metal cations, such as Li + 、Na + , K+ , Rb + , Cs + ; Formula [R1R2R3R4N] + A cation, wherein R1, R2, R3, and R4 are each independently selected from hydrogen, unsubstituted or substituted C 1-20 Alkyl and unsubstituted or substituted C 6-12 Aryl, and at least one of R1, R2, R3 and R4 is not hydrogen; formula [R5R6N=CH-NR7R8] + wherein R5, R6, R7 and R8 are each independently selected from hydrogen, unsubstituted or substituted C 1-20 Alkyl and unsubstituted or substituted C 6-12 Aryl; and C 1-10 Alkyl ammonium ion, C 2-10 Alkenyl ammonium ion, C 1-10 Alkyl iminium ion, C 3-10 Cycloalkylammonium ions and C 3-10 Cycloalkyl iminium ions, each of which is unsubstituted or substituted with a cycloalkyl iminium ion selected from C 1-6 Alkylamino, C 1-6 Alkyl imino, C 1-6 Alkyl, C 2-6 Alkenyl, C 3-6 Cycloalkyl and C 6-12 One or more substituents of the aryl group.
[0185] Preferably, each A cation is selected from Cs + , Rb + 、Methylammonium ion [(CH3NH3) + ], ethylammonium ion [(CH3CH2NH3) + ]、propylammonium ion [(CH3CH2CH2NH3) + ]、Butyl ammonium ion [(CH3CH2CH2CH2NH3) + ]、pentyl ammonium ion [(CH3CH2CH2CH2CH2NH3) + ]、hexyl ammonium ion [(CH3CH2CH2CH2CH2CH2NH3) + ]、Heptyl ammonium ion [(CH3CH2CH2CH2CH2CH2CH2CH2NH3) + ]、octylammonium ion [(CH3CH2CH2CH2CH2CH2CH2CH2CH2NH3) + ], tetramethylammonium ion [(N(CH3)4) + ]、Formamidinium ion [(H2N-C(H)=NH2) + ]、1-aminoethyl-1-imide ion [(H2N–C(CH3)=NH2) +], guanidine [(H2N-C(NH2)=NH2) + ].
[0186] [A] typically includes one, two or three A monovalent cations. [A] may include a single cation selected from the following: methylammonium ion [(CH3NH3) + ], ethylammonium ion [(CH3CH2NH3) + ]、propylammonium ion [(CH3CH2CH2NH3) + ], dimethylammonium ion [(CH3)2NH + ], tetramethylammonium ion [(N(CH3)4) + ]、Formamidinium ion [(H2N-C(H)=NH2) + ]、1-aminoethyl-1-imide ion [(H2N–C(CH3)=NH2) + ], guanidine [(H2N-C(NH2)=NH2) + ]、Cs + and Rb + For example, [A] may include a single cation, methylammonium ion [(CH3NH3) + ].
[0187] Alternatively, [A] may include two cations selected from this group, such as Cs + and formamidinium ion [(H2N-C(H)=NH2) + ], or for example Cs + and Rb + , or for example, methylammonium ion [(CH3NH3) + ] and formamidinium ion [(H2N-C(H)=NH2) + ].
[0188] Typically, in the methods of the present invention, [A] comprises a compound of the formula [R1NH3] + A cation wherein R1 is an unsubstituted C 1-10 alkyl, and the organic amine includes unsubstituted (C 1-10 The characteristics of the organic amine in the solvent can be matched with the alkylamine corresponding to the cation A when protonated. Therefore, the formula [R1NH3] + A cation on C 1-10 Alkyl groups and unsubstituted (C 1-10 C on alkyl)amine 1-10The alkyl groups may be the same. For example, the A cation may be a methylammonium ion, and the organic amine may include methylamine; or the A cation may be an ethylammonium ion, and the organic amine may include ethylamine; or the A cation may be a propylammonium ion, and the organic amine may include propylamine; or the A cation may be a butylammonium ion, and the organic amine may include butylamine; or the A cation may be a pentylammonium ion, and the organic amine may include pentylamine; or the A cation may be a hexylammonium ion, and the organic amine may include hexylamine; or the A cation may be a heptylammonium ion, and the organic amine may include heptylamine; or the A cation may be an octylammonium ion, and the organic amine may include octylamine. In a preferred embodiment, [A] includes a methylammonium ion, and the organic amine includes methylamine.
[0189] [X] comprises one or more X anions. Typically, [X] comprises one or more halide anions, i.e., selected from F – , Cl – Br – and I – Typically, each X anion is a halide ion. [X] typically includes one, two or three X anions, and they are typically selected from Br – , Cl – and I – -. Typically, [X] includes two or more different halide anions. [X] may, for example, consist of two X anions, such as Cl and Br; Br and I; or Cl and I. Thus, formula [A] a [M] b [X] c Compounds of the formula [A] generally include mixed halide perovskites. When [A] includes one or more organic cations, the formula [A] a [M] b [X] c The compound may be an organic-inorganic metal halide perovskite.
[0190] The film-forming solution may further comprise one or more A cations as described herein. Thus, it may be preferred that the film-forming solution comprises each of the one or more A cations present in [A]. The method of the present invention may comprise the step of forming the film-forming solution by dissolving at least one A precursor in a solvent. As discussed in more detail below, an A precursor is a compound comprising one or more A cations present in [A]. When [A] (i.e., formula [A] a [M] b [X] c When [A] in the compound comprises only one type of A cation, only one A precursor is required in the method of the present invention.
[0191] The film-forming solution may further comprise one or more X anions as described herein. With regard to the source of the X anions in the method of the present invention, it may not be necessary to provide a separate X precursor in the method of the present invention. This is because in certain embodiments, the A precursor (or in the case where the method involves multiple A precursors, at least one of them) and / or the M precursor (or in the case where the method involves multiple M precursors, at least one of them) is a salt comprising one or more X anions, such as a halide salt. In a preferred embodiment, the A precursor (or multiple A precursors) and the M precursor (or multiple M precursors) together comprise each X cation present in [X].
[0192] For example, SnF2 or SnCl2 can be added as additives to the film-forming solution to form a film. - ) or chlorine (Cl - ) is added to the film-forming solution as a "dopant". Pb:Sn perovskites in particular can benefit from further additions of SnF2 to the solution.
[0193] The film-forming solution generally further comprises one or more A cations as described herein and one or more X anions as described herein. In this embodiment, the film-forming solution comprises one or more A cations, one or more M cations and one or more X anions. Thus, in one embodiment, the film-forming solution may comprise a preparation of formula [A] a [M] b [X] c All the ions required for the compound.
[0194] Both the A cation and the X anion may be derived from the same precursor compound or compounds, which are dissolved in a solvent as described herein to form a film-forming solution. Preferably, the A / X precursor compound is a compound of formula [A][X], wherein: [A] comprises one or more A cations as described herein; and [X] comprises one or more X anions as described herein. The A / X precursor compound is typically a compound of formula AX, wherein X is a halide ion and the A cation is as defined herein. When in formula [A] a [M] b [X] c When more than one A cation or more than one X anion is present in the compound, more than one compound of formula AX may be dissolved in the film-forming solution.
[0195] The A / X precursor compound(s) may be, for example, selected from CH3NH3Cl, CH3NH3Br, CH3NH3I, CH3CH2NH3Cl, CH3CH2NH3Br, CH3CH2NH3I, CH3CH2CH2NH3Cl, CH3CH2CH2NH3Br, CH3CH2CH2NH3I, N(CH3)4Cl, N(CH3)4Br, N(CH3)4I, (H2N-C(H)=NH2)Cl , (H2N–C(H)=NH2)Br, (H2N–C(H)=NH2)I, (H2N–C(CH3)=NH2)Cl, (H2N–C(CH3)=NH2)Br, (H2N–C(CH3)=NH2 )I, (H2N-C(NH2)=NH2)Cl, (H2N-C(NH2)=NH2)Br, (H2N-C(NH2)=NH2)I, CsCl, CsBr, CsI, RbCl, RbBr and RbI.
[0196] In one embodiment, the membrane-forming solution comprises an excess of A cations relative to M cations. In this context, the term "excess" means that the molar ratio of one ion to another ion is greater than the formula [A] a [M] b [X] c Typically, the ratio of A cations to M cations in the membrane-forming solution is 1:1 to 5:1, such as 1:1 to 4:1, 1:1 to 3:1, 1:1 to 2:1, 1:1 to 1.5:1, 1:1 to 1.25:1, or 1:1 to 1.1:1.
[0197] In one embodiment, the membrane-forming solution comprises an excess of M cations relative to A cations. Typically, the ratio of M cations to A cations in the membrane-forming solution is 1:1 to 5:1, such as 1:1 to 4:1, 1:1 to 3:1, 1:1 to 2:1, 1:1 to 1.5:1, 1:1 to 1.25:1, or 1:1 to 1.2:1. When the formula [A] a [M] b [X] c When the compound comprises two M cations, preferably, [M] comprises Pb 2+ and Sn 2+ .
[0198] Therefore, typically, the total concentration of [A] cations in the membrane-forming solution is 0.01M to 10M, such as 0.1M to 5M, 0.25M to 2.5M, 0.5M to 1.5M, preferably 0.6M to 1.4M.
[0199] Typically, the total concentration of X anions depends on the total concentration of A and / or M cations. For example, when using A / X precursor compounds and / or M precursor compounds containing one or more X anions, the total concentration of X anions will depend on the total amount of A / X precursor compounds and / or M precursor compounds present as described above.
[0200] Formula [A] a [M] b [X] c Compounds - More details
[0201] Usually, a=1, b=1, and c=3. Therefore, formula [A] a [M] b [X] c The compound may be a compound of formula [A][M][X]3, wherein [A], [M] and [X] are as described herein. Typically, the crystalline A / M / X material comprises: a perovskite of formula (I):
[0202] [A][M][X]3 (I)
[0203] Wherein: [A] comprises one or more A cations, wherein the A cations are monovalent cations; [M] comprises one or more M cations, wherein the M cations are metal or metalloid divalent cations; and [X] comprises one or more anions, wherein the anions are halide anions.
[0204] In some embodiments, the perovskite of formula (I) comprises a single A cation, a single M cation, and a single X cation. That is, the perovskite is a perovskite of formula (IA):
[0205] AMX3 (IA)
[0206] Wherein A, M and X are as defined above. In a preferred embodiment, A is selected from (CH3NH3) + 、(CH3CH2NH3) + 、(CH3CH2CH2NH3) + 、(N(CH3)4) + 、(H2N–C(H)=NH2) + 、(H2N–C(CH3)=NH2) + 、(H2N–C(NH2)=NH2) + , Cs + and Rb + ; M is Pb 2+ or Sn 2+ , and X is selected from Br - , Cl - and I - .
[0207] For example, the crystalline A / M / X material may comprise or consist essentially of a perovskite compound of formula (IA) selected from the group consisting of APbI3, APbBr3, APbCl3, ASnI3, ASnBr3, and ASnCl3, wherein A is a cation as described herein.
[0208] For example, the crystalline A / M / X material may comprise or consist essentially of a perovskite compound of formula (IA) selected from the group consisting of CH3NH3PbI3, CH3NH3PbBr3, CH3NH3PbCl3, CH3NH3SnI3, CH3NH3SnBr3, CH3NH3SnCl3, CsPbI3, CsPbBr3, CsPbCl3, CsSnI3, CsSnB r3, CsSnCl3, (H2N–C(H)=NH2)PbI3, (H2N–C(H)=NH2)PbBr3, (H2N–C(H)=NH2)PbCl3, (H2N–C(H)=NH2)SnI3, (H2N–C(H)=NH2)SnBr3 and (H2N–C(H)=NH2)SnCl3; in particular CH3NH3PbI3 or CH3NH3PbBr3, preferably CH3NH3PbI3.
[0209] In one embodiment, the perovskite is a perovskite of formula (IB):
[0210] [A I x A II 1-x ]MX3 (IB)
[0211] Among them A I and A II As defined above for A, wherein M and X are as defined above, and wherein x is greater than 0 and less than 1. In a preferred embodiment, A I and A II Each selected from (CH3NH3) + 、(CH3CH2NH3) + 、(CH3CH2CH2NH3) + 、(N(CH3)4) + 、(H2N–C(H)=NH2) + 、(H2N–C(CH3)=NH2) + 、(H2N–C(NH2)=NH2) + , Cs + and Rb + ; M is Pb 2+or Sn 2+ , and X is selected from Br - , Cl - and I - . A I and A II For example, they can be (H2N-C(H)=NH2) + and Cs + , or they can be (CH3NH3) + and (H2N-C(H)=NH2) + Alternatively, they can be Cs + and Rb + .
[0212] For example, the crystalline A / M / X material may comprise or consist essentially of a perovskite compound of formula (IB) selected from the group consisting of: (Cs x R 1-x )PbBr3、(Cs x R 1-x )PbCl3、(Cs x R 1-x )PbI3,
[0213] [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]PbCl3, [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]PbBr3,
[0214] [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]PbI3, [(CH3NH3) x Cs 1-x ]PbCl3, [(CH3NH3) x Cs 1-x ]PbBr3,
[0215] [(CH3NH3) x Cs 1-x ]PbI3, [(H2N–C(H)=NH2) x Cs 1-x ]PbCl3, [(H2N–C(H)=NH2) x Cs 1-x ]PbBr3,
[0216] [(H2N–C(H)=NH2) x Cs 1-x]PbI3, [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]SnCl3,
[0217] [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]SnBr3, [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]SnI3,
[0218] [(CH3NH3) x Cs 1-x ]SnCl3, [(CH3NH3) x Cs 1-x ]SnBr3, [(CH3NH3) x Cs 1-x ]SnI3,
[0219] [(H2N–C(H)=NH2) x Cs 1-x ]SnCl3, [(H2N–C(H)=NH2) x Cs 1-x ]SnBr3 and [(H2N–C(H)=NH2) x Cs 1-x ]SnI3, wherein x is greater than 0 and less than 1, for example, x can be 0.01 to 0.99, or 0.05 to 0.95, or 0.1 to 0.9.
[0220] In one embodiment, the perovskite is a perovskite compound of formula (IC):
[0221] AM[X I y X II 1-y ]3 (IC)
[0222] wherein A and M are as defined above, wherein X I and X II As defined above with respect to X, and wherein y is greater than 0 and less than 1. In a preferred embodiment, A is selected from (CH3NH3) + 、(CH3CH2NH3) + 、(CH3CH2CH2NH3) + 、(N(CH3)4) + 、(H2N–C(H)=NH2) + 、(H2N–C(CH3)=NH2) + 、(H2N–C(NH2)=NH2)+ , Cs + and Rb + ; M is Pb 2+ or Sn 2+ ; and X I and X II Each selected from Br - , Cl - and I - .
[0223] For example, the crystalline A / M / X material may comprise or consist essentially of a perovskite compound of formula (IC) selected from the group consisting of: APb[Br y I 1-y ]3.APb[Br y Cl 1-y ]3.APb[I y Cl 1-y ]3.ASn[Br y I 1-y ]3.ASn[Br y Cl 1-y ]3.ASn[I y Cl 1-y ]3, wherein y is greater than 0 and less than 1, and wherein A is a cation as described herein. y can be from 0.01 to 0.99. For example, y can be from 0.05 to 0.95, or from 0.1 to 0.9.
[0224] For example, the crystalline A / M / X material may comprise or consist essentially of a perovskite compound of formula (IC) selected from the group consisting of: CH3NH3Pb[Br y I 1-y ]3、CH3NH3Pb[Br y Cl 1-y ]3, CH3NH3Pb[I y Cl 1-y ]3、CH3NH3Sn[Br y I 1-y ]3、CH3NH3Sn[Br y Cl 1-y ]3, CH3NH3Sn[I y Cl 1-y ]3. CsPb[Br y I 1-y ]3. CsPb[Br y Cl 1-y ]3. CsPb[I y Cl 1-y ]3. CsSn[Br y I1-y ]3. CsSn[Br y Cl 1-y ]3. CsSn[I y Cl 1-y ]3. (H2N–C(H)=NH2)Pb[Br y I 1-y ]3. (H2N–C(H)=NH2)Pb[Br y Cl 1-y ]3. (H2N–C(H)=NH2)Pb[I y Cl 1-y ]3. (H2N–C(H)=NH2)Sn[Br y I 1-y ]3. (H2N–C(H)=NH2)Sn[Br y Cl 1-y ]3 and (H2N–C(H)=NH2)Sn[I y Cl 1-y ]3, wherein y is greater than 0 and less than 1, for example, y can be 0.01 to 0.99, or 0.05 to 0.95, or 0.1 to 0.9
[0225] In a preferred embodiment, the perovskite is a perovskite of formula (ID):
[0226] [A I x A II 1-x ]M[X I y X II 1-y ]3 (ID)
[0227] Among them A I and A II As defined in the text regarding A, M is as defined above, and X I and X II As defined above with respect to X, and wherein x and y are both greater than 0 and less than 1. In a preferred embodiment, A I and A II Each selected from (CH3NH3) + 、(CH3CH2NH3) + 、(CH3CH2CH2NH3) + 、(N(CH3)4) + 、(H2N–C(H)=NH2) + 、(H2N–C(CH3)=NH2) + 、(H2N–C(NH2)=NH2) + , Cs+ and Rb + ; M is Pb 2+ or Sn 2+ , and X I and X II Each selected from Br - , Cl - and I - .
[0228] For example, the crystalline A / M / X material may comprise or consist essentially of a perovskite compound of formula (ID) selected from the group consisting of: (Cs x R 1-x )Pb(Br y Cl 1-y )3、(Cs x R 1-x )Pb(Br y I 1-y )3、(Cs x R 1-x )Pb(Cl y I 1-y )3, [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Pb[Br y I 1-y ]3, [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Pb[Br y Cl 1-y ]3. [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Pb[I y Cl 1-y ]3, [(CH3NH3) x Cs 1-x ]Pb[Br y I 1-y ]3. [(CH3NH3) x Cs 1-x ]Pb[Br y Cl 1-y ]3. [(CH3NH3) x Cs 1-x ]Pb[I y Cl 1-y ]3. [(H2N–C(H)=NH2) x Cs 1-x ]Pb[Br y I 1-y]3. [(H2N–C(H)=NH2) x Cs 1-x ]Pb[Br y Cl 1-y ]3. [(H2N–C(H)=NH2) x Cs 1-x ]Pb[I y Cl 1-y ]3. [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Sn[Br y I 1-y ]3. [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Sn[Br y Cl 1-y ]3. [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Sn[I y Cl 1-y ]3. [(CH3NH3) x Cs 1-x ]Sn[Br y I 1-y ]3. [(CH3NH3) x Cs 1-x ]Sn[Br y Cl 1-y ]3. [(CH3NH3) x Cs 1-x ]Sn[I y Cl 1-y ]3. [(H2N–C(H)=NH2) x Cs 1-x ]Sn[Br y I 1-y ]3. [(H2N–C(H)=NH2) x Cs 1-x ]Sn[Br y Cl 1-y ]3, and [(H2N–C(H)=NH2) x Cs 1-x ]Sn[I y Cl 1-y ]3, wherein x and y are both greater than 0 and less than 1, for example, x and y can both be 0.01 to 0.99, or 0.05 to 0.95, or 0.1 to 0.9.
[0229] In one embodiment, the perovskite is a perovskite of formula (IE):
[0230] A[M I z M II 1-z ]X3 (IE)
[0231] Among them, M I and M II As defined above for M, A and X are as defined above, and wherein z is greater than 0 and less than 1. In a preferred embodiment, A is selected from (CH3NH3) + 、(CH3CH2NH3) + 、(CH3CH2CH2NH3) + 、(N(CH3)4) + 、(H2N–C(H)=NH2) + 、(H2N–C(CH3)=NH2) + 、(H2N–C(NH2)=NH2) + , Cs + and Rb + ;M I It is Pb 2+ , and M II It's Sn 2 + , and X is selected from Br - , Cl - and I - .
[0232] For example, the crystalline A / M / X material may comprise or consist essentially of a perovskite compound of formula (IE) selected from the group consisting of: CH3NH3[Pb z Sn 1-z ]Cl3、CH3NH3[Pb z Sn 1-z ]Br3、CH3NH3[Pb z Sn 1-z ]I3, Cs[Pb z Sn 1-z ]Cl3、Cs[Pb z Sn 1-z ]Br3、Cs[Pb z Sn 1-z ]I3, (H2N–C(H)=NH2)[Pb z Sn 1-z ]Cl3、(H2N–C(H)=NH2)[Pb z Sn 1-z ]Br3 and (H2N–C(H)=NH2)[Pb z Sn 1-z]I3, wherein z is greater than 0 and less than 1, for example, z can be 0.01 to 0.99, or 0.05 to 0.95, or 0.1 to 0.9.
[0233] In one embodiment, the perovskite is a perovskite of formula (IF):
[0234] [A I x A II 1-x ][M I z M II 1-z ]X3 (IF)
[0235] Among them A I and A II As defined above with respect to A, wherein M I and M II As defined above for M, and X is as defined above, and wherein x and z are both greater than 0 and less than 1. In a preferred embodiment, A I and A II Each selected from (CH3NH3) + 、(CH3CH2NH3) + 、(CH3CH2CH2NH3) + 、(N(CH3)4) + 、(H2N–C(H)=NH2) + 、(H2N–C(CH3)=NH2) + 、(H2N–C(NH2)=NH2) + , Cs + and Rb + ;M I It is Pb 2+ , and M II It's Sn 2+ , and X is selected from Br - , Cl - and I - . A I and A II For example, they can be (H2N-C(H)=NH2) + and Cs + , or they can be (CH3NH3) + and (H2N-C(H)=NH2) + Alternatively, they can be Cs + and Rb + .
[0236] For example, the crystalline A / M / X material may comprise or consist essentially of a perovskite compound of formula (IF) selected from the group consisting of: [(CH3NH3) x (H2N–C(H)=NH2) 1-x ][Pb z Sn 1-z ]Cl3, [(CH3NH3) x (H2N–C(H)=NH2) 1-x ][Pb z Sn 1-z ]Br3, [(CH3NH3) x (H2N–C(H)=NH2) 1-x ][Pb z Sn 1-z ]I3, [(CH3NH3) x Cs 1-x ][Pb z Sn 1-z ]Cl3, [(CH3NH3) x Cs 1-x ][Pb z Sn 1-z ]Br3, [(CH3NH3) x Cs 1-x ][Pb z Sn 1-z ]I3, [(H2N–C(H)=NH2) x Cs 1-x ][Pb z Sn 1-z ]Cl3, [(H2N–C(H)=NH2) x Cs 1-x ][Pb z Sn 1-z ]Br3, [(H2N–C(H)=NH2) x Cs 1-x ][Pb z Sn 1-z ]I3, wherein x and z are both greater than 0 and less than 1, for example, x and z can each be 0.01 to 0.99, or 0.05 to 0.95, or 0.1 to 0.9.
[0237] In one embodiment, the perovskite is a perovskite compound of formula (IG):
[0238] A[M I z M II 1-z ][X I y XII 1-y ]3 (IG)
[0239] Where A is as defined above, M I and M II As defined above with respect to M, and wherein X I and X II As defined above for X, and wherein y and z are both greater than 0 and less than 1. In a preferred embodiment, A is selected from (CH3NH3) + 、(CH3CH2NH3) + 、(CH3CH2CH2NH3) + 、(N(CH3)4) + 、(H2N–C(H)=NH2) + 、(H2N–C(CH3)=NH2) + 、(H2N–C(NH2)=NH2) + , Cs + and Rb + ;M I It is Pb 2+ , and M II It's Sn 2+ , and X I and X II Each selected from Br - , Cl - and I - .
[0240] For example, the crystalline A / M / X material may comprise or consist essentially of a perovskite compound of formula (IG) selected from the group consisting of: A[Pb z Sn 1-z ][Br y I 1-y ]3. A[Pb z Sn 1-z ][Br y Cl 1-y ]3. A[Pb z Sn 1-z ][I y Cl 1-y ]3, wherein y and z are both greater than 0 and less than 1, and wherein A is a cation as described herein. y and z may each be 0.01 to 0.99. For example, y and z may each be 0.05 to 0.95, or 0.1 to 0.9.
[0241] For example, the crystalline A / M / X material may comprise or consist essentially of a perovskite compound of formula (IG) selected from the group consisting of: CH3NH3[Pb z Sn 1-z ][Br y I 1-y ]3, CH3NH3[Pb z Sn 1-z ][Br y Cl 1-y ]3, CH3NH3[Pb z Sn 1-z ][I y Cl 1-y ]3. Cs[Pb z Sn 1-z ][Br y I 1-y ]3. Cs[Pb z Sn 1-z ][Br y Cl 1-y ]3. Cs[Pb z Sn 1-z ][I y Cl 1-y ]3. (H2N–C(H)=NH2)[Pb z Sn 1-z ][Br y I 1-y ]3. (H2N–C(H)=NH2)[Pb z Sn 1-z ][Br y Cl 1-y ]3, and (H2N–C(H)=NH2)[Pb z Sn 1-z ][I y Cl 1-y ]3, wherein y and z are both greater than 0 and less than 1, for example, y and z can each be 0.01 to 0.99, or 0.05 to 0.95, or 0.1 to 0.9.
[0242] In a preferred embodiment, the perovskite is a perovskite of formula (IH):
[0243] [A I x A II 1-x ][M I z M II 1-z ][X I y X II1-y ]3 (IH)
[0244] Among them A I and A II As defined above for A, M I and M II As defined above for M, X I and X II As defined above with respect to X, and wherein x, y and z are all greater than 0 and less than 0. In a preferred embodiment, A I and A II Each selected from (CH3NH3) + 、(CH3CH2NH3) + 、(CH3CH2CH2NH3) + 、(N(CH3)4) + 、(H2N–C(H)=NH2) + 、(H2N–C(CH3)=NH2) + 、(H2N–C(NH2)=NH2) + , Cs + and Rb + ;M I It is Pb 2+ , and M II It's Sn 2+ ; and X I and X II Selected from Br - , Cl - and I - .
[0245] For example, the crystalline A / M / X material may include or consist essentially of a perovskite compound of formula (IH) selected from the group consisting of: [(CH3NH3) x (H2N–C(H)=NH2) 1-x ][Pb z Sn 1-z ][Br y I 1-y ]3. [(CH3NH3) x (H2N–C(H)=NH2) 1-x ][Pb z Sn 1-z ][Br y Cl 1-y ]3. (CH3NH3) x (H2N–C(H)=NH2) 1-x ][Pb z Sn 1-z ][Iy Cl 1-y ]3. [(CH3NH3) x Cs 1-x ][Pb z Sn 1-z ][Br y I 1-y ]3. [(CH3NH3) x Cs 1-x ][Pb z Sn 1-z ][Br y Cl 1-y ]3. [(CH3NH3) x Cs 1-x ][Pb z Sn 1-z ][I y Cl 1-y ]3. [(H2N–C(H)=NH2) x Cs 1-x ][Pb z Sn 1-z ][Br y I 1-y ]3. [(H2N–C(H)=NH2) x Cs 1-x ][Pb z Sn 1-z ][Br y Cl 1-y ]3 and [(H2N–C(H)=NH2) x Cs 1-x ][Pb z Sn 1-z ][I y Cl 1-y ]3, wherein x, y and z are all greater than 0 and less than 1, for example, x, y and z can each be 0.01 to 0.99, or 0.05 to 0.95, or 0.1 to 0.9.
[0246] In one embodiment, a = 2, b = 1, and c = 4. In this embodiment, the crystalline A / M / X material comprises a compound of formula (II) ("2D layered perovskite"):
[0247] [A]2[M][X]4 (II)
[0248] Wherein [A] comprises one or more A cations, the A cations being monovalent cations; [M] comprises one or more M cations, the M cations being metal or metalloid divalent cations; and [X] comprises one or more anions, the anions being halide anions. In this embodiment, the A and M cations and the X anions are as defined above.
[0249] In another embodiment, a = 2, b = 1, and c = 6. In this embodiment, in this case, the crystalline A / M / X material may include a hexahalide metal salt of formula (III):
[0250] [A]2[M][X]6 (III)
[0251] Wherein: [A] comprises one or more A cations, wherein the A cations are monovalent cations; [M] comprises one or more M cations, wherein the M cations are tetravalent cations of metals or metalloids; and [X] comprises one or more anions, wherein the anions are halide anions.
[0252] In a preferred embodiment, the hexahalide metal salt of formula (III) can be a mixed monovalent cation hexahalide metal salt. In the mixed monovalent cation hexahalide metal salt, [A] includes at least two A cations that are monovalent cations; [M] includes at least one M cation that is a metal or metalloid tetravalent cation (and, typically, [M] includes a single M cation that is a metal or metalloid tetravalent cation); and [X] includes at least one anion that is a halide anion (and, typically, [X] includes a single halide anion or two types of halide anions). In the mixed metal hexahalide metal salt, [A] includes at least one monovalent cation (and, typically, [A] is a single monovalent cation or two types of monovalent cations); [M] includes at least two metal or metalloid tetravalent cations (e.g., Ge 4+ and Sn 4+ ); and [X] comprises at least one halide anion (and, typically, [X] is a single halide anion or two types of halide anions). In a mixed halide hexahalide metal salt, [A] comprises at least one monovalent cation (and, typically, [A] is a single monovalent cation or two types of monovalent cations); [M] comprises at least one metal or metalloid tetravalent cation (and typically, [M] is a single metal tetravalent cation); and [X] comprises at least two halide anions, such as Br – and Cl - , or Br - and I - .
[0253] [A] may include at least one A monovalent cation selected from any suitable monovalent cation, such as those described above for perovskites. In the case of a hexahalide metal salt, each A cation is typically selected from Li + 、Na + , K + , Rb + , Cs + NH4 +and a monovalent organic cation. A monovalent organic cation is a single positively charged organic cation, which may have a molecular weight of no more than 500 g / mol, for example. For example, [A] may be a single A cation selected from Li + 、Na + , K + , Rb + , Cs + NH4 + and a monovalent organic cation. [A] preferably comprises at least one A cation selected from Rb + , Cs + NH4 + and a monovalent organic cation. For example, [A] may be selected from Li + 、Na + , K + , Rb + , Cs + and NH4 + In another embodiment, [A] may be at least one monovalent organic A cation. For example, [A] may be a single monovalent organic A cation. In one embodiment, [A] is (CH3NH3) + In another embodiment, [A] is (H2N-C(H)=NH2) + .
[0254] Preferably, [A] comprises two or more types of A cations. [A] may be a single A monovalent cation, or indeed two A monovalent cations, each independently selected from K + , Rb + , Cs + NH4 + 、(CH3NH3) + 、(CH3CH2NH3) + 、(CH3CH2CH2NH3) + 、(N(CH3)4) + 、(N(CH2CH3)4) + 、(N(CH2CH2CH3)4) + 、(H2N–C(H)=NH2) + and (H2N–C(CH3)=NH2) + .
[0255] [M] may include one or more M cations selected from suitable metal or metalloid tetravalent cations. Metals include elements from Groups 3 to 12 of the periodic table, as well as Ga, In, Tl, Sn, Pb, Bi, and Po. Metalloids include Si, Ge, As, Sb, and Te. For example, [M] may include at least one M cation selected from Ti 4+ 、V 4+ , Mn 4+ , Fe 4+ 、Co 4+ 、Zr 4+ , Nb 4+ 、Mo 4+ 、Ru 4+ , Rh 4+ , Pd 4+ , Hf 4+ 、 4+ , W 4+ 、Re 4+ , Os 4+ , Ir 4+ , Pt 4+ Sn 4+ , Pb 4+ 、Po 4+ 、Si 4+ ,Ge 4 and Te 4+ Typically, [M] comprises a metal or metalloid tetravalent cation selected from Pd 4+ , W 4+ 、Re 4+ , Os 4+ , Ir 4+ , Pt 4 + Sn 4+ , Pb 4+ ,Ge 4+ and Te 4+ At least one metal or metalloid tetravalent cation. For example, [M] can be selected from Pd 4+ , W 4 + 、Re 4+ , Os 4+ , Ir 4+ , Pt 4+ Sn 4+ , Pb 4+ ,Ge 4+ and Te 4+ A single metal or metalloid tetravalent cation.
[0256] Typically, [M] comprises at least one M cation selected from Sn 4+ 、Te 4+,Ge 4+ and Re 4+ In one embodiment, [M] comprises at least one M cation selected from Pb 4+ Sn 4+ 、Te 4+ ,Ge 4+ and Re 4+ For example, [M] may include an M cation selected from Pb 4+ Sn 4+ 、Te 4+ and Ge 4+ Preferably, [M] comprises at least one metal or metalloid tetravalent cation selected from Sn 4+ 、Te 4+ and Ge 4+ At least one metal or metalloid tetravalent cation. As discussed above, the metal hexahalide compound can be a mixed metal or a single metal hexahalide. Preferably, the metal hexahalide compound is a single metal hexahalide compound. More preferably, [M] is selected from Sn 4+ 、Te 4+ and Ge 4+ For example, [M] can be a single metal or metalloid tetravalent cation, Te 4+ For example, [M] can be a single metal or metalloid tetravalent cation, Ge 4+ Most preferably, [M] is a single metal or metalloid tetravalent cation, Sn 4+ .
[0257] [X] may include at least one X anion, wherein the X anion is a halide anion. Thus, [X] includes a – , Cl – Br – , and I – Typically, [X] comprises at least one halide anion selected from Cl – Br – , and I – The hexahalide metal salt compound may be a mixed halide hexahalide metal salt or a single halide hexahalide metal salt. If the hexahalide metal salt is mixed, then [X] comprises a member selected from F – , Cl – Br – , and I – Typically, in the mixed halide, [X] comprises a compound selected from F – , Cl – Br –, and I – Two halide anions.
[0258] In some embodiments, [A] is a single monovalent cation and [M] is a single metal or metalloid tetravalent cation. Thus, the crystalline A / M / X material may, for example, include a hexahalide metal salt compound of formula (IIIA)
[0259] A2M[X]6 (IIIA)
[0260] Wherein: A is a monovalent cation; M is a metal or metalloid tetravalent cation; and [X] is at least one halide anion. [X] can be selected from F – , Cl – Br – , and I – , preferably selected from Cl – Br – , and I – In formula (IIIA), [X] is preferably selected from Cl – Br – , and I – One or two halide anions.
[0261] The crystalline A / M / X material may, for example, comprise or consist essentially of a hexahalide metal salt compound of formula (IIIB):
[0262] A2MX 6-y X′ y (IIIB)
[0263] Wherein: A is a monovalent cation (i.e., the second cation); M is a metal or metalloid tetravalent cation (i.e., the first cation); X and X' are each independently (different) halide anions (i.e., two second anions); and y is 0 to 6. When y is 0 or 6, the hexahalide metal salt compound is a single halide. When y is 0.01 to 5.99, the compound is a mixed halide hexahalide metal salt compound. When the compound is a mixed halide, y can be 0.05 to 5.95. For example, y can be 1.00 to 5.00.
[0264] The hexahalide metal salt compound may be, for example, A2SnF 6-y Cl y 、A2SnF 6-y Br y 、A2SnF 6-y I y 、A2SnCl 6-y Br y 、A2SnCl 6-y Iy 、A2SnBr 6-y I y 、A2TeF 6-y Cl y 、A2TeF 6-y Br y 、A2TeF 6-y I y 、A2TeCl 6-y Br y 、A2TeCl 6-y I y 、A2TeBr 6-y I y 、A2GeF 6-y Cl y 、A2GeF 6-y Br y 、A2GeF 6-y I y 、A2GeCl 6-y Br y 、A2GeCl 6-y I y ,A2GeBr 6-y I y 、A2ReF 6-y Cl y 、A2ReF 6-y Br y 、A2ReF 6-y I y 、A2ReCl 6-y Br y 、A2ReCl 6-y I y or A2ReBr 6-y I y , where: A is K + , Rb + , Cs + , (R 1 NH3) + ,(NR 2 4) + or (H2N–C(R 1 )=NH2) + , where R 1 is H, substituted or unsubstituted C 1-20 alkyl, or substituted or unsubstituted aryl, and R 2 is substituted or unsubstituted C 1-10 alkyl; and y is 0 to 6. Optionally, y is 0.01 to 5.99. If the hexahalide metal salt compound is a mixed halide, y is typically 1.00 to 5.00. A may be as defined above. For example, A may be Cs + NH4+ 、(CH3NH3) + 、(CH3CH2NH3) + 、(N(CH3)4) + 、(N(CH2CH3)4) + 、(H2N–C(H)=NH2) + or (H2N–C(CH3)=NH2) + , for example Cs + NH4 + or (CH3NH3) + .
[0265] The hexahalide metal salt compound may typically be A2SnF 6-y Cl y 、A2SnF 6-y Br y 、A2SnF 6-y I y 、A2SnCl 6-y Br y 、A2SnCl 6-y I y or A2SnBr 6-y I y , where: A is K + , Rb + , Cs + , (R 1 NH3) + ,(NR 2 4) + or (H2N–C(R 1 )=NH2) + , or A is as defined herein, wherein R 1 is H, substituted or unsubstituted C 1-20 Alkyl, or substituted or unsubstituted aryl, or R 2 is substituted or unsubstituted C 1-10 alkyl; and y is 0 to 6.
[0266] In another embodiment, the hexahalide metal salt compound is A2GeF 6-y Cl y 、A2GeF 6-y Br y 、A2GeF 6-y I y 、A2GeCl 6-y Br y 、A2GeCl 6-y I y or A2GeBr 6-y I y , where: A is K +, Rb + , Cs + , (R 1 NH3) + ,(NR 2 4) + or (H2N–C(R 1 )=NH2) + , or A is as defined herein, wherein R 1 is H, substituted or unsubstituted C 1-20 alkyl, or substituted or unsubstituted aryl, and R 2 is substituted or unsubstituted C 1-10 alkyl; and y is 0 to 6.
[0267] The hexahalide metal salt compound may be, for example, A2TeF 6-y Cl y 、A2TeF 6-y Br y 、A2TeF 6-y I y 、A2TeCl 6-y Br y 、A2TeCl 6-y I y or A2TeBr 6-y I y , where: A is K + , Rb + , Cs + , (R 1 NH3) + ,(NR 2 4) + or (H2N–C(R 1 )=NH2) + , or A is as defined herein, wherein R 1 is H, substituted or unsubstituted C 1-20 Alkyl, or substituted or unsubstituted aryl, or R 2 is substituted or unsubstituted C 1-10 alkyl; and y is 0 to 6, or y is as defined herein.
[0268] Typically, y is between 1.50 and 2.50. For example, y may be between 1.80 and 2.20. This may be the case if two equivalents of AX' and one equivalent of MX4 are used to prepare the compound, as described below.
[0269] In some embodiments, all ions are a single anion or cation. Thus, the crystalline A / M / X material may comprise or consist essentially of a hexahalide metal salt compound of formula (IIIC)
[0270] A2MX6 (IIIC)
[0271] wherein: A is a monovalent cation; M is a metal or metalloid tetravalent cation; and X is a halide anion. A, M and X may be as defined herein.
[0272] The hexahalide metal salt compound can be A2SnF6, A2SnCl6, A2SnBr6, A2SnI6, A2TeF6, A2TeCl6, A2TeBr6, A2TeI6, A2GeF6, A2GeCl6, A2GeBr6, A2GeI6, A2ReF6, A2ReCl6, A2ReBr6 or A2ReI6, wherein: A is K + , Rb + , Cs + , (R 1 NH3) + ,(NR 2 4) + or (H2N–C(R 1 )=NH2) + , where R 1 is H, substituted or unsubstituted C 1-20 alkyl, or substituted or unsubstituted aryl, and R 2 is substituted or unsubstituted C 1-10 Alkyl. A may be as defined herein.
[0273] Preferably, the hexahalide metal salt compound is Cs2SnI6, Cs2SnBr6, Cs2SnBr 6-y I y 、Cs2SnCl 6-y I y 、Cs2SnCl 6-y Br y , (CH3NH3)2SnI6, (CH3NH3)2SnBr6, (CH3NH3)2SnBr 6-y I y 、(CH3NH3)2SnCl 6-y I y 、(CH3NH3)2SnCl 6-y Br y , (H2N–C(H)=NH2)2SnI6, (H2N–C(H)=NH2)2SnBr6, (H2N–C(H)=NH2)2SnBr 6-y I y 、(H2N–C(H)=NH2)2SnCl 6-y I y or (H2N–C(H)=NH2)2SnCl 6-y Br y, wherein y is 0.01 to 5.99. For example, the hexahalide metal salt compound may be (CH3NH3)2SnI6, (CH3NH3)2SnBr6, (CH3NH3)2SnCl6, (H2N–C(H)=NH2)2SnI6, (H2N–C(H)=NH2)2SnBr6 or (H2N–C(H)=NH2)2SnCl6. The hexahalide metal salt compound may be Cs2SnI6, Cs2SnBr6, Cs2SnCl 6-y Br y , (CH3NH3)2SnI6, (CH3NH3)2SnBr6 or (H2N–C(H)=NH2)2SnI6.
[0274] The crystalline A / M / X material may include a metal halide salt of bismuth or antimony. For example, the crystalline A / M / X material may include a metal halide salt compound comprising: (i) one or more monovalent cations ([A]) or one or more divalent cations ([B]); (ii) one or more metal or metalloid trivalent cations ([M]); and (iii) one or more halide anions ([X]). The compound may be a compound of formula BBiX5, B2BiX7 or B3BiX9, wherein B is (H3NCH2NH3) 2+ 、(H3N(CH2)2NH3) 2+ 、(H3N(CH2)3NH3) 2+ 、(H3N(CH2)4NH3) 2+ 、(H3N(CH2)5NH3) 2+ 、(H3N(CH2)6NH3) 2+ 、(H3N(CH2)7NH3) 2+ 、(H3N(CH2)8NH3) 2+ or (H3N–C6H4–NH3) 2+ , and X is I – Br – or Cl – , preferably I – .
[0275] In another embodiment, the crystalline A / M / X material may be a double perovskite. Such compounds are defined in WO 2017 / 037448, the entire contents of which are incorporated herein by reference. Typically, the compound is a double perovskite compound of formula (IV):
[0276] [A]2[B + ][B 3+ ][X]6 (IV);
[0277] wherein: [A] comprises one or more A cations, wherein the A cation is a monovalent cation, as defined herein; [B + ] and [B 3+ ] relative to [M], wherein M includes one or more M cations that are monovalent cations and one or more M cations that are tetravalent cations; and [X] includes one or more anions that are halide anions.
[0278] [B + The one or more M cations included in ] are usually selected from metal and metalloid monovalent cations. Preferably, the one or more M cations are selected from Li + 、Na + , K + , Rb + , Cs + , Cu + 、Ag + 、Au + and Hg + More preferably, the one or more monovalent cations are selected from Cu + 、Ag + and Au + Most preferably, one or more monovalent cations M are selected from Ag + and Au + For example, [B + ] can be a monovalent cation, Ag + , or [B + ] can be a monovalent cation, Au + .
[0279] [B 3+ The one or more trivalent cations M cations included in ] are usually selected from metal and metalloid trivalent cations. Preferably, the one or more trivalent cations M cations are selected from Bi 3+ , Sb 3+ Cr 3+ , Fe 3+ 、Co 3+ , Ga 3+ 、As 3+ 、Ru 3+ , Rh 3+ 、In 3+ , Ir 3+ and Au 3+ More preferably, one or more trivalent cations M are selected from Bi 3+ and Sb 3+ For example, [B 3+ ] can be a trivalent cation, Bi 3+ , or [B3+ ] can be a trivalent cation, Sb 3+ Bismuth has relatively low toxicity compared to heavy metals such as lead. In some embodiments, one or more M cations ([B + ]) is selected from Cu + 、Ag + and Au + , and one or more M cations that are trivalent cations ([B 3+ ]) Selected from Bi 3+ and Sb 3+ .
[0280] An exemplary double perovskite is Cs2BiAgBr6.
[0281] Typically, where the compound is a double perovskite, it is a compound of formula (IVa):
[0282] A2B + B 3+ [X]6 (IVa);
[0283] Wherein: A cation is as defined herein; B + is an M cation as defined herein, said M cation being a monovalent cation; B 3+ is an M cation as defined herein, said M cation being a trivalent cation; and [X] comprises one or more X anions, said X anion being a halide anion, such as two or more halide anions, preferably a single halide anion.
[0284] In yet another embodiment, the compound may be a layered double perovskite compound of formula (V):
[0285] [A]4[B + ][B 3+ ][X]8 (V);
[0286] Where: [A], [B + ]、[B 3+ ] and [X] are as defined above. In some embodiments, the layered double perovskite compound is a double perovskite compound of formula (Va):
[0287] A4B + B 3+ [X]8 (Va);
[0288] Wherein: A cation is as defined herein; B + is an M cation as defined herein, said M cation being a monovalent cation; B 3+is an M cation as defined herein, said M cation being a trivalent cation; and [X] comprises one or more X anions, said X anions being halide anions, such as two or more halide anions, preferably a single halide anion or two types of halide anions.
[0289] In another embodiment, the compound may be a compound of formula (VI):
[0290] [A]4[M][X]6 (VI);
[0291] wherein: [A], [M] and [X] are as defined above (for example, with respect to compounds of formula (I) or (II)). However, preferably, the compound is not a compound of formula (VI). When the compound is a compound of formula (VI), the compound may preferably be a compound of formula (VIA)
[0292] [A I A II ]4[M][X]6 (VIA);
[0293] That is, wherein [A] comprises two types of compounds of monovalent cations of A. In other preferred embodiments, the compound of formula (VI) may be a compound of formula (VIB):
[0294] [A]4[M][X I X II ]6 (VIB);
[0295] That is, a compound of formula (VI) wherein [X] comprises two types of X anions. In other preferred embodiments, the compound of formula (VI) may be a compound of formula (VIC):
[0296] [A I A II ]4[M][X I X II ]6 (VIC);
[0297] That is, a compound of formula (VI) wherein [A] comprises two types of A monovalent cations and [X] comprises two types of X anions. In formulas (VIa), (VIb) and (VIc), [A], [M] and [X] are each as defined above (for example, compounds of formula (I) or (II)).
[0298] In another embodiment, a = 1, b = 1, and c = 4. In this embodiment, in this case, the crystalline A / M / X material may include a compound of formula (VII):
[0299] [A][M][X]4 (VII)
[0300] wherein: [A] comprises one or more A cations, the A cations being monovalent cations; [M] comprises one or more M cations, the M cations being metal or metalloid trivalent cations; and [X] comprises one or more X anions, the X anions being halide anions. The A monovalent cations and the M trivalent cations are as defined herein. An exemplary compound of formula (VII) is AgBiI4.
[0301] It should be understood that the present invention also includes methods for producing variations of the above-mentioned structures (I), (II), (III), (IV), (V), (VI) and (VII) in which one or more of the associated a, b and c values are non-integer values.
[0302] Preferably, formula [A] a [M] b [X] c The compound is a compound of formula [A] [M] [X] 3, a compound of formula [A] 4 [M] [X] 6 or a compound of formula [A] 2 [M] [X] 6. For example, in a preferred embodiment, formula [A] a [M] b [X] c The compound is a compound of formula (I), such as a compound of formula (IA), formula (IB), formula (IC), formula (ID), formula (IE), formula (IF), formula (IG), formula (IH); or a compound of formula (IIIA), formula (IIIB), formula (IIIC), formula (VIA), formula (VIB), or formula (VIC). Generally, formula [A] a [M] b [X] c The compound is a compound of formula (I), for example, a compound of formula (IA), formula (IB), formula (IC), formula (ID), formula (IE), formula (IF), formula (IG) or formula (IH).
[0303] In some embodiments, formula [A] a [M] b [X] c A compound of formula [A] is a compound wherein [A] includes two or more different A cations. For example, [A] may include two types of cations. In some embodiments, formula [A] a [M] b [X] c A compound of formula [A] is a compound wherein [X] includes two or more different X anions. For example, [X] may include two types of anions, such as halide anions. In some embodiments, formula [A] a [M] b [X] cA compound is one in which [M] comprises two or more different M cations. For example, [X] may comprise two types of anions, such as Sn 2+ and Pb 2 + .
[0304] In one aspect of each of these embodiments, formula [A] a [M] b [X] c A compound is one in which [A] includes two or more different A cations and [X] includes two or more different X anions. For example, [A] may include two types of A cations, and [X] may include two types of X anions (e.g., two types of halide anions).
[0305] In one aspect of each of these embodiments, formula [A] a [M] b [X] c A compound is a compound wherein [A] comprises two or more different A cations and [M] comprises two or more different M cations. For example, [A] may comprise two types of A cations, and [M] may comprise two types of M cations (e.g., Sn 2+ and Pb 2+ ).
[0306] In one aspect of each of these embodiments, formula [A] a [M] b [X] c A compound is a compound in which [X] includes two or more different X anions and [M] includes two or more different M cations. For example, [X] may include two types of X anions (e.g., two types of halide anions), and [M] may include two types of M cations (e.g., Sn 2+ and Pb 2+ ).
[0307] In one aspect of each of these embodiments, formula [A] a [M] b [X] c A compound is one in which [A] comprises two or more different A cations, and in which [X] comprises two or more different X anions, and [M] comprises two or more different M cations. For example, [A] may comprise two types of A cations, [X] may comprise two types of X anions (e.g., two types of halide anions), and [M] may comprise two types of M cations (e.g., Sn 2+ and Pb 2+).
[0308] Charge transport layer
[0309] The substrate may include one or more additional layers. For example, the substrate may further include a charge transport material layer. Preferably, the charge transport material layer is arranged on the charge recombination layer. Typically, the charge transport material layer is arranged directly on the charge recombination layer. Alternatively, there may be an intermediate layer between the charge transport material layer and the charge recombination layer. Thus, the substrate may include the following layers in the following order:
[0310] A layer of charge transport material (typically an n-type material as described herein, but this could alternatively be a p-type material);
[0311] Charge recombination layer;
[0312] Photoactive region.
[0313] Typically, the crystalline A / M / X material layer is disposed directly on the charge transport material layer. Alternatively, there may be an intermediate layer between the charge transport material layer and the crystalline A / M / X material layer.
[0314] Typically, the charge transport material layer is disposed directly on the charge recombination layer, and the crystalline A / M / X material layer is disposed directly on the charge transport material layer. Thus, a multi-junction device produced according to the present invention may include the following layers in the following order:
[0315] Crystalline A / M / X material layer;
[0316] A layer of charge transport material (typically an n-type material as described herein, but this could alternatively be a p-type material);
[0317] Charge recombination layer;
[0318] Photoactive region.
[0319] In one embodiment, the charge transport material layer is an electron transport (n-type) material layer. In another embodiment, the charge transport material layer is a hole transport (p-type) material layer. Typically, the charge transport material layer is an electron transport (n-type) material layer.
[0320] Typically, the charge transport material is soluble in dimethylformamide. Thus, the charge transport material may be soluble in dimethylformamide (DMF), dimethyl sulfoxide (DMSO), or a mixture thereof.
[0321] Typically, the thickness of the charge transport material layer is less than 1000 nm, or less than 500 nm, or less than 250 nm, preferably less than 100 nm. For example, the thickness of the charge transport material layer can be 1 nm to 500 nm, such as 5 nm to 250 nm, or 10 nm to 75 nm.
[0322] Examples of electron transport (n-type) materials are known to the skilled person. Suitable n-type materials may be organic or inorganic materials. Suitable inorganic n-type materials may be selected from metal oxides, metal sulfides, metal selenides, metal tellurides, perovskites, amorphous silicon, n-type IV semiconductors, n-type III-V semiconductors, n-type II-VI semiconductors, n-type I-VII semiconductors, n-type IV-VI semiconductors, n-type V-VI semiconductors, and n-type II-V semiconductors, any of which may be doped or undoped. More typically, the n-type material is selected from metal oxides, metal sulfides, metal selenides, and metal tellurides.
[0323] Thus, the n-type layer may include an inorganic material selected from the oxide of the following metals, or an oxide of a mixture of two or more of the metals: titanium, tin, zinc, niobium, tantalum, tungsten, indium, gallium, neodymium, palladium or cadmium. For example, the n-type layer may include TiO2, SnO2, ZnO, Nb2O5, Ta2O5, WO3, W2O5, In2O3, Ga2O3, Nd2O3, PbO or CdO. Other suitable n-type materials that may be used include sulfides of cadmium, tin, copper or zinc, including sulfides of a mixture of two or more of the metals. For example, the sulfide may be FeS2, CdS, ZnS or Cu2ZnSnS4.
[0324] The n-type layer may, for example, include a selenide of cadmium, zinc, indium or gallium, or a selenide of a mixture of two or more of the metals; or a telluride of cadmium, zinc, cadmium or tin, or a telluride of a mixture of two or more of the metals. For example, the selenide may be Cu(In,Ga)Se2. Typically, the telluride is a telluride of cadmium, zinc, cadmium or tin. For example, the telluride may be CdTe.
[0325] The n-type layer may, for example, include an inorganic material selected from the following: oxides of titanium (e.g., TiO2), tin (e.g., SnO2), zinc (e.g., ZnO), niobium, tantalum, tungsten, indium, gallium, neodymium, palladium, cadmium, or oxides of a mixture of two or more of the metals; sulfides of cadmium, tin, copper, zinc, or sulfides of a mixture of two or more of the metals; selenides of cadmium, zinc, indium, gallium, or selenides of a mixture of two or more of the metals; or tellurides of cadmium, zinc, cadmium or tin, or tellurides of a mixture of two or more of the metals.
[0326] Examples of other semiconductors that may be suitable n-type materials, for example if they are n-doped, include Group IV compound semiconductors; amorphous silicon; Group III-V semiconductors (e.g., gallium arsenide); Group II-VI semiconductors (e.g., cadmium selenide); Group I-VII semiconductors (e.g., cuprous chloride); Group IV-VI semiconductors (e.g., lead selenide); Group V-VI semiconductors (e.g., bismuth telluride) and Group II-V semiconductors (e.g., cadmium arsenide).
[0327] Other n-type materials, including organic and polymer electron transport materials, and electrolytes may also be used. Suitable examples include, but are not limited to, fullerenes or fullerene derivatives (e.g., C 60 , C 70 , phenyl-C 61 -Methyl butyrate (PCBM), PC 71 BM (phenyl C 71 Methyl butyrate), bis[C 60 ]BM (i.e. double-C 60 butyric acid methyl ester) and 1',1",4',4"-tetrahydro-di[1,4]methylenenaphtho[1,2:2',3',56,60:2",3"][5,6]fullerene-C 60 (ICBA)). The organic electron transport material includes perylene or its derivatives, or poly{[N,N0-bis(2-octyldodecyl)-naphthalene-1,4,5,8-bis(dicarboximide)-2,6-diyl]-alternative-5,50-(2,20-bithiophene)}(P(NDI2OD-T2)).
[0328] Preferably, the n-type material is phenyl-C61-butyric acid methyl ester (PCBM).
[0329] Examples of hole transport (p-type) materials are known to the skilled person. The p-type material may be a single p-type compound or elemental material, or a mixture of two or more p-type compounds or elemental materials, which may be undoped or doped with one or more dopant elements.
[0330] The p-type material may include an inorganic or organic p-type material. Typically, the p-type material is an organic p-type material.
[0331] Suitable p-type materials may be selected from polymers or molecular hole transporters. The p-type materials may include, for example, spiro-OMeTAD (2,2',7,7'-tetra-(N,N-di-p-methoxyaniline) 9,9'-spirobifluorene), P3HT (poly(3-hexylthiophene)), PCPDTBT (poly[2,1,3-benzothiadiazole-4,7-diyl[4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b:3,4-b']bithiophene-2,6-diyl]]), PVK (poly(N-vinylcarbazole)), HTM-TFSI (1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide), Li-TFSI (lithium bis(trifluoromethylsulfonyl)imide), spiro-OMETAD + -Bis(trifluoromethanesulfonyl)imide - (spiro(TFSI)2), tBP (tert-butylpyridine), m-MTDATA (4,4',4"-tris(methylphenylphenylamino)triphenylamine), MeOTPD (N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine), BP2T (5,5'-di(biphenyl-4-yl)-2,2'-bithiophene), Di-NPB (N,N'-di[(1-naphthyl)-N,N'-diphenyl]-1,1'-biphenyl)-4,4'-diamine), α-NPB (N,N'-di(naphthyl-1-yl)-N,N'-diphenyl-benzidine), TNATA (4,4',4"-tris(N-(naphthyl)- 2-yl)-N-aniline)triphenylamine), BPAPF (9,9-bis[4-(N,N-bis-biphenyl-4-yl-amino)phenyl]-9H-fluorene), spiro-NPB (N2,N7-di-1-naphthyl-N2,N7-diphenyl-9,9'-spirobis[9H-fluorene]-2,7-diamine), 4P-TPD (4,4-bis-(N,N-biphenylamino)-tetraphenyl), polyTPD (i.e. poly[N,N'-bis(4-butylphenyl)-N,N'-bisphenylbenzidine]), PTAA (i.e. poly(triarylamine), also known as poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]) or PEDOT:PSS. The p-type material may include carbon nanotubes. Typically, the p-type material is selected from spiro-OMeTAD, P3HT, PCPDTBT, spiro(TFSI)2 and PVK. Preferably, the p-type material is spiro-OMeTAD or spiro(TFSI)2.
[0332] Suitable p-type materials also include molecular hole transporters, polymer hole transporters, and copolymer hole transporters. The p-type material can be, for example, a molecular hole transport material, a polymer or copolymer comprising one or more of the following moieties: thienyl, phenylene, dithiazolyl, benzothiazolyl, diketopyrrolopyrrole, ethoxydithienyl, amino, triphenylamino, carbazolyl, ethylenedioxythienyl, dioxythienyl, or fluorenyl.
[0333] The p-type material may be doped with, for example, tert-butylpyridine and LiTFSI. The p-type material may be doped to increase the hole density. For example, the p-type material may be doped with, for example, NOBF4 (nitrosonium tetrafluoroborate) to increase the hole density.
[0334] In other embodiments, the p-type layer may include an inorganic hole transporter. For example, the p-type layer may include an inorganic hole transporter including an oxide of nickel (e.g., NiO), vanadium, copper, or molybdenum; CuI, CuBr, CuSCN, Cu2O, CuO, or CIS; perovskite; amorphous silicon; p-type IV semiconductor, p-type III-V semiconductor, p-type II-VI semiconductor, p-type I-VII semiconductor, p-type IV-VI semiconductor, p-type V-VI semiconductor, and p-type II-V semiconductor, and the inorganic material may be doped or undoped. The p-type layer may be a dense layer of the inorganic hole transporter.
[0335] The p-type material may be an inorganic p-type material, for example, a material including the following: an oxide of nickel, vanadium, copper or molybdenum; CuI, CuBr, CuSCN, Cu2O, CuO or CIS; perovskite; amorphous silicon; p-type IV semiconductor, p-type III-V semiconductor, p-type II-VI semiconductor, p-type I-VII semiconductor, p-type IV-VI semiconductor, p-type V-VI semiconductor and p-type II-V semiconductor, and the inorganic material may be doped or undoped. The p-type material may, for example, include an inorganic hole transporter selected from CuI, CuBr, CuSCN, Cu2O, CuO and CIS.
[0336] In one embodiment, the present invention includes a step of forming a substrate by arranging a charge transport material layer as described herein on a charge recombination layer. Typically, a composition comprising a charge transport material, preferably a solution comprising a charge transport material, is arranged on the charge recombination layer. Typically, a solution comprising a charge transport material is arranged on the charge recombination layer by a solution phase deposition method, such as gravure coating, slit dye coating, screen printing, inkjet printing, blade coating, spraying, roll-to-roll (R2R) processing, or spin coating, preferably by spin coating.
[0337] Typically, the solvent in the solution containing the charge transport material is selected from chlorobenzene, chloroform, anisole, toluene, tetrahydrofuran, xylene, or a mixture thereof. For example, the step of forming a substrate by arranging a charge transport material layer on the charge recombination layer may include:
[0338] preparing a solution of a charge transport material, preferably a solution of an electron transport (n-type) material in chlorobenzene, chloroform or a mixture thereof, more preferably wherein the electron transport (n-type) material is PCBM;
[0339] • Arrange the charge transport material on the charge recombination layer by spin coating.
[0340] Charge recombination layer
[0341] The method of the present invention may further comprise the step of producing the substrate by arranging the charge recombination layer on the photoactive region by means of a solution deposition method.
[0342] Typically, the charge recombination layer comprises nanoparticles of a transparent conductive oxide. The nanoparticles create an ohmic contact between the electron transport layer and the hole transport layer, allowing efficient charge transfer into the recombination layer. Furthermore, such nanoparticles are easily processed using solution-based methods to form substrates.
[0343] The nanoparticles of transparent conductive oxide may include indium zinc oxide (IZO), indium tin oxide (ITO), aluminum zinc oxide (AZO), indium cadmium oxide, fluorine-doped tin oxide (FTO), antimony-doped tin oxide, antimony-doped titanium dioxide, niobium-doped tin oxide, niobium-doped titanium dioxide, barium stannate, strontium vanadate and calcium vanadate. Preferably, the nanoparticles of transparent conductive oxide include indium tin oxide (ITO). Therefore, the nanoparticles of transparent conductive oxide may be nanoparticles of indium tin oxide. Preferably, the nanoparticles of transparent conductive oxide are nanoparticles of indium tin oxide having a size of less than 500 nm, preferably less than 250 nm, and more preferably less than 100 nm. Generally, the size of the nanoparticles can be determined by dynamic light scattering in solution or transmission electron microscopy of a dried film.
[0344] The nanoparticles of the transparent conductive oxide may be arranged in a matrix material. The matrix material may be an inorganic or organic matrix material. It is typically a dielectric matrix material, such as an inorganic or organic dielectric matrix material. Alternatively, it may be an electron transport matrix material. Typically, the matrix material is an organic matrix material. Typically, the organic matrix material is an electron transport organic matrix material. Suitable examples include, but are not limited to, fullerenes or fullerene derivatives (e.g., C 60 or phenyl-C61 butyric acid methyl ester (PCBM)), an organic electron transport material comprising perylene or a derivative thereof, or poly{[N,N0-bis(2-octyldodecyl)-naphthalene-1,4,5,8-bis(imide)-2,6-diyl]-alternate-5,50-(2,20-bithiophene)}(NDI2OD-T2). Preferably, the organic matrix material comprises [6,6]-phenyl-C61-butyric acid methyl ester (PCBM).
[0345] Typically, the charge recombination layer further comprises a conductive polymer. For example, the charge recombination layer may comprise p-doped poly-TPD, poly-triarylamine (PTAA), polythiophene. Typically, the conductive polymer comprises poly (3,4-ethylenedioxythiophene) (PEDOT) or a derivative thereof. For example, the conductive polymer may comprise poly (3,4-ethylenedioxythiophene) and polystyrene sulfonate (PEDOT:PSS) or poly (3,4-ethylenedioxythiophene)-tetramethylacrylate (PEDOT:TMA). Preferably, the conductive polymer comprises poly (3,4-ethylenedioxythiophene) and polystyrene sulfonate (PEDOT:PSS).
[0346] The charge recombination layer may include nanoparticles of a transparent conductive oxide and a conductive polymer. For example, the charge recombination layer may include nanoparticles of indium tin oxide (ITO) and poly(3,4-ethylenedioxythiophene) and polystyrene sulfonate (PEDOT:PSS). The nanoparticles of the transparent conductive oxide may be uniformly distributed in the conductive polymer of the charge recombination layer. Alternatively, the nanoparticles of the transparent conductive oxide and the conductive polymer may form two different sublayers within the charge recombination layer.
[0347] Typically, the thickness of the charge recombination layer is less than 1000 nm, such as less than 750 nm, less than 250 nm, preferably less than 100 nm. For example, the thickness of the charge recombination layer can be 5 nm to 500 nm, 10 nm to 250 nm, 20 nm to 150 nm, preferably 25 nm to 125 nm. In some embodiments, such as when the charge recombination layer is a tunnel junction, the thickness of the charge recombination layer is less than 50 nm, such as less than 30 nm, such as less than or equal to 20 nm, or such as less than or equal to 10 nm.
[0348] The charge recombination layer may be a tunnel junction. A tunnel junction is typically a very thin film, such as a film having a thickness less than or equal to 20 nm, such as less than or equal to 10 nm. The film typically includes a very thin layer of highly doped n-type material interfaced with a very thin layer of highly doped p-type material. This enables charge to tunnel through the junction.
[0349] Therefore, in one embodiment, the charge recombination layer is a tunnel junction. Typically, the thickness of the tunnel junction is less than 30nm, for example less than or equal to 20nm, or less than or equal to 10nm. The tunnel junction typically includes a first sublayer on a second sublayer, and more typically consists of a first sublayer arranged on a second sublayer, wherein one of the first sublayer and the second sublayer is an n-type material, and the other of the first sublayer and the second sublayer is a p-type material. The n-type material may include any of the n-type materials described herein. The n-type material is typically doped with a dopant. The p-type material may include any of the p-type materials described herein. Typically, the p-type material is doped with a dopant. Dopants used to dope n-type and p-type materials in tunnel junctions are known in the art.
[0350] Typically, disposing the charge recombination layer on the photoactive region includes the step of disposing a solvent dispersion of nanoparticles of a transparent conductive oxide on the photoactive region.
[0351] Typically, the solvent is selected to be orthogonal to the solvent used for the underlying layer, such as the photoactive region and / or charge transport layer (if present). A solvent is orthogonal to another solvent when it does not dissolve the material layer deposited by the other solvent. For example, the solvent can be a polar solvent, such as a polar protic solvent, such as an alcohol. It can be, for example, isopropanol (2-propanol), methanol or ethanol. It can be a polar aprotic solvent, such as acetone, acetonitrile, methyl ethyl ketone.
[0352] Typically, the solvent dispersion of nanoparticles of a transparent conductive oxide is a dispersion of indium tin oxide nanoparticles in isopropanol.
[0353] Typically, the indium tin oxide nanoparticles comprise less than 75% by weight of the solvent dispersion (total weight of the solvent plus the nanoparticles), such as less than 50% by weight of the solvent dispersion. For example, the indium tin oxide nanoparticles may comprise 0.001% to 50% by weight of the solvent dispersion, 0.1% to 10% by weight of the solvent dispersion, 0.5% to 5% by weight of the solvent dispersion, and preferably about 1% by weight of the solvent dispersion.
[0354] The solvent dispersion of nanoparticles of transparent conductive oxide is arranged on the charge recombination layer by roll-to-roll (R2R) processing, doctor blade coating, inkjet printing or spin coating. Typically, the solvent dispersion of nanoparticles of transparent conductive oxide is arranged on the photoactive area by spin coating. In one embodiment, the solvent dispersion of nanoparticles of transparent conductive oxide is directly spin coated onto the photoactive area. Typically, the spin coating is performed at a speed of at least 1000RPM, such as at least 2000RPM, at least 3000RPM, at least 4000RPM or at least 5000RPM, such as 2000RPM to 10000RPM, 4000RPM to 8000RPM, preferably about 6000RPM. Typically, the spin coating lasts for at least one second, at least 5 seconds or at least 10 seconds, such as 1 second to 1 minute, 10 seconds to 30 seconds, preferably about 20 seconds.
[0355] Thus, the step of producing the substrate by disposing the charge recombination layer on the photoactive area by means of solution deposition may comprise spin coating a solvent dispersion of indium tin oxide nanoparticles in isopropanol on the substrate (photoactive area) at a speed of about 6000 RPM for about 20 seconds.
[0356] The charge recombination layer may further comprise a matrix material. The matrix material may be an inorganic or organic matrix material. It may be a dielectric matrix material, such as an inorganic or organic dielectric matrix material. However, it is typically an electron transport matrix material. As described herein, typically, the matrix material is an organic matrix material. Therefore, the solvent dispersion of nanoparticles may further comprise a matrix material, such as an organic matrix material as described herein. The matrix material may, for example, be a dielectric matrix material, or it may be an electron transport matrix material. The matrix material may be organic or inorganic, but is typically organic, such as an organic electron transport matrix material. Arranging the charge recombination layer on the photoactive region may include arranging the solvent dispersion of the nanoparticles of the transparent conductive oxide and the matrix material (e.g., an organic matrix material) on the photoactive region.
[0357] In the method for the present invention, host material and nanoparticle can be arranged together (for example as mentioned above) or arranged separately. When arranged separately, one selection is to arrange nanoparticle at first, such as the solvent dispersion of nanoparticle, and arrange host material subsequently, for example solution or dispersion of host material in solvent. Then, host material can penetrate in the nanoparticle that is arranged, so that nanoparticle is dispersed in host material.
[0358] When a conductive polymer is present in the charge recombination layer, arranging the charge recombination layer on the photoactive region may include arranging a conductive polymer as described above on the photoactive region, and arranging a solvent dispersion of nanoparticles of a transparent conductive oxide on the photoactive region. Preferably, the conductive polymer includes poly(3,4-ethylenedioxythiophene) and polystyrene sulfonate (PEDOT:PSS). Typically, the conductive polymer is dispersed in a solvent. For example, the conductive polymer may be dispersed in an alcohol, water, a mixture of one or more alcohols and water, or a mixture of alcohols, for example, it may be dispersed in isopropanol (2-propanol), ethanol (EtOH), methanol (MeOH), or water, or a mixture thereof. Therefore, arranging the charge recombination layer on the photoactive region may include arranging a dispersion of poly(3,4-ethylenedioxythiophene) and polystyrene sulfonate (PEDOT:PSS) in isopropanol (2-propanol), ethanol (EtOH), methanol (MeOH), water, or a mixture thereof on the photoactive region.
[0359] The conductive polymer may be disposed on the photoactive region by roll-to-roll (R2R) processing, blade coating, inkjet printing, or spin coating. Typically, the conductive polymer is disposed on the photoactive region by spin coating. In one embodiment, the conductive polymer is spin coated directly onto the photoactive region. Typically, the spin coating is performed at a speed of at least 1000 RPM, such as at least 2000 RPM, at least 3000 RPM, at least 4000 RPM, or at least 5000 RPM, such as 2000 RPM to 10000 RPM, 4000 RPM to 8000 RPM, preferably about 6000 RPM. Typically, the spin coating lasts for at least one second, at least 5 seconds, or at least 10 seconds, such as 1 second to 1 minute, 10 seconds to 30 seconds, preferably about 20 seconds.
[0360] Typically, placing a charge recombination layer on the photoactive region involves two steps:
[0361] 1) Arranging a conductive polymer on the photoactive region;
[0362] 2) Disposing a solvent dispersion of nanoparticles of a transparent conductive oxide on the photoactive area.
[0363] Typically, both the solvent dispersion of nanoparticles and the conductive polymer are arranged on the photoactive area by spin coating. The step of spin coating the solvent dispersion of nanoparticles and the conductive polymer (if present) on the photoactive area can be combined with one or more annealing steps. Typically, annealing is performed at a temperature of at least 20°C, such as in the range of 20°C to 150°C, such as 30°C to 120°C, 40°C to 110°C, 60°C to 100°C, 70°C to 90°C, preferably at a temperature of about 80°C. Typically, annealing is performed for a period of 1 minute to 120 minutes, such as 2 minutes to 60 minutes, 3 minutes to 45 minutes, 4 minutes to 30 minutes, 5 minutes to 15 minutes or about 10 minutes. Therefore, annealing can be performed at a temperature of 20°C to 150°C for a period of 1 minute to 120 minutes, such as at a temperature of 60°C to 100°C for a period of 4 minutes to 30 minutes, preferably at about 80°C for about 10 minutes.
[0364] In one embodiment, disposing the charge recombination layer on the photoactive region comprises the following steps:
[0365] 1. disposing a conductive polymer by disposing a solvent dispersion of the conductive polymer on the photoactive region (optionally by spin coating), preferably, wherein the conductive polymer comprises poly(3,4-ethylenedioxythiophene) and polystyrene sulfonate (PEDOT:PSS);
[0366] 2. optionally annealing the conductive polymer disposed on the photoactive region, preferably at about 80° C. for about 10 minutes;
[0367] 3. disposing a solvent dispersion of nanoparticles of a transparent conductive oxide on the photoactive area (optionally by spin coating), preferably wherein the nanoparticles are nanoparticles of indium tin oxide (ITO);
[0368] 4. Optionally, anneal the transparent conductive oxide nanoparticles on the photoactive area, preferably at about 80° C. for 10 minutes.
[0369] Disposing the charge recombination layer on the photoactive region may include disposing a solvent dispersion of nanoparticles of a conductive polymer and a transparent conductive oxide on the photoactive region simultaneously. For example, the conductive polymer and the nanoparticles of the transparent conductive oxide may be present in the same solvent dispersion. As described above, the dispersion comprising the conductive polymer and the nanoparticles of the transparent conductive oxide may be disposed on the photoactive region by spin coating.
[0370] Photoactive region
[0371] The photoactive material in the photoactive region of the substrate may include any suitable photoactive material known to a skilled person. For example, the photoactive material in the photoactive region may include silicon; Cu(In,Ga)Se2 (CIGS), Cu2ZnSn(S,Se)4 (CZTSSe), CuInS (CIS) metal chalcogenide nanocrystals such as PbS, PbSe or CdTe 1-x S x ; or chalcogenide films, such as CdTe or CdTe 1-x Se x or CdTe 1-x S x ; or crystalline A / M / X material. Typically, the photoactive material in the photoactive region of the substrate comprises a crystalline A / M / X material comprising the formula [A] as described herein: a [M] b [X] c Compounds. ;
[0372] For example, the photoactive material in the photoactive region may include [A] a [M] b [X] c wherein the compound is a compound of formula (IA), (IB), (IC), (ID), (IE), (IF), (IG), (IH), (IIIA), (IIIB), (IIIC), (VIA), (VIB) or (VIC). Typically, the photoactive material in the photoactive region comprises formula [A] a [M] b [X] c A compound of formula (I), wherein the compound is a compound of formula (I), for example, a compound of formula (IA), formula (IB), formula (IC), formula (ID), formula (IE), formula (IF), formula (IG) or formula (IH).
[0373] For example, the photoactive material in the photoactive zone may include a compound of formula (IA):
[0374] AMX3 (IA)
[0375] Wherein A, M and X are as defined above. In a preferred embodiment, A is selected from (CH3NH3) + 、(CH3CH2NH3) + 、(CH3CH2CH2NH3) + 、(N(CH3)4) + 、(H2N–C(H)=NH2) + 、(H2N–C(CH3)=NH2) +、(H2N–C(NH2)=NH2) + , Cs + and Rb + ; M is Pb 2+ or Sn 2+ , and X is selected from Br - , Cl - and I - .
[0376] For example, the photoactive material in the photoactive zone may comprise or consist essentially of a perovskite compound of formula (IA) selected from the group consisting of APbI3, APbBr3, APbCl3, ASnI3, ASnBr3, and ASnCl3, wherein A is a cation as described herein.
[0377] For example, the photoactive material in the photoactive region may comprise or consist essentially of a perovskite compound of formula (IA) selected from the group consisting of CH3NH3PbI3, CH3NH3PbBr3, CH3NH3PbCl3, CH3NH3SnI3, CH3NH3SnBr3, CH3NH3SnCl3, CsPbI3, CsPbBr3, CsPbCl3, CsSnI3, CsSn Br3, CsSnCl3, (H2N–C(H)=NH2)PbI3, (H2N–C(H)=NH2)PbBr3, (H2N–C(H)=NH2)PbCl3, (H2N–C(H)=NH2)SnI3, (H2N–C(H)=NH2)SnBr3 and (H2N–C(H)=NH2)SnCl3; in particular CH3NH3PbI3 or CH3NH3PbBr3; preferably CH3NH3PbI3.
[0378] For example, the photoactive material in the photoactive region may include a compound of formula (ID):
[0379] [A I x A II 1-x ]M[X I y X II 1-y ]3 (ID)
[0380] Among them A I and A II As defined above with respect to A, M is as defined above, and X I and X II As defined above with respect to X, and wherein x and y are both greater than 0 and less than 1. In a preferred embodiment, AI and A II Each selected from (CH3NH3) + 、(CH3CH2NH3) + 、(CH3CH2CH2NH3) + 、(N(CH3)4) + 、(H2N–C(H)=NH2) + 、(H2N–C(CH3)=NH2) + 、(H2N–C(NH2)=NH2) + , Cs + and Rb + ; M is Pb 2+ or Sn 2+ , and X I and X II Selected from Br - , Cl - and I - .
[0381] For example, the photoactive material in the photoactive region may comprise or consist essentially of a perovskite compound of formula (ID) selected from the group consisting of: [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Pb[Br y I 1-y ]3. [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Pb[Br y Cl 1-y ]3. [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Pb[I y Cl 1-y ]3. [(CH3NH3) x Cs 1-x ]Pb[Br y I 1-y ]3. [(CH3NH3) x Cs 1-x ]Pb[Br y Cl 1-y ]3. [(CH3NH3) x Cs 1-x ]Pb[I y Cl 1-y ]3. [(H2N–C(H)=NH2) x Cs 1-x ]Pb[Br y I1-y ]3. [(H2N–C(H)=NH2) x Cs 1-x ]Pb[Br y Cl 1-y ]3. [(H2N–C(H)=NH2) x Cs 1-x ]Pb[I y Cl 1-y ]3. [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Sn[Br y I 1-y ]3. [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Sn[Br y Cl 1-y ]3. [(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Sn[I y Cl 1-y ]3. [(CH3NH3) x Cs 1-x ]Sn[Br y I 1-y ]3. [(CH3NH3) x Cs 1-x ]Sn[Br y Cl 1-y ]3. [(CH3NH3) x Cs 1-x ]Sn[I y Cl 1-y ]3. [(H2N–C(H)=NH2) x Cs 1-x ]Sn[Br y I 1-y ]3. [(H2N–C(H)=NH2) x Cs 1-x ]Sn[Br y Cl 1-y ]3 and [(H2N–C(H)=NH2) x Cs 1-x ]Sn[I y Cl 1-y ]3, wherein x and y are both greater than 0 and less than 1, for example, x and y can be 0.01 to 0.99, or 0.05 to 0.95, or 0.1 to 0.9. Preferably, the photoactive material in the photoactive region comprises the formula [(H2N-C(H)=NH2) x Cs 1-x]Pb[Br y I 1-y ]3 perovskite compound, wherein x and y are both 0.1 to 0.9.
[0382] The crystalline A / M / X material deposited on the substrate and the crystalline A / M / X material in the photoactive zone may be different or the same. Typically, the crystalline A / M / X material deposited on the substrate and the crystalline A / M / X material in the photoactive zone are different. For example, the crystalline A / M / X material in the photoactive zone may comprise or consist essentially of a compound of Formula (IA), (IB), (IC), (ID), (IE), (IF), (IG), (IH), (IIIA), (IIIB), (IIIC), (VIA), (VIB) or (VIC) described herein, preferably a compound of Formula (I) described herein, such as a compound of Formula (IA), (IB), (IC), (ID), (IE), (IF), (IG) or (IH), And the crystalline A / M / X material deposited on the substrate may contain or consist essentially of a compound of Formula (IA), (IB), (IC), (ID), (IE), (IF), (IG), (IH), (IIIA), (IIIB), (IIIC), (VIA), (VIB) or (VIC) described herein, preferably a compound of Formula (I) described herein, for example, a compound of Formula (IA), (IB), (IC), (ID), (IE), (IF), (IG) or (IH).
[0383] For example, the crystalline A / M / X material in the photoactive region may contain or consist essentially of a compound of formula (IA), and the crystalline A / M / X material deposited on the substrate may contain or consist essentially of a compound of formula (IB), formula (IC), formula (ID), formula (IE), formula (IF), formula (IG), formula (IH), formula (IIIA), formula (IIIB), formula (IIIC), formula (VIA), formula (VIB), or formula (VIC) described herein, for example, a compound of formula (IB), formula (IC), formula (ID), formula (IE), formula (IF), formula (IG), or formula (IH) described herein, preferably a compound of formula (ID), formula (IE), or formula (IF) described herein.
[0384] For example, the crystalline A / M / X material in the photoactive region may comprise or consist essentially of a compound of formula APbI3, APbBr3, APbCl3, ASnI3, ASnBr3, or ASnCl3, wherein A is a cation as described herein, preferably APbI3, more preferably CH3NH3PbI3, and the crystalline A / M / X material deposited on the substrate may comprise or consist essentially of a compound of formula CH3NH3[Pb z Sn 1-z ]Cl3、CH3NH3[Pb z Sn 1-z ]Br3、CH3NH3[Pb z Sn 1-z ]I3, Cs[Pb z Sn 1-z ]Cl3、Cs[Pb z Sn 1-z ]Br3、Cs[Pb z Sn 1-z ]I3, (H2N–C(H)=NH2)[Pb z Sn 1-z ]Cl3、(H2N–C(H)=NH2)[Pb z Sn 1-z ]Br3 or (H2N–C(H)=NH2)[Pb z Sn 1-z ]I3, wherein z is greater than 0 and less than 1, for example, z can be 0.01 to 0.99, or 0.05 to 0.95, or 0.1 to 0.9; or a compound of the formula [(CH3NH3) x (H2N–C(H)=NH2) 1-x ][Pb z Sn 1-z ]Cl3, [(CH3NH3) x (H2N–C(H)=NH2) 1-x ][Pb z Sn 1-z ]Br3, [(CH3NH3) x (H2N–C(H)=NH2) 1-x ][Pb z Sn 1-z ]I3, [(CH3NH3) x Cs 1-x ][Pb z Sn 1-z ]Cl3, [(CH3NH3) x Cs 1-x ][Pb z Sn 1-z]Br3, [(CH3NH3) x Cs 1-x ][Pb z Sn 1-z ]I3, [(H2N–C(H)=NH2) x Cs 1-x ][Pb z Sn 1-z ]Cl3, [(H2N–C(H)=NH2) x Cs 1-x ][Pb z Sn 1-z ]Br3 or [(H2N–C(H)=NH2) x Cs 1-x ][Pb z Sn 1-z ]I3, wherein x and z are both greater than 0 and less than 1, for example, x and z can be 0.01 to 0.99, or 0.05 to 0.95, or 0.1 to 0.9; preferably CH3NH3[Pb z Sn 1-z ]I3 or [(CH3NH3) x (H2N–C(H)=NH2) 1-x ][Pb z Sn 1-z ]I3, wherein x, y and z are respectively 0.05 to 0.95, or 0.1 to 0.9.
[0385] The photoactive material in the photoactive region may include a perovskite compound of the formula:
[0386] Cs z (H2N–C(H)=NH2) (1-z) [M][X]3
[0387] wherein: [M] is as defined above, and may include, for example, Pb, Sn, or a mixture of Pb and Sn; [X] is one or more different halide anions, such as two or more different halide anions; and z is 0.01 to 0.99. For example, the perovskite may be of the formula Cs z (H2N–C(H)=NH2) (1-z) [Pb x Sn 1-x ]I3、Cs z (H2N–C(H)=NH2) (1-z) [Pb x Sn 1-x ]Br3 or Cs z (H2N–C(H)=NH2) (1-z) [Pb x Sn1-x ]I y Br 3(1-y) A compound wherein z is as defined above, x is from 0 to 1 (and may be, for example, 0.5), and y is from 0.01 to 0.99.
[0388] The photoactive material in the photoactive region may include a compound of the formula:
[0389] Cs z (H2N–C(H)=NH2) (1-z) [M]X 3y X′ 3(1–y)
[0390] wherein: [M] is as defined above, and may include, for example, Pb, Sn, or a mixture of Pb and Sn; and X is selected from I – Br – , Cl – and F – X' is a second halide anion different from the first halide anion and is selected from I – Br – , Cl – and F – ; z is 0.01 to 0.99; and y is 0.01 to 0.99. For example, the perovskite may be of the formula Cs z (H2N–C(H)=NH2) (1-z) PbB 3y I 3(1–y) of compounds.
[0391] The crystalline A / M / X material in the photoactive region may comprise or consist essentially of a compound of formula (ID), and the crystalline A / M / X material deposited on the substrate may comprise or consist essentially of a compound of formula (IA), formula (IB), formula (IC), formula (IE), formula (IF), formula (IG), formula (IH), formula (IIIA), formula (IIIB), formula (IIIC), formula (VIA), formula (VIB) or formula (VIC) described herein, for example, a compound of formula (IA), formula (IB), formula (IC), formula (IE), formula (IF), formula (IG) or formula (IH) described herein, preferably a compound of formula (IA), formula (IE) or formula (IF) described herein.
[0392] For example, the crystalline A / M / X material in the photoactive region may comprise or consist essentially of: x (H2N–C(H)=NH2) 1-x ]Pb[Br y I 1-y]3、[(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Pb[Br y Cl 1-y ]3、[(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Pb[I y Cl 1-y ]3、[(CH3NH3) x Cs 1-x ]Pb[Br y I 1-y ]3、[(CH3NH3) x Cs 1-x ]Pb[Br y Cl 1-y ]3、[(CH3NH3) x Cs 1-x ]Pb[I y Cl 1-y ]3、[(H2N–C(H)=NH2) x Cs 1-x ]Pb[Br y I 1-y ]3、[(H2N–C(H)=NH2) x Cs 1-x ]Pb[Br y Cl 1-y ]3、[(H2N–C(H)=NH2) x Cs 1-x ]Pb[I y Cl 1-y ]3、[(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Sn[Br y I 1-y ]3、[(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Sn[Br y Cl 1-y ]3、[(CH3NH3) x (H2N–C(H)=NH2) 1-x ]Sn[I y Cl 1-y ]3、[(CH3NH3) x Cs 1-x ]Sn[Br y I 1-y ]3、[(CH3NH3) x Cs 1-x]Sn[Br y Cl 1-y ]3. [(CH3NH3) x Cs 1-x ]Sn[I y Cl 1-y ]3. [(H2N–C(H)=NH2) x Cs 1-x ]Sn[Br y I 1-y ]3. [(H2N–C(H)=NH2) x Cs 1-x ]Sn[Br y Cl 1-y ]3 or [(H2N–C(H)=NH2) x Cs 1-x ]Sn[I y Cl 1-y ]3, wherein x and y are both greater than 0 and less than 1, for example, x and y can be 0.01 to 0.99, or 0.05 to 0.95, or 0.1 to 0.9; preferably the formula [(CH3NH3) x Cs 1-x ]Pb[Br y I 1-y ]3, wherein x and y are 0.05 to 0.95, or 0.1 to 0.9, and the crystalline A / M / X material deposited on the substrate may comprise or consist essentially of: a compound of formula APbI3, APbBr3, APbCl3, ASnI3, ASnBr3 or ASnCl3, wherein A is a cation as described herein, preferably APbI3, more preferably CH3NH3PbI3; or a compound of formula CH3NH3[Pb z Sn 1-z ]Cl3、CH3NH3[Pb z Sn 1-z ]Br3、CH3NH3[Pb z Sn 1-z ]I3, Cs[Pb z Sn 1-z ]Cl3、Cs[Pb z Sn 1-z ]Br3、Cs[Pb z Sn 1-z ]I3, (H2N–C(H)=NH2)[Pb z Sn 1-z ]Cl3、(H2N–C(H)=NH2)[Pb z Sn 1-z ]Br3 and (H2N–C(H)=NH2)[Pb z Sn1-z ]I3, wherein z is greater than 0 and less than 1, for example, z can be 0.01 to 0.99, or 0.05 to 0.95, or 0.1 to 0.9, preferably CH3NH3[Pb z Sn 1-z ]I3, wherein z is 0.05 to 0.95, or 0.1 to 0.9.
[0393] Alternatively, the crystalline A / M / X material deposited on the substrate and the crystalline A / M / X material in the photoactive region can both be the same compound of Formula (IA), (IB), (IC), (ID), (IE), (IF), (IG), (IH), (IIIA), (IIIB), (IIIC), (VIA), (VIB) or (VIC) described herein, but have different chemical compositions (for example, one can be CH3NH3PbI3 and the other can be CH3NH3PbBr3, or one can be CH3NH3PbI3 and the other can be CH3NH3SnI3).
[0394] Typically, the photoactive region includes one or more charge transport layers, for example, two charge transport layers. The charge transport layer can be an electron transport (n-type) material layer as described herein, or a hole transport (p-type) material layer as described herein. Typically, the photoactive region includes two charge transport layers, one of which is an electron transport (n-type) material layer as described herein, and the other charge transport layer is a hole transport (p-type) material layer as described herein.
[0395] Preferably, the photoactive region comprises an electron transport (n-type) material layer, wherein the electron transport material comprises PCBM, and the other charge transport layer is a hole transport (p-type) material layer, wherein the hole transport material comprises spiro-OMeTAD or spiro(TFSI)2.
[0396] Thus, the photoactive region may comprise the following layers in the following order:
[0397] a layer of charge transport material, preferably a layer of hole transport (p-type) material, more preferably wherein the hole transport material comprises spiro-OMeTAD;
[0398] A layer of photoactive material as described herein;
[0399] • A layer of charge transport material, preferably an electron transport (n-type) material layer, more preferably wherein the electron transport material comprises PCBM.
[0400] The electron transport (n-type) material layer may, for example, include an organic n-type material layer and an inorganic n-type material layer. Typically, the organic n-type material layer (which may be as further defined herein, for example it may be PCBM) is arranged on the inorganic n-type material layer (which may also be as further defined herein, and may be, for example, SnO2). When the electron transport (n-type) material layer is in contact with an electrode, for example when it is in contact with a first electrode comprising a transparent conductive oxide such as, for example, fluorine-doped tin oxide (FTO) or indium-doped tin oxide (ITO), the electron transport (n-type) material layer typically has this structure. Typically, the inorganic n-type layer of the electron transport material layer (typically SnO2) is in contact with a transparent conductive oxide, such as FTO. In fact, the inventors have found that such an inorganic n-type layer improves the electrical contact of the organic n-type layer with the transparent conductive oxide. Similarly, the inventors have found that an organic n-type layer (e.g., PCBM) forms a more stable electrical contact with the photoactive material than an inorganic n-type layer, particularly when the photoactive material is a crystalline A / M / X material as defined herein. They have also found that having a double n-layer helps suppress pinholes in the n-layer. Thus, the present invention generally employs two n-type layers between the electrode comprising a transparent conductive oxide and the photoactive material. The inventors have found in particular that SnO2 improves the electrical contact of PCBM with FTO, and that a double SnO2 / PCBM n-type layer is improved compared to SnO2 alone because PCBM forms a more stable electrical contact with the perovskite photoactive material.
[0401] Typically, the total thickness of the photoactive region including the photoactive material layer and optionally the charge transport material layer is from 10 nm to 5000 nm, for example from 50 nm to 3000 nm, from 100 nm to 2000 nm, from 200 nm to 1500 nm, preferably from 250 nm to 1250 nm. Typically, when any charge transport material layer is present, their single layer thickness is less than 200 nm, for example less than 150 nm or less than 100 nm, from 1 nm to 100 nm, typically from 10 nm to 75 nm, typically from 30 nm to 60 nm.
[0402] The photoactive material layer in the photoactive region can also be produced using the aprotic solvent / organic amine solvent system used in the method of the present invention. For example, the method of the present invention can further include the step of producing the substrate by arranging a layer of crystalline A / M / X material, the crystalline A / M / X material comprising the formula [A] as described herein: a [M] b [X] c wherein the method comprises forming the crystalline A / M / X material layer by arranging a film-forming solution on a substrate layer, the substrate layer being, for example, an n-type layer or a p-type layer in the substrate, wherein the film-forming solution comprises:
[0403] (a) one or more M cations; and
[0404] (b) a solvent;
[0405] The solvents include
[0406] (i) an aprotic solvent; and
[0407] (ii) Organic amines.
[0408] Alternatively, the photoactive material layer in the photoactive region may be produced according to other methods known to the skilled person. For example, the method of the present invention may further comprise the step of producing the substrate by arranging a layer of crystalline A / M / X material comprising [A] as described herein. a [M] b [X] c wherein the method comprises forming a crystalline A / M / X material layer by a conventional high boiling point solvent deposition method, for example, by disposing (e.g., by spin coating) a solution of an A / M / X precursor compound in DMF, DMSO or a mixture thereof on a substrate precursor.
[0409] Triple Junction Device
[0410] In one embodiment, the substrate comprises two separated photoactive regions as described herein, wherein each photoactive region comprises a photoactive material. Two separated photoactive regions refer to that the substrate comprises two photoactive regions that are not in direct physical contact with each other. When the substrate comprises two separated photoactive regions, the crystalline A / M / X material layer formed on the substrate forms part of a third photoactive region. Therefore, the multi-junction device produced according to the method of the present invention may include three photoactive regions. Therefore, the multi-junction device produced according to the method of the present invention may be a triple-junction device. Typically, with reference to the method of the present invention, a film-forming solution as defined herein is used to form at least two photoactive regions in a multi-junction device.
[0411] In this embodiment, an additional charge recombination layer as described herein may be arranged between two photoactive regions in the substrate. Thus, the substrate may include two photoactive regions separated by another charge recombination layer. For example, the substrate may include the following layers in the following order:
[0412] · optionally a charge transport layer, preferably a layer of electron transport (n-type) material;
[0413] Charge recombination layer;
[0414] Photoactive area;
[0415] Charge recombination layer;
[0416] Photoactive region.
[0417] Each photoactive region may be as described above. For example, each photoactive region may include one or more charge transport layers as described herein, such as two charge transport layers. The charge transport layer may be an electron transport (n-type) material layer as described herein, or a hole transport (p-type) material layer as described herein. Typically, each photoactive region includes two charge transport layers, one of which is an electron transport (n-type) material layer as described herein, and the other charge transport layer is a hole transport (p-type) material layer as described herein. These layers are typically arranged on both sides of the photoactive material layer as described herein (above and below, respectively).
[0418] Preferably, each photoactive region comprises a layer of electron transport (n-type) material, wherein the electron transport material comprises PCBM, and the other charge transport layer is a layer of hole transport (p-type) material, wherein the hole transport material comprises spiro-OMeTAD.
[0419] The electron transport material layer in one of the photoactive regions may include an organic n-type material layer and an inorganic n-type material layer. Typically, the organic n-type material (e.g., PCBM) layer is disposed on an inorganic n-type material (e.g., SnO2) layer. When the electron transport (n-type) material layer is in contact with an electrode, for example, when it is in contact with a first electrode comprising a transparent conductive oxide (such as, for example, fluorine-doped tin oxide, FTO), the electron transport (n-type) material layer typically has this structure.
[0420] Thus, each photoactive region may include the following layers in the following order:
[0421] a layer of charge transport material, preferably a layer of hole transport (p-type) material, more preferably wherein the hole transport material comprises spiro-OMeTAD;
[0422] A layer of photoactive material as described herein;
[0423] • A charge transport material layer, preferably an electron transport (n-type) material layer, more preferably, wherein the electron transport material comprises PCBM, or comprises PCBM and SnO2.
[0424] Each photoactive material in each photoactive region may include a crystalline A / M / X material comprising formula [A] as described herein: a [M] b [X] c For example, each photoactive material in the photoactive region may comprise a compound of formula [A] a [M] b [X] cwherein the compound is a compound of Formula (IA), (IB), (IC), (ID), (IE), (IF), (IG), (IH), (IIIA), (IIIB), (IIIC), (VIA), (VIB), or (VIC) as described herein. Typically, each photoactive material in the photoactive region comprises formula [A] a [M] b [X] c A compound of formula (I), wherein the compound is a compound of formula (I), for example, a compound of formula (IA), formula (IB), formula (IC), formula (ID), formula (IE), formula (IF), formula (IG) or formula (IH).
[0425] The crystalline A / M / X material in the two photoactive regions may be the same crystalline A / M / X material or different crystalline A / M / X materials as described herein. Preferably, at least two of the crystalline A / M / X materials selected from the crystalline A / M / X material deposited on the substrate and the crystalline A / M / X material in the two photoactive regions are different. In one embodiment, all three of the crystalline A / M / X materials selected from the crystalline A / M / X material deposited on the substrate and the crystalline A / M / X material in the two photoactive regions are different.
[0426] For example, the photoactive material layer in one photoactive zone may comprise a compound of Formula ID, the photoactive material layer in another photoactive zone may comprise a compound of Formula IA, and the crystalline A / M / X material deposited on the substrate may comprise a compound of Formula IE.
[0427] Preferably, at least one of the crystalline A / M / X material layers in one of the photoactive regions is deposited using an aprotic solvent / organic amine solvent system as used in the method of the present invention. In one embodiment, each of the photoactive material layers in each photoactive region can be deposited using an aprotic solvent / organic amine solvent system as used in the method of the present invention.
[0428] Alternatively, one layer of the photoactive material layer in one of the photoactive regions is produced according to other methods known to the skilled person. For example, the photoactive material layer can be deposited by conventional high boiling point solvent deposition methods, such as by spin coating a solution of the A / M / X precursor compound in DMF, DMSO or a mixture thereof.
[0429] electrode
[0430] The substrate typically includes a first electrode. The first electrode may include a metal such as silver, gold, aluminum or tungsten, or a transparent conductive oxide such as fluorine-doped tin oxide (FTO) or indium-doped tin oxide (ITO). Typically, the first electrode includes a transparent conductive oxide. The thickness of the layer of the first electrode is typically 5 nm to 100 nm.
[0431] The substrate typically includes:
[0432] i) a first electrode, preferably, wherein the first electrode comprises a transparent conductive oxide,
[0433] ii) a photoactive region, said photoactive region preferably comprising a crystalline A / M / X material comprising the formula [A] as described herein a [M] b [X] c The compound
[0434] iii) a charge recombination layer as described herein, disposed on the photoactive region; and
[0435] iv) optionally a layer of charge transport material as described herein, disposed on the charge recombination layer.
[0436] To fabricate a triple junction device, the substrate typically includes
[0437] i) a first electrode, preferably, wherein the first electrode comprises a transparent conductive oxide,
[0438] ii) a photoactive region, said photoactive region preferably comprising a crystalline A / M / X material comprising the formula [A] as described herein a [M] b [X] c The compound
[0439] iii) a charge recombination layer as described herein, disposed on the photoactive region;
[0440] iv) a photoactive region, said photoactive region preferably comprising a crystalline A / M / X material comprising the formula [A] as described herein a [M] b [X] c The compound
[0441] v) a charge recombination layer as described herein, disposed on the photoactive region; and
[0442] vi) optionally a layer of charge transport material as described herein, disposed on the charge recombination layer.
[0443] The first electrode may be deposited on a layer of transparent material, such as a glass layer. The layer of transparent material may be treated with an anti-reflective coating. Typically, the anti-reflective coating comprises magnesium fluoride (MgF2).
[0444] The method may further include disposing a second electrode on the crystalline A / M / X material layer disposed on the substrate.
[0445] The second electrode may be as defined above for the first electrode. Typically, the second electrode comprises a metal (e.g., a simple metal) or is substantially composed of a metal (e.g., a simple metal). Examples of metals that the second electrode material may include or is substantially composed of include silver, gold, copper, aluminum, platinum, palladium, or tungsten. The second electrode may be arranged by vacuum evaporation. The thickness of the second electrode material layer is typically 1 nm to 250 nm, preferably 5 nm to 100 nm.
[0446] Preferably, the method comprises arranging a charge transport material layer as described herein on a crystalline A / M / X material layer arranged on a substrate, and arranging a second electrode on the charge transport material. The charge transport material layer may be an electron transport (n-type) material layer as described herein, or a hole transport (p-type) material layer as described herein. Typically, the charge transport material layer arranged on the crystalline A / M / X material layer is a hole transport (p-type) material layer as described herein, preferably, wherein the hole transport material comprises spiro-OMeTAD.
[0447] Thus, a multi-junction device produced by the method of the present invention may comprise the following layers in the following order:
[0448] A first electrode;
[0449] Photoactive area;
[0450] Charge recombination layer;
[0451] - optionally a layer of charge transport material, preferably an electron transport (n-type) material, preferably wherein the electron transport material comprises PCBM;
[0452] A layer of crystalline A / M / X material as described herein;
[0453] - optionally a layer of charge transport material, preferably a layer of hole transport (p-type) material, preferably wherein the hole transport material comprises spiro-OMeTAD;
[0454] A second electrode.
[0455] In the case of a triple junction device produced by the method of the present invention, the triple junction device may comprise the following layers in the following order:
[0456] A first electrode;
[0457] Photoactive area;
[0458] Charge recombination layer;
[0459] Photoactive area;
[0460] Charge recombination layer;
[0461] - optionally a layer of charge transport material, preferably an electron transport (n-type) material, preferably wherein the electron transport material comprises PCBM;
[0462] A layer of crystalline A / M / X material as described herein;
[0463] - optionally a layer of charge transport material, preferably a layer of hole transport (p-type) material, preferably wherein the hole transport material comprises spiro-OMeTAD;
[0464] A second electrode.
[0465] In one embodiment, the film-forming solution described herein is used to form at least two photoactive regions in a multi-junction device. In this embodiment, the method of the present invention may include forming a crystalline A / M / X material layer by disposing the film-forming solution on a substrate, wherein the substrate includes: a photoactive region, which contains a photoactive material; and a charge recombination layer, which is disposed on the photoactive region by solution deposition; and then the following further steps:
[0466] Optionally, forming a layer of charge transport material as described herein on the crystalline A / M / X material layer already disposed on the substrate, preferably wherein the charge transport material comprises a hole transport (p-type) material;
[0467] · forming another charge recombination layer as described herein;
[0468] Depositing a layer of crystalline A / M / X material using a film-forming solution as described herein to form another photoactive region; and optionally forming one or more charge transport layers as described herein;
[0469] • Forming the second electrode.
[0470] Such a device may therefore comprise the following layers in the following order:
[0471] A first electrode;
[0472] Photoactive area;
[0473] Charge recombination layer;
[0474] - optionally a layer of charge transport material, preferably an electron transport (n-type) material, preferably wherein the electron transport material comprises PCBM;
[0475] A layer of crystalline A / M / X material as described herein;
[0476] - optionally a layer of charge transport material, preferably a layer of hole transport (p-type) material, preferably wherein the hole transport material comprises spiro-OMeTAD;
[0477] Charge recombination layer;
[0478] Optionally, a layer of charge transport material, preferably an electron transport (n-type) material layer, preferably, wherein the electron transport material comprises PCBM;
[0479] A layer of crystalline A / M / X material as described herein;
[0480] Optionally, a layer of charge transport material, preferably a layer of hole transport (p-type) material, preferably, wherein the hole transport material comprises spiro-OMeTAD;
[0481] A second electrode.
[0482] Multi-junction devices
[0483] The present invention also relates to a multi-junction device obtained or obtainable by the method of the present invention. The multi-junction device may include any of the features described above with respect to the method for producing a multi-junction device. For example, the multi-junction device may include any combination of layer sequences and materials as described above. Moreover, the crystalline A / M / X materials may each be further defined anywhere in this document.
[0484] In one embodiment, the present invention also relates to a multi-junction device, comprising:
[0485] (a) at least two photoactive regions, wherein at least one photoactive region comprises a layer of crystalline A / M / X material, the crystalline A / M / X material comprising the formula [A] a [M] b [X] c The compound
[0486] wherein: [A] comprises one or more A cations; [M] comprises one or more M cations, the M cations being metal or metalloid cations; [X] comprises one or more X anions; a is a number from 1 to 6; b is a number from 1 to 6; and c is a number from 1 to 18; and
[0487] (b) A charge recombination layer comprising nanoparticles of a transparent conductive oxide.
[0488] The nanoparticles of transparent conductive oxide may be any nanoparticles of transparent conductive oxide as described herein. For example, the nanoparticles of transparent conductive oxide may be indium tin oxide (ITO) nanoparticles, preferably ITO nanoparticles having a size of less than 100 nm.
[0489] The present invention also relates to a multi-junction device, comprising:
[0490] (a) at least two photoactive regions, wherein at least one photoactive region comprises a layer of crystalline A / M / X material, the crystalline A / M / X material comprising the formula [A] a [M] b [X] c wherein: [A] comprises one or more A cations; [M] comprises one or more M cations, the M cations being metal or metalloid cations; [X] comprises one or more X anions; a is a number from 1 to 6; b is a number from 1 to 6; and c is a number from 1 to 18; and
[0491] (b) A charge recombination layer comprising a conductive polymer.
[0492] In the above multi-junction device, [A], [M] and [X] may all be as described herein. Each A / M / X material may be further defined as herein. Moreover, each photoactive region may be further defined as herein, for example, each photoactive region may further include an n-type material layer and a p-type material layer, and the n-type material and the p-type material may be further defined as herein.
[0493] The conductive polymer can be any conductive polymer described herein. For example, the conductive polymer can include poly(3,4-ethylenedioxythiophene) and polystyrene sulfonate (PEDOT:PSS).
[0494] In the above-mentioned multi-junction device, the charge recombination layer generally comprises nanoparticles of transparent conductive oxide and a conductive polymer, and the nanoparticles of the transparent conductive oxide and the conductive polymer may be further defined as anywhere in this document. Thus, the charge recombination layer may comprise (i) nanoparticles of indium tin oxide (ITO), and (ii) a polymer comprising poly(3,4-ethylenedioxythiophene) and polystyrene sulfonate.
[0495] In the above multi-junction device, two of the photoactive regions may include a crystalline A / M / X material layer as described herein. In one embodiment, the above multi-junction device includes at least three photoactive regions. Preferably, each photoactive region includes a crystalline A / M / X material layer as described herein. Each crystalline A / M / X material may include or be substantially composed of the following: a compound of formula (IA), formula (IB), formula (IC), formula (ID), formula (IE), formula (IF), formula (IG), formula (IH), formula (IIIA), formula (IIIB), formula (IIIC), formula (VIA), formula (VIB) or formula (VIC) described herein, preferably a compound of formula (I) described herein, such as a compound of formula (IA), formula (IB), formula (IC), formula (ID), formula (IE), formula (IF), formula (IG) or formula (IH). Each photoactive region may further include an n-type layer and a p-type layer as further defined herein.
[0496] The present invention also relates to a multi-junction device, comprising
[0497] (a) at least three photoactive regions, wherein each photoactive region comprises a layer of crystalline A / M / X material, the crystalline A / M / X material comprising the formula [A] a [M] b [X] c The compound
[0498] wherein: [A] comprises one or more A cations; [M] comprises one or more M cations, the M cations being metal or metalloid cations; [X] comprises one or more X anions; a is a number from 1 to 6; b is a number from 1 to 6; and c is a number from 1 to 18; and
[0499] (b) at least one charge recombination layer disposed between the photoactive regions.
[0500] In a multi-junction device comprising three photoactive regions, [A], [M] and [X] may all be as described herein.
[0501] Typically, at least two charge recombination layers are arranged between the photoactive regions. For example, a multijunction device may include the following layers in the following order:
[0502] Photoactive area;
[0503] Charge recombination layer;
[0504] Photoactive area;
[0505] Charge recombination layer;
[0506] Photoactive region.
[0507] Typically, at least one of the charge recombination layers comprises nanoparticles of a conductive polymer or a transparent conductive oxide. For example, each charge recombination layer comprises nanoparticles of a conductive polymer or a transparent conductive oxide.
[0508] Typically, at least one of the charge recombination layers comprises nanoparticles of a transparent conductive oxide and a conductive polymer. For example, each charge recombination layer may comprise nanoparticles of a transparent conductive oxide and a conductive polymer. The nanoparticles of the transparent conductive oxide and the conductive polymer may be as described herein, for example, the nanoparticles of the transparent conductive oxide may be indium tin oxide (ITO) nanoparticles, preferably ITO nanoparticles having a size of less than 100 nm, and the conductive polymer may comprise poly(3,4-ethylenedioxythiophene) and polystyrene sulfonate (PEDOT:PSS). Therefore, each of the charge recombination layer or multiple charge recombination layers may comprise (i) nanoparticles of indium tin oxide (ITO), and (ii) a polymer comprising poly(3,4-ethylenedioxythiophene) and polystyrene sulfonate (PEDOT:PSS).
[0509] In the above-mentioned multi-junction device, at least two crystalline A / M / X materials may be different from each other. In one embodiment, more than two crystalline A / M / X materials are different from each other. For example, in a multi-junction device in which there are three crystalline A / M / X materials, all three crystalline A / M / X materials may be different from each other. The crystalline A / M / X material in each photoactive region may include the following or be substantially composed of the following: a compound of formula (IA), formula (IB), formula (IC), formula (ID), formula (IE), formula (IF), formula (IG), formula (IH), formula (IIIA), formula (IIIB), formula (IIIC), formula (VIA), formula (VIB) or formula (VIC) described herein, preferably a compound of formula (I) described herein, such as a compound of formula (IA), formula (IB), formula (IC), formula (ID), formula (IE), formula (IF), formula (IG) or formula (IH). Each photoactive region may further include at least one, preferably two charge transport layers, such as an n-type layer and a p-type layer as further defined herein.
[0510] The multi-junction device as described above may further comprise a first electrode and a second electrode as described herein, wherein a photoactive region and a charge recombination layer or multiple charge recombination layers are arranged between the first electrode and the second electrode. Preferably, the first electrode comprises a transparent conductive oxide and the second electrode comprises a single elemental metal.
[0511] Typically, the multi-junction device described herein is selected from the group consisting of: optoelectronic device, photovoltaic device, solar cell, photodetector, photodiode, photoelectric sensor, color display device, transistor, photosensitive transistor, phototransistor, solid-state triode, battery, battery electrode, capacitor, supercapacitor, light emitting device, light emitting diode and laser. For example, the multi-junction device can be a photoelectric device. Examples of optoelectronic devices include photovoltaic devices, photodiodes (including solar cells), phototransistors, photomultiplier tubes, photoresistors and light emitting devices. Preferably, the multi-junction device is a photovoltaic device or a light emitting device.
[0512] Example
[0513] Advantages of the present invention will be described below with reference to some specific embodiments.
[0514] Here, we adopt the previous method of Noel et al. (NK Noel, SN Habisreutinger, B. Wenger, MT Klug, MT MB Johnston, RJ Nicholas, DT Moore, HJ Snaith, Energy Environ. Sci. 2017, 10, 145) introduced acetonitrile / methylamine (ACN / MA) composite solvent to sequentially process the perovskite absorber layer on the underlying perovskite device. This architecture using all-solution processing has the potential to be suitable for manufacturing large-area films on rigid and flexible substrates using deposition techniques such as roll-to-roll (R2R) processing, blade coating or inkjet printing. A fully solution-processed tandem architecture is proposed that can achieve a stable power conversion efficiency (PCE) of more than 15% and provide an open circuit voltage (V) of 2.18V. oc ). In addition, we demonstrated that the mixed metal Sn / Pb perovskite MAPb 0.75 Sn 0.25 I3 can also be processed via the ACN / MA solvent system, where the reducing nature of MA avoids the need to use SnF2 to achieve respectable efficiencies, enabling the use of a nip architecture to achieve scanned PCEs in excess of 11% (stabilized at 10.5%). 0.75 Sn 0.25 I3 perovskite material extends multi-junction light absorption to 925nm, and the first monolithic triple-junction perovskite solar cell has an open circuit voltage (V) of 2.83V oc). Optoelectronic modeling was used to validate the experimental results and reveal the optical losses present in this particular architecture. The electronic properties of currently feasible 1.94eV / 1.57eV / 1.24eV perovskite materials were then used to model a triple-junction perovskite solar cell, confirming that a PCE of 24.3% and a corresponding V of 3.15V could be achieved. oc of triple junction devices.
[0515] Results and discussion
[0516] All-perovskite monolithic 2T tandem and multi-junction solar cells require tunnel junctions (TJs) or recombination layers to provide a means for establishing electronic series connections between different sub-cells. Subsequently, the sum of the photovoltages generated by each sub-cell results in a high-voltage device. However, due to charge conservation, the current density flowing out of each sub-cell must match, and the current will be limited by the lowest current density generated by any sub-junction. Therefore, in order to maximize the photocurrent density in the 2T monolithic string stack, the two sub-cells should produce equal current densities, which can be achieved by finely tuning the band gap and thickness of each junction. The recombination layers between sub-cells must meet strict requirements. First, they must be able to make ohmic contact with the charge extraction layer and promote the recombination of collected electrons and holes without introducing resistive losses. Second, they must be as optically transparent as possible to avoid stray absorption of light. Third, the deposition of the recombination layer should not damage any of the layers below, which is usually achieved by introducing a "buffer layer" during sputtering or by solution processing using orthogonal solvents. Finally, the interlayer must provide a sufficient barrier to solvent penetration to prevent redissolution of the underlying perovskite layer or other electronic layers when another perovskite layer is subsequently processed.
[0517] Here, composite layer and nip perovskite solar cell architectures that satisfy these constraints are developed. For the composite layer, a combination of a PEDOT:PSS layer followed by an ITO nanoparticle layer was found to work well. In the first case, a “wide bandgap”, i.e., pure lead-based perovskite tandem cell was developed by processing a top cell of approximately 1.94 eV (determined by the Tauc plot shown in Figure 5) on top of a 1.57 eV bottom cell. The wide bandgap junction was processed first, so the solvent orthogonality issue did not have to be overtly considered. The FA was therefore prepared following the conventional solution processing route. 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3, which has 2% (relative to the molar concentration of Pb) potassium ions (K +) added (see Z.Tang, T.Bessho, F.Awai, T.Kinoshita, MMMaitani, R.Jono, TNMurakami, H.Wang, T.Kubo, S.Uchida, H.Segawa,Sci.Rep.2017,7,12183;JKNam,SUChai,W.Cha,YJChoi,W.Kim,MSJung,J.Kwon,D.Kim,JHPark,Nano Lett.2017,17,2028;M.Muzammal uz Zaman,M.Imran,A.Saleem,AHKamboh,M.Arshad,NAKhan,P.Akhter,Phys.B Condens.Matter 2017,522,57; T.Bu,X.Liu,Y.Zhou,J.Yi,X.Huang,L.Luo,J.Xiao,Z.Ku,Y.Peng,F.Huang,Y.-B.Cheng,J.Zhong,Energy Environ.Sci.2017,10,2509;M.Abdi-Jalebi,Z.Andaji-Garmaroudi,S.Cacovich,C.Stavrakas,B.Philippe,JMRichter,M.Alsari,EPBo oker,EMHutter,AJPearson,S.Lilliu,TJSavenije,H.Rensmo,G.Divitini,C.Ducati,RHFriend,SDStranks,Nature,2018,555,497-501). As described above, the use of a deposition technique using a hydrohalic acid additive enables the preparation of highly ordered perovskite materials with grains reaching micrometers in diameter ( Figure 6) (DP McMeekin, Z. Wang, W. Rehman, F. Pulvirenti, JB Patel, NK Noel, MB Johnston, SR Marder, LM Herz, HJ Snaith, Adv. Mater. 2017, 1607039). Highly crystalline perovskite materials with low-energy disorder have been shown to suppress halide segregation (W. Rehman, RL Milot, GE Eperon, C. Wehrenfennig, JL Boland, HJ Snaith, MB Johnston, LM Herz, Adv. Mater. 2015, n / a). In addition, as shown in the recent above-mentioned report, potassium ions are used as additives to suppress ion migration and reduce the abnormal hysteresis behavior inherent in perovskite solar cells (HJSnaith, A. Abate, JM Ball, GEEperon, T. Leijtens, NK Noel, SD Stranks, JT-W. Wang, K. Wojciechowski, W. Zhang, J. Phys. Chem. Lett. 2014, 5, 1511). For this absorber material, an open circuit voltage of up to 1.27 V and a stable energy conversion efficiency of 10.9% can be obtained in a single-junction perovskite solar cell, as shown in Figure 7.
[0518] For the bottom cell processed on the top of the wide gap cell, the problem of dissolution of the underlying perovskite film must be considered. If one of the standard DMF / DMSO solvent-based approaches is adopted, the underlying perovskite film may be completely solvated and discolored, which makes it obvious that the composite layer is not impermeable to DMF or DMSO. The time these high-boiling point solvents stay on the surface is enough to slowly leak through the solution-processed intermediate layer, dissolving the underlying perovskite layer again, thereby limiting their availability in all-solution-processed tandem solar cells. ACN / MA-based composite solvent system for processing perovskite films has been previously developed, which has several obvious advantages (DPMcMeekin, Z. Wang, W. Rehman, F. Pulvirenti, JBPatel, NK Noel, MB Johnston, SR Marder, LM Herz, HJS Naith, Adv. Mater. 2017, 1607039). First, it is more volatile than DMF, so it can dry very quickly. Secondly, the solvation strength can be tuned by varying the amount of methylamine introduced. The correct amount of MA is chosen to completely dissolve the salt, but with minimal excess. It has been found that having an excess of MA in solution can have adverse effects on the device. Unwanted pinholes in the interlayer may cause the methylamine to penetrate and redissolve the underlying perovskite bottom layer. Therefore, by finely tuning the MA content in the solution to obtain a solution at its critical solubility point, the probability of the underlying layer redissolving can be minimized. This solubility point can be determined by slowly adding the ACN / MA perovskite solution to the pure ACN perovskite dispersion until the mixture becomes an all-perovskite solution. By this approach, a robust and reliable protocol for the preparation of all-perovskite multi-junction solar cells is obtained.
[0519] For best results, for MAPbI3 and MAPb processed via the ACN / MA solvent route 0.75 Sn 0.25 I3 perovskite materials all require fine-tuning of the content of metal ions at the B site. Figure 1A Figure 2 shows a series of top-view scanning electron microscopy (SEM) images of MAPbI3 perovskite films processed using an ACN / MA solvent system with various non-stoichiometric compositions prepared on phenyl-C 61 -FA on methyl butyrate (PC61BM) layer 0.83 Cs 0.17 Pb(Br 0.7 I 0.3)3 above the top cell (TC). The role of non-stoichiometric perovskite precursor solutions has been discussed previously (see Roldán-Carmona, P. Gratia, I. Zimmermann, G. Grancini, P. Gao, M. Graetzel, M. K. Nazeeruddin, Energy Environ. Sci. 2015, 8, 3550; M. Yang, Z. Li, M. O. Reese, O. G. Reid, D. H. Kim, S. Siol, T. R. Klein, Y. Yan, J. J. Berry, M. F. A. van Hest, K. Zhu, Nat. Energy 2017, 2, 17038; D. Bi, W. Tress, M. I. Dar, P. Gao, J. Luo, C. Renevier, K. Schenk, A. Abate, F. Giordano, J.-P. Correa Baena, J.-D. Decopet, S. M. Zakeeruddin, M. K. Nazeeruddin, M. Gra tzel, A. Hagfeldt, Sci. Adv. 2016, 2, e1501170; Q. Chen, H. Zhou, T.-B. Song, S. Luo, Z. Hong, H.-S. Duan, L. Dou, Y. Liu, Y. Yang, Nano Lett. 2014, 14, 4158; T. J. Jacobsson, J.-P. Correa-Baena, E. Halvani Anaraki, B. Philippe, S. D. Stranks, M. E. F. Bouduban, W. Tress, K. Schenk, J. Teuscher, J.-E. Moser, H. Rensmo, A. Hagfeldt, J. Am. Chem. Soc. 2016, 138, 10331), however, the research community has not yet reached a consensus on which type of precise non-stoichiometry is ideal. Some studies have shown that excess amounts of organic ammonium ions lead to improved performance, while others have shown the benefits of having excess PbI2 in the precursor solution. However, it is clear that these small stoichiometric changes do affect the perovskite in a variety of ways, ranging from morphology, luminescence, trap passivation, to stability.
[0520] exist Figure 1AIn Figure 1, a series of top-down SEM images are shown for various A-site and B-site compositions of the ACN-MA precursor solution adjusted from 6% excess MAI to 6% excess PbI2 when processed on top of an existing solar cell. The effect of precursor solutions with different compositions on morphology and surface coverage is observed.
[0521] In a fully solution processed tandem architecture, the presence of pinholes must be eliminated to prevent dissolution of the underlying layers. In Figure 8, the tandem solar cell performance of devices processed with different ranges of compositions is shown. The ideal composition for maximizing the efficiency of a single junction cell includes 3% excess MAI, and a fully tandem solar cell was prepared using this composition.
[0522] exist Figure 1B and Figure 1C A schematic diagram of a 2T tandem and the corresponding SEM cross-sectional image are shown in Figure 1. A conventional nip-structured solar cell was prepared and it has been found that a composite layer consisting of PEDOT:PSS followed by indium tin oxide (ITO) nanoparticles sandwiched between a 2,2',7,7'-tetrakis(N,N'-dimethoxyaniline)-9,9'-spirobifluorene (spiro-OMeTAD) p-type charge extraction layer and an n-doped PC 61 Between BM electron transporters.
[0523] exist Figure 1D The figure shows that the energy density is 100 mW cm -2 Positive and negative current density-voltage (JV) characteristics of one of the highest performing two-terminal tandem solar cells measured under simulated air mass (AM) 1.5 solar radiation. A detailed description of how the mismatch factor is calculated can be found below.
[0524] In this work, the composite layer includes a PEDOT:PSS sublayer and an indium tin oxide (ITO) nanoparticle (NP) sublayer. A high conductivity PEDOT:PSS (Heraus H1000) solution is diluted with isopropyl alcohol (IPA) and spin-coated directly on the spiro-OMeTAD layer, which acts as both a composite layer and a solvent barrier. The ITO layer is then spin-coated on it from a solvent dispersion of ITO nanoparticles (>100nm). The prepared ITO nanoparticle layer can be porous and discontinuous. However, these nanoparticles, due to their high carrier density, make the holes and PC in PEDOT:PSS 61 The electrons in the BM recombine and improve the recombination process. The ITO NP layer establishes an ohmic contact between the electron accepting layer and the hole accepting layer, thus enabling efficient charge transfer to the recombination layer.
[0525] The tandem device produced 11.5 mA cm -2 The short-circuit current density (J SC ), fill factor (FF) of 0.63, open circuit voltage (V oc ), and 15.2% energy conversion efficiency (stable) ( Fig. 9 ). Perovskite solar cells are prone to hysteresis behavior. Therefore, if Figure 3A As shown in the inset of Figure 1, a stable efficiency measurement was performed by holding the device at a fixed maximum energy point voltage of 1.72V, which achieved a stable efficiency of 15.2%. Figure 3B The external quantum efficiency (EQE) of the two junctions is shown in Figure 2, where the integrated current density of the front cell is 10.0 mA cm -2 The integrated current density of the back battery is 9.3 mA cm -2 During EQE measurements, a voltage bias equal to the V of the optical bias subcell is applied to the solar cell. oc This enables the measurement of the EQE near Jsc. Note that there is a slight mismatch in the current density between the two subcells. Fig.10 In Figure 11, the mismatch factors calculated for each material used in a multi-junction solar cell are shown. The spectrum of a xenon arc lamp can have a significant mismatch with the AM1.5G spectrum due to the large strong spikes in the infrared part of the spectrum (as shown in Figure 11). As a result, specific sub-cells of a multi-junction solar cell may be overestimated or underestimated, especially in the case of a multi-junction solar cell. In this specific case, the tandem cell is the back cell limited to the AM1.5G spectrum and the top cell limited to the solar simulator light. To account for these differences, a mismatch factor correction was applied, which reduced our estimated efficiency by about a relative 0.4%. However, in the case of a triple junction, a significant mismatch factor was present due to the strong spikes of xenon, which required a relative 32.3% reduction in efficiency to account for the spectral mismatch. Both correction factors have been applied to the reported efficiencies. The estimation of voltage loss is a key indicator of the quality of the resulting composite interlayer. As shown in Figure 12, the V of a 2T stack measured using a PEDOT:PSS / ITO NPs interlayer as the composite layer is oc Up to 2.22V, so if we assume that the two sublayers produce 1.27V for the front cell and 1.11V for the back cell, the highest measured single junction V oc , the voltage loss in the middle layer is about 180mV.
[0526] Although pure lead-based devices have been able to produce stable perovskite materials, for tandem applications, it is still very desirable to use less stable tin-based perovskites to promote narrowing the band gap. The effect of non-stoichiometric precursor solutions on MAPb was also studied by adjusting the ratio of A site to B site, as shown in Figure 2. 0.75 Sn 0.25 The material properties of I3 (with a band gap of 1.34 eV as determined by the Tauc plot, Figure 13) are affected. In order to maintain the expected MAPb 0.75 Sn 0.25 I3 perovskite composition with excess PbI2 and SnI2 added in a ratio of 75 to 25. Figure 2A Kelvin probe force microscopy (KPFM) images are shown, and when MAPb 0.75 Sn 0.25 When the I3 perovskite precursor solution contains an excess of metal ions, a significant increase in the work function is observed. Slower time-resolved photoluminescence (PL) decays are also noted, such as Figure 2B shown. Figure 2C The transient photoconductivity of the corresponding samples over a range of excitation densities is given, measuring the maximum perturbation of the conductivity decay after being photoexcited by a laser pulse. Similarly, an increase in the photoconductivity of the film with excess metal ions is observed, which means a higher effective mobility. It has been found that these longer carrier lifetimes and higher photoconductivity are associated with a substantial improvement in device performance (Figure 14), which results in an optimized MAPb of more than 11%. 0.75 Sn 0.25 I3PCE, such as Figure 2D shown.
[0527] Surprisingly, it has been found that the optimal ratio of A-site to B-site is significantly different in Sn-Pb-based perovskite materials compared to pure Pb-based perovskites. In the case of Sn / Pb-based perovskites, the research community seems to have consistently observed performance gains when using excess tin halides, most notably in the form of tin fluoride (SnF2) or tin chloride (SnF2) (see D. Zhao, Y. Yu, C. Wang, W. Liao, N. Shrestha, C. R. Grice, A. J. Cimaroli, L. Guan, R. J. Ellingson, K. Zhu, X. Zhao, R.-G. Xiong, Y. Yan, Nat. Energy 2017, 2, 17018; K. P. Marshall, M. Walker, R. I. Walton, R. A. Hatton, Nat. Energy 2016, 1, 16178; S. J. Lee, S. S. Shin, Y. C. Kim, D. Kim, T. K. Ahn, J. H. Noh, J. Seo, S. Il Seok,J.Am.Chem.Soc.2016,138,3974;MHKumar,S.Dharani,WLLeong,PPBoix,RRPrabhakar,T.Baikie,C.Shi,H.Ding,R.Ramesh,M.Asta,M.Graetzel,SGMhaisalkar,N.Mathews,Adv.Mater.2014,26, 7122; AG Kontos, A. Kaltzoglou, E. Siranidi, D. Palles, GK Angeli, MKArfanis, V. Psycharis, YSRaptis, EIKamitsos, PNTrikalitis, CCStoumpos, MGKanatzidis, P. Falaras, Inorg. Chem. 2017, 56, 84). To suppress tin from Sn 2+ To Sn 4+ The oxidation of Sn is suppressed, and SnF is conveniently used as a reducing agent. 2+Vacancies are restricted, leading to undesirable p-type behavior in Sn-based perovskites. In this study, because SnF2 has poor solubility in the ACN / MA solvent system, MA is relied upon to replace SnF2 as a reducing agent. Amines are known to act as reducing agents and are one of the most commonly used substances in the synthesis of metal nanoparticles (see JD Snand, GJ Blanchard*, 2006, DOI 10.1021 / LA060045Z). Here, the reducing property of amines is utilized, enabling the effective replacement of SnF2 with MA. Figure 14 shows a graph of non-optimized devices with different cation ratios of A site to B site. Devices with excess MAI produce almost zero PCE and almost no short-circuit density (Jsc), while devices with excess metal ions clearly show an improvement in the efficiency of single-junction devices, reaching the optimal composition with an excess of 15% metal ions. Therefore, tin-based perovskites require not only reducing agents to suppress Sn +2 To Sn +4 oxidation, and an excess of metal ions is required to achieve optimal performance. This is consistent with the findings of Song et al., who observed that a non-stoichiometric CsSnI3 perovskite composition of 0.4:1 CsI:SnI2 was required to achieve optimal performance when processed in a reducing hydrazine atmosphere (see T.-B. Song, T. Yokoyama, S. Aramaki, MG Kanatzidis, ACS Energy Lett. 2017, 2, 897). Excess SnI2 is believed to serve as a replacement for Sn due to exposure to moisture or oxygen. 2+ Loses two electrons to become Sn 4+ Any Sn 2+ The "compensation" salt for the vacancy. Figure 2A In the MAPb with MAI-rich composition, 0.75 Sn 0.25 The deeper Fermi level of I3 perovskite is consistent with the higher concentration of Sn that is expected to lead to p-doping of perovskite. 2+ In contrast, for the metal-ion-rich perovskite film, the shallower Fermi level observed would correspond to more intrinsic perovskite materials, indicating that Sn 2+ There are fewer vacancies. Figure 2A The observed increase in carrier lifetime in the perovskite absorber is interpreted as consistent with and indicative of a transition from a high p-type material to a more intrinsic semiconductor. Furthermore, this shift in the Fermi level may induce an energy barrier between the perovskite and the electron or hole accepting layer, in this case the PC 61 BM and doped with spiro-OMETAD+ Bis(trifluoromethanesulfonyl)imide - Spiro-OMeTAD of (Spiro(TFSI)2).
[0528] Figure 3 shows the structural and performance characteristics of the first all-perovskite monolithic triple-junction solar cell, which was prepared via a solution processing route. The narrow bandgap MAPb depicted in Figure 2 0.75 Sn 0.25 The I3 perovskite solar cell is processed on top of the double-junction tandem solar cell architecture described in Figure 1 to produce a triple-junction solar cell that can absorb light up to 925nm. Figure 3A Shown by FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 / MAPb 0.75 Sn 0.25 Schematic diagram of a 2T triple junction battery composed of I3, where FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 perovskite acts as the front cell, MAPbI3 perovskite is the middle cell, and MAPb 0.75 Sn 0.25 I3 perovskite is the back cell. Figure 3B The corresponding SEM cross-sectional images are shown. Figure 3C The positive and negative current density voltage (JV) characteristics of one of the “highest performing” two-terminal triple junction solar cells are shown at 100 mW cm -2 The PCE was measured under simulated air mass (AM) 1.5 and solar radiation. The measured PCE was 7.5% (7.1% after stabilization), while Figure 3D The highest V oc This was measured on a separate device (as shown in Figure 15) and showed a stable open circuit voltage of 2.83V after 60s.
[0529] Figure 17 shows a high performance FA based on a pin architecture. 0.83 Cs 0.17 Pb 0.5 Sn 0.5 I3 perovskite, which was processed with DMF / DMSO solvent and FA without Ag electrode 0.83 Cs 0.17 Pb(Br 0.7 I 0.3)3 / MAPbI3 tandem solar cell filtering. Although not measured for a four-terminal (4T) tandem because no semi-transparent electrode was used on the front tandem stack, this measurement enables a rough estimate of the expected efficiency gain if higher performance and lower bandgap are achieved using the ACN / MA solvent system approach. Fig. 17C It shows that based on FA 0.83 Cs 0.17 Pb 0.5 Sn 0.5 The I3 junction, which has an absorption onset of 1.22 eV, achieves a PCE of 15.5% (stable) when unfiltered and 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 stacked after filtering, a PCE of 2.6% (stable) can be obtained. Therefore, narrow bandgap materials may 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 is enhanced by more than 2.6% to a PCE of 17.7%. It should also be noted that this measurement includes the air gap between the stack and the narrow-bandgap single-junction solar cell, as well as an additional PEDOT:PSS layer that would otherwise not be present in a standard monolithic triple-junction solar cell. For these reasons, we measured a lower integrated current density from the EQE, as Fig. 17B shown.
[0530] like All-perovskite triple-junction solar cells employing perovskite absorbers with bandgaps similar to those we use in this work should be able to outperform single- and double-junction efficiencies as reported by H. modeling by et al. showed that the optimized 1.22 eV bandgap material should be matched with two wider bandgap subcells of 2.04 eV and 1.58 eV to achieve 12 mA cm -2 Theoretical maximum J SC , V of 3.54V oc , and 36.6% PCE (see MT T.Leijtens, M.E.Ziffer, G.E.E.peron, M.G.Christoforo, M.D.McGehee, H.J.Snaith, A.C.E.Energy Lett. 2017, 2, 2506). However, this performance can only be achieved by reducing stray absorption and reflection losses through optically transparent interlayers. Figure 16 shows the optical properties of each interlayer used in the multi-junction stack. The PC used in the interlayer structure is about 100 nm thick. 61 The BM layer is responsible for most of the stray absorption and reflection losses.
[0531] To evaluate the true potential of this fully solution-processed all-perovskite multi-junction solar cell architecture, et al. used a similar optoelectronic model to simulate the semiconductor stack and reveal where improvements can be made to further improve the performance of multi-junction devices. Using experimental thicknesses, combined with selected electrical properties of state-of-the-art single-junction perovskite cells, FIG. 4A to FIG. 4B An estimate of the performance of the tandem stack is given, along with the corresponding modeled external quantum efficiency spectrum. It is estimated that by 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 combined with the optimal ACN / MAMAPbI3 can improve the performance of tandem solar cells (subcells with 1.94 eV and 1.57 eV bandgaps) to nearly 19%. Modeling of stacks with the same absorber and interlayer materials (e.g. FIG. 4C to FIG. 4D ), which has the state of the art MAPbI3 processed via the DMF / DMSO route, an optimized perovskite thickness, an interlayer as thin as 50nm, and a MgF2 antireflection film. These improvements enable a tandem cell to achieve a PCE of 21.8%. In this figure, an optimized stack with an enhanced front cell with improved electrical properties is also modeled, assuming that for FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3. Electroluminescence efficiency EQE EL 1%, the series resistance R S 4.10 -2 Ωcm 2 , and the shunt resistor R SH 10MΩcm 2 , increasing the achievable PCE to 26.8%. FIG. 4E to FIG. 4F The performance of the triple junction architecture is revealed, assuming that the thickness of the perovskite is targeted to the state-of-the-art MAPbI3 and FA 0.6 MA 0.4 Pb0.4 Sn 0.6 The current matching of the I3 perovskite subcell was optimized and an anti-reflection coating was added on top. By using the optimized thickness, a PCE of 26.7% was achieved, and by increasing the V oc , a PCE triple junction efficiency of over 30% can be achieved. The specific layer thicknesses of each simulation body and their details are provided below.
[0532] in conclusion
[0533] Fully solution-processed all-perovskite multijunction solar cells open up new avenues for large-scale manufacturing of efficient multijunction architectures. These tandem architectures can be realized using a highly volatile ACN / MA-based solvent system that enables sequential stacking of perovskite absorbers of different energy gaps. The first fully solution-processed monolithic FA has been fabricated using highly transparent and efficient PEDOT:PSS / ITO NPs composite layers. 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 tandem solar cells, which achieved a stable energy conversion efficiency of 15.2%. 0.75 Sn 0.25 I3 perovskite junction, extending multi-junction light absorption to 925nm and fabricating the first triple-junction perovskite solar cell with a record-breaking V level of 2.83V oc .
[0534] Experimental details
[0535] Top Cell (TC) Fabrication: Glass / FTO / SnO2 / PC 61 BM / FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / Spiral-OMeTAD
[0536] Substrate preparation: On glass (Pilkington, 15Ω) coated with fluorine-doped tin oxide (FTO) -1 ). Initially, the FTO was removed at specific areas where the anode contacts would be deposited. The FTO was etched using 2M HCl and zinc powder. The substrate was then cleaned in Hellmanex detergent, acetone, isopropanol, and dried with a compressed air gun.
[0537] Fabrication of the tin oxide (SnO2) layer: We prepared a SnO2 precursor solution consisting of 17.5 mg ml dissolved in anhydrous 2-propanol (IPA) and immediately performed spin coating. -1 The solution was spin coated at 3000 rpm for 30 seconds at a ramp rate of 200 rpm / s in nitrogen. The substrate was then dried at 100° C. for 10 minutes in nitrogen. The subsequent annealing step was performed at 180° C. for 90 minutes in air.
[0538] PC 61 Preparation of BM layer: by adding 7.5 mg ml -1 PC 61 Phenyl-C61-butyric acid methyl ester (PC 61 We used dihydro-1H-benzimidazol-2-yl (N-DBI) derivatives, especially 3-dimethyl-2-phenyl-2,3-dihydro-1H-benzimidazole (N-DMBI) to synthesize PC 61 BM is doped (see S. Rossbauer, C. Müller, TD Anthopoulos, Adv. Funct. Mater. 2014, 24, n / a; Z. Wang, DP McMeekin, N. Sakai, S. van Reenen,K.Wojciechowski,JBPatel,MBJohnston,HJSnaith,Adv.Mater.2017,29,1604186;SSKim,S.Bae ,WHJo,Chem.Commun.2015,51,17413;P.Wei,T.Menke,BDNaab,K.Leo,M.Riede,Z.Bao,J.Am.Chem.Soc.2 012, 134, 3999; BD Naab, S. Guo, S. Olthof, EGB Evans, P. Wei, GL Millhauser, A. Kahn, S. Barlow, SR Marder, Z. Bao, J. Am. Chem. Soc. 2013, 135, 15018; P. Wei, J H Oh, G. Dong, Z. Bao, J. Am. Chem. Soc. 2010, 132, 8852). We used 0.25% wt% N-DMBI to treat PC 61The BM precursor solution was doped. The solution was then filtered using 0.45 μm PTFE filter paper. The solution was spin coated at 2000 rpm for 20 seconds at a slope of 1000 rpm / s in a nitrogen-filled glove box, and then the substrate was annealed at 80° C. for 10 minutes.
[0539] FAI synthesis: Formamidine acetate salt (99%, Sigma-Aldrich) was dissolved in a 1.5-fold molar excess of 57 wt.% hydroiodic acid (HI) (99.95%, Sigma-Aldrich) in stabilized distilled water to synthesize formamidine iodide (FAI). After the addition of the acid, the solution was stirred at 50°C for 10 minutes. After drying at 100°C for 2 hours in a large glass dish, a yellow-white powder was formed. It was then washed three times with ether. The powder was then dissolved in anhydrous ethanol (99.5%, Sigma-Aldrich) and heated at 120°C in an atmosphere rich in N2 to obtain a supersaturated solution. Once completely dissolved, the solution was slowly cooled to room temperature in an atmosphere rich in N2 until recrystallization occurred. The recrystallization process formed white flaky crystals. The solution was then placed in a refrigerator at 4°C and then transferred to a freezer for further crystallization. The powder was then washed three times with ether. Finally, the powder was dried overnight at 50°C in a vacuum oven.
[0540] FA with 2% K supplement 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 Preparation of perovskite precursor solution: The precursor salt is dissolved in anhydrous N,N-dimethylformamide (DMF) to obtain a desired FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3)3 composition and 2% K addition (using KI to KBr with a molar ratio of 30% to 70%) to prepare a FA / Cs (formamidine / Cs) perovskite solution with 2% K addition. The following precursor salts were used to prepare the precursor solution: formamidine iodide (FAI), cesium iodide (CsI) (99.9%, Alfa Aesar), lead iodide (PbI2) (99%, Sigma-Aldrich), lead bromide (PbBr2) (98%, Alfa Aesar), potassium iodide (KI) (99%, Sigma-Aldrich), potassium bromide (99%, KBr) (Sigma-Aldrich). 27.2 μl / ml of hydroiodic acid (HI) (57 wt.%, in stabilized distilled H2O, 99.95%, Sigma-Aldrich) and 54.8 μl / ml of hydrobromic acid (HBr) (48 wt.%, in H2O) were added to 1 ml of 0.75 M precursor solution. After the addition of the acid, the perovskite precursor solution was aged for 2 days under a nitrogen atmosphere.
[0541] FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 Preparation of perovskite layer: This aged perovskite precursor solution was spin coated at 1200 rpm for 45 s at a slope of 500 rpm / s in a nitrogen-filled glove box. The film was dried on a hot plate at 70°C for 1 minute in a N2 glove box. The film was then annealed in an oven at 185°C in an air atmosphere for 90 minutes. During this annealing, the sample was covered by a large glass container to prevent dust contamination.
[0542] Fabrication of Spiro-OMeTAD Hole Transport Layer: The electron blocking layer was deposited with 72.5 mg / ml of 2,2',7,7'-tetrakis-(N,N-di-p-methoxyaniline)9,9'-spirobifluorene (spiro-OMeTAD) (Lumtec) in chlorobenzene. 38 μl of lithium bis(trifluoromethanesulfonyl)imide (170 mg / mL in 1-butanol solution) was added per 1 mL of spiro-OMeTAD solution, and 21 μl of 4-tert-butylpyridine (TBP) was added per 11 mL of spiro-OMeTAD solution. The sample was placed in a desiccator for oxidation for 24 hours. Spin coating was performed at 2000 rpm for 20 seconds at a slope of 1000 rpm / s in a nitrogen-filled glove box.
[0543] Fabrication of composite interlayer (applicable to TC / MC and MC / BC): PEDOT:PSS / ITO NP
[0544] The intermediate layer was fabricated using PEDOT:PSS (PH 1000) (Heraeus Clevios) in water and 30 wt.% indium tin oxide (ITO), >100 nm nanoparticle (NP) dispersion (Sigma) in isopropanol (IPA) as precursor solutions. We first deposited a thin layer of PEDOT:PSS directly on top of the existing spiro-OMeTAD layer. Spin coating was performed immediately after the PEDOT:PSS precursor solution was prepared by diluting PEDOT:PSS (PH 1000) in anhydrous 2-propanol (IPA) at a volume ratio of 1 to 1.5 (PEDOT:PSS to IPA) and then filtering through a 2.7 μm GF / D membrane filter (Whatman). The substrate was preheated at 80°C, and then we dynamically spin-coated the diluted PEDOT:PSS solution at 6000 rpm for 20 s in a dry air atmosphere with a relative humidity (RHM) of >10%, followed by annealing at 80°C for 10 minutes. We then deposited the ITO NP layer. We prepared the ITO NP precursor solution by diluting 30 wt.% in IPA to 1 wt.% in IPA. Prior to deposition, the diluted solution was sonicated in an ultrasonic bath for 15 minutes. We dynamically spin-coated the diluted ITO NP solution at 6000 rpm for 20 s in a dry air atmosphere with a relative humidity (RHM) of >10%, followed by annealing at 80°C for 10 minutes.
[0545] Manufacturing of intermediate cells (MC): PC 61 BM / MAPbI3 / Spiro-OMeTAD
[0546] PC 61 Preparation of BM layer: by adding 30 mg ml -1 PC 61 Phenyl-C61-butyric acid methyl ester (PC 61 BM) precursor solution. The solvents were mixed in a volume ratio of 2:1 (CB to CF). We used dihydro-1H-benzimidazol-2-yl (N-DBI) derivatives, especially 3-dimethyl-2-phenyl-2,3-dihydro-1H-benzimidazole (N-DMBI) to 61 We doped PC with 0.25wt% N-DMBI. 61The BM precursor solution was doped. The solution was then filtered using a 0.45 μm PTFE filter paper. The substrate was preheated at 80°C, and then we dynamically spin-coated the solution at a speed of 4000 rpm for 20 s in a dry air atmosphere with a relative humidity (RHM) of >10%, and then the substrate was annealed at 80°C for 10 minutes.
[0547] Preparation of ACN / MA MAPbI3 perovskite precursor solution:
[0548] In this work, we found that controlling the MA content in acetonitrile (CH3CN) / methylamine (CH3NH2) (ACN / MA) MAPbI3 solutions can produce better tandem performance with higher reproducibility. Excess MA in the ACN / MA MAPbI3 solution may penetrate through the pinholes of the imperfect thin interlayer, thereby partially or completely dissolving the underlying junction. Therefore, a solution with the minimum amount of MA required to dissolve the perovskite is used. The MA content in the solution can be potentially controlled by controlling the MA flow rate and stirring speed, however, precise control of these parameters is sometimes challenging. Instead, we prepared two ACNMAPbI3 dispersions, one with excess MA content, resulting in a complete CN / MAMAPbI3 solution, and the other is an ACN MAPbI3 dispersion without any MA. We slowly added the ACN / MA MAPbI3 with excess MA to the ACN MAPbI3 dispersion until the dispersion was completely dissolved and became a full solution, and then immediately spin-coated. The resulting solution is an ACN / MAMAPbI3 solution at its critical solubility point. The preparation of ACN / MA MAPbI3 solution and ACN MAPbI3 dispersion was described as follows.
[0549] ACN MAPbI3 perovskite precursor solution without any MA was prepared using precursor salts methylammonium iodide (MAI) (Dyesol) and lead iodide (PbI2) (TCI) added to anhydrous acetonitrile (ACN) (Sigma Aldrich) at a concentration of 1.03 M MAI and 1 M PbI2 under nitrogen to produce a non-stoichiometric solution (1.03:1, MAI:PbI2). The solution was then sonicated in an ultrasonic bath for 1 hour to allow the MAI to react completely with PbI2, and then a black perovskite dispersion was seen at the bottom of the ACN filled vial.
[0550] Using Noel et al. (see NK Noel, SN Habisreutinger, B. Wenger, MT Klug, MT MB Johnston, RJ Nicholas, DT Moore, HJ Snaith, Energy Environ. Sci. 2017, 10, 145) described an improved method to prepare ACN / MA MAPbI3 perovskite precursor solution. We first prepared the ACN / MA MAPbI3 perovskite precursor solution using the same preparation method as above. In order to dissolve the perovskite in ACN, a solution of methylamine (MA) in ethanol (Sigma Aldrich, 33wt%) was placed in an aerator maintained in an ice bath. Nitrogen was then bubbled into the solution to degas the MA solution. The resulting MA gas was then passed through a drying tube containing a desiccant (Drietire and CaO). While the ACN / MA MAPbI3 dispersion was vigorously stirred at a speed of approximately 700 rpm using a large magnetic stirring bar, the gas was bubbled into the black dispersion. The dispersion was bubbled for 15 minutes to completely dissolve the black perovskite particles to obtain a clear light yellow solution. We note that this solution has an “excess” amount of MA in the ACN / MA MAPbI3 solution.
[0551] Preparation of ACN / MA MAPbI3 perovskite layer: The ACN / MA MAPbI3 precursor perovskite solution (at its critical solubility point) was immediately dynamically spin-coated at 5000 rpm for 20 seconds in dry air at a relative humidity (RHM) greater than 10%. Then, a post-treatment of methylammonium chloride (MACl) was performed by dynamically spin-coating 50 μl of MACl (Alfa Aesar, 2 mg / ml in isopropanol) at 6000 rpm for 20 seconds. The film was then annealed in an oven at 80°C in an air atmosphere for 90 minutes. During this annealing, the sample was covered with a large glass container to prevent dust contamination.
[0552] Fabrication of Spiro-OMeTAD Hole Transport Layer: The electron blocking layer was deposited by dynamically spin coating a solution of 85 mg / ml of 2,2',7,7'-tetrakis-(N,N-di-p-methoxyanilino)9,9'-spirobifluorene (spiro-OMeTAD) (Lumtec) in chlorobenzene. 20 μl of lithium bis(trifluoromethanesulfonyl)imide (520 mg / mL in acetonitrile solution) and 33 μl of 4-tert-butylpyridine (tBP) were added per 1 mL of Spiro-OMeTAD solution. Spin coating was performed at 2000 rpm for 30 s dynamically and in a dry air atmosphere with a relative humidity (RHM) greater than 10%. The samples were placed in a desiccator for oxidation for 24 hours.
[0553] Bottom Cell (BC) Manufacturing: PC 61 BM / ACN / MA MA-MAPb0.75 Sn 0.25 I3 / Screw (TFSI)2
[0554] PC 61 Preparation of BM layer: by adding 30 mg ml -1 PC 61 Phenyl-C61-butyric acid methyl ester (PC 61 The solvents were mixed in a volume ratio of CB:CF of 2:1. We used dihydro-1H-benzimidazol-2-yl (N-DBI) derivatives, especially 3-dimethyl-2-phenyl-2,3-dihydro-1H-benzimidazole (N-DMBI) to synthesize PC 61 We doped PC with 0.25wt% N-DMBI. 61 The BM precursor solution was doped. The solution was then filtered using a 0.45 μm PTFE filter paper. The substrate was preheated at 80°C, and then we dynamically spin-coated the solution at a speed of 4000 rpm for 20 s in a dry air atmosphere with a relative humidity (RHM) of >10%, and then the substrate was annealed at 80°C for 10 minutes.
[0555] ACN / MA-MAPb 0.75 Sn 0.25 Preparation of I3 perovskite precursor solution:
[0556] In order to obtain mixed metal ACN / MA MAPb 0.75 Sn 0.25 I3 perovskite precursor solution, we mixed ACN / MAMAPbI3 and ACN / MA MAPbI3 (without any MA) in a volume ratio of 1:1 to obtain ACN / MA MAPb 0.75 Sn 0.25 I3. ACN / MA MAPb without any MA was prepared using precursor salts methylammonium iodide (MAI) (Dyesol), lead iodide (PbI2) (TCI), and anhydrous tin iodide (SnI2) beads (TCI) in anhydrous acetonitrile (ACN) (Sigma Aldrich) at concentrations of 0.8 M MAI, 0.46 M PbI2, and 0.46 M SnI2 under nitrogen to produce a non-stoichiometric solution with a 15% excess of metal salts (1:1.15, MAI:PbI2+SnI2). 0.5 Sn 0.5I3 perovskite precursor solution. The solution was then stirred at 70 °C for 1 h under nitrogen to allow the MAI to react completely with the mixed metals, and then a black perovskite dispersion was seen at the bottom of the ACN filled vial.
[0557] ACN / MA MAPbI3 perovskite precursor solution was prepared using a modified method described by Noel et al. We first prepared an ACN / MA MAPbI3 perovskite precursor solution with 0.8 M MAI and 0.46 M PbI2 to obtain a non-stoichiometric solution with a 15% excess of metal salt (1:1.15, MAI:PbI2). To dissolve the perovskite in ACN, a solution of methylamine (MA) in ethanolic H2O (Sigma Aldrich, 40 wt%) was placed in an aerator maintained in an ice bath. Nitrogen was then bubbled into the solution to degas the MA solution. The resulting MA gas was then passed through a drying tube filled with desiccants (Drietire and CaO). The gas was bubbled into the black dispersion while the ACN / MA MAPbI3 dispersion was vigorously stirred at approximately 700 rpm using a large magnetic stir bar. The dispersion was bubbled for 15 minutes to completely dissolve the black perovskite particles, resulting in a clear, light yellow solution. We note that this solution has an “excess” amount of MA in the ACN / MA MAPbI3 solution. The solution is then activated to remove any H2O introduced during the MA bubbling process. The molecular sieves were kept in nitrogen for about 3 hours.
[0558] ACN / MA MAPb 0.75 Sn 0.25 I3 Perovskite Layer: This precursor perovskite solution was immediately dynamically spin-coated at 5000 rpm for 20 seconds in a nitrogen glove box. A second spin-coating step was then used to deposit methylammonium chloride (MACl) for post-treatment. 2 mg ml -1 A solution of MACl in IPA was dynamically spin-coated at 6000 rpm for 20 s. The film was then annealed at 80 °C in nitrogen for 90 min.
[0559] Synthesis of Spiro(TFSI)2: The modified method described by Nguyen et al. (see WH Nguyen, CD Bailie, EL Unger, MD McGehee, J. Am. Chem. Soc. 2014, 136, 10996) was used to prepare the MAPb 0.75 Sn 0.25 Spiro(TFSI)2 hole transport layer of I3 perovskite. We first prepared 2,2',7,7'-tetrakis-(N,N-di-p-methoxyaniline)9,9'-spirobifluorene (spiro-OMeTAD) (Lumtec) solution at 2 mg ml-1 Separately, we dissolved silver(I)bis(trifluoromethanesulfonyl)imide (Ag-TFSI) at 100 mg ml -1 dissolved in methanol. We slowly mixed equal volumes of both solutions together while stirring. The final molar ratio was 1 to 0.95 (spiro-OMeTAD to Ag-TFSI). We then stirred the mixed solution overnight. We filtered the solution using 2 μm PTFE filter paper to remove the Ag colloid. We used rotary evaporation to remove the CB until about 5% of the original volume remained. We then added toluene to the remaining flask at a volume of 50% of the initial CB volume. We kept the solution in a refrigerator for 24 h, where a fine black powder precipitated. Once the black powder was completely settled, we removed the excess toluene using a glass powder filter. We washed the powder with cold toluene at 4 °C. After the powder was dried, we prepared it into 20 mg ml -1 of methanol. The solubility of this black powder in methanol should not be too low, otherwise the precipitation process will start. We refrigerated the solution at 4°C overnight. The black powder was collected at the bottom of the vial. We removed the excess toluene using a glass frit filter and washed with methanol at 4°C. Once dried, the spiro(TFSI)2 powder was immediately collected and weighed.
[0560] Fabrication of spiro-OMeTAD hole transport layer doped with 10 wt.% spiro(TFSI)2: The electron blocking layer was deposited by dynamically spin coating spiro(TFSI)2-doped spiro-OMeTAD at 2000 rpm for 30 s in a nitrogen glove box. -1 of spiro (TFSI) 2 and 65.25 mg ml -1 A solution of 2,2',7,7'-tetrakis-(N,N-di-p-methoxyanilino)-9,9'-spirobifluorene (spiro-OMeTAD) (Lumtec) in chlorobenzene consisting of 72.5 mg ml -1 The precursor solution was prepared by adding spiro solution with wt.% of spiro-OMeTAD. No additives were added to the spiro-OMeTAD solution.
[0561] Fabrication of bottom cell (BC): PEDOT:PSS / FA 0.83 Cs 0.17 Pb 0.5 Sn 0.5 I3 / PC 61 BM / BCP
[0562] FA 0.83 Cs 0.17 Pb 0.5 Sn 0.5Preparation of I3 perovskite precursor: 1.2 M FAI (Dyesol), CsI (99.9%, Alfa Aesar), PbI2 (99.999%, Alfa Aesar), and SnI2 (99.999%, Alfa Aesar) were dissolved in a mixed solvent of DMF:DMSO with a volume ratio of 4:1 to prepare 1.2 M FAI (Dyesol). 0.83 Cs 0.17 Pb 0.5 Sn 0.5 A stoichiometric solution of I3 was prepared. 60 mM tin(II) fluoride (SnF2, 99%, Sigma Aldrich) and 36 mM lead(II) thiocyanate (99.5%, Sigma Aldrich) were also dissolved in the solution.
[0563] Device preparation: The patterned indium tin oxide (ITO) substrate was cleaned by rinsing in acetone and IPA sequentially. After drying, the substrate was cleaned with O2 plasma for 10 min. Immediately after the plasma treatment, a PEDOT:PSS solution (PVPAI 4083, Heraeus, with a volume ratio of 1:2 to methanol) was spin-coated at 4 krpm for 30 s under ambient conditions and then annealed at 150 °C for 10 min under ambient atmosphere. The device was immediately transferred to a N2 glove box. Just before fabricating the perovskite film, the PEDOT:PSS-coated ITO substrate was annealed again at 120 °C for 10 min. The perovskite film was prepared by spin-coating the solution at 3.6 krpm for 14 s at a slope of 6 s. 13 s after starting the spin-coating procedure, 200 μL of anisole was dispensed onto the rotating substrate. After the spin coating was completed, a N2 gas flow was applied to the film for 15 s and then immediately annealed at 120 °C for 10 min. By mixing 50uL PC 61 A hot solution (90 °C) of BM (20 mg / mL, dissolved in a mixed solvent of 3:1 chlorobenzene:1,2-dichlorobenzene by volume) was dynamically spin-coated for 30 s to produce PC 61 BM layer, then PC 61 The BM layer was annealed for 2 minutes at 90° C. After cooling to room temperature, 70 μL of 0.5 mg / mL deep cuprous solution (BCP, 98%, Alfa Aesar) was dynamically spin-coated at 4 krpm for 20 s.
[0564] Electrode: at ≈10 -6 Torr vacuum, at ≈0.2nm·s -1 Thermally evaporate 100nm of silver or gold electrode at a rate of
[0565] Characterization of solar cells: A simulated 100mWcm-2 The current density-voltage (JV) curves were measured (2400 Series SourceMeter, Keithley Instruments) under AM 1.5 sunlight with an irradiance of 1.5°, using a Si reference cell calibrated with KG5 filter from NREL for intensity calibration. The calculated mismatch factor was less than 1%. The active area of the solar cell was 0.0919 cm -2 The positive JV sweep was measured from positive bias (FB) to short circuit (SC), and the negative sweep was measured from short circuit to positive bias, both at 0.25 V s -1 Before scanning, complete the stabilization time of 5 seconds under 1 sunlight and the expected V OC A positive bias voltage of 0.3V is applied.
[0566] EQE Characterization: The multijunction EQE was measured by optically biasing the unmeasured subcell with a 3W 470-475nm LED and a 3W 730-740nm LED for TC and BC, respectively. During the measurement, a negative bias equal to the Voc of the subjunction being optically biased was applied to the stack. This enabled us to measure the response of the string stack under short circuit conditions.
[0567] Transient photoconductivity: A Nd:YAG laser excitation source tuned to 470 nm and pumped at a frequency of 10 Hz, 7 ns pulses was used over a fluence range to have various charge carrier densities as described in the main text. This pulsed light illuminates the entire sample area to uniformly excite the film. A bias of 24 V was applied across the in-plane (lateral) electrodes. Here, we employ a two-electrode conductivity measurement because the contact resistance between the perovskite film and the Au electrode is smaller than the sample resistance. A variable resistor is connected in series with the sample in the circuit to always be less than 1% of the sample resistance. We monitor the voltage drop across the variable series resistor via a parallel oscilloscope (1 MΩ) to determine the potential drop across the two in-plane Au electrodes in the sample (channel to channel distance is 4 mm). The perovskite film is described as having a channel width of 5 mm and coated with an inert 200 nm PMMA. Transient photoconductivity (σ Ph ) is calculated by the following formula: Where Rr is a variable resistor, V 偏压 is the bias voltage, l is the channel-channel length, w is the channel width, and t is the film thickness.
[0568] Modeling:
[0569] Overview: We modeled the optical properties of the stack using the generalized transfer matrix method (TMM) (see E. Centurioni, Appl. Opt. 2005, 44, 7532). All calculations were done in Python making extensive use of the NumPy and SciPy libraries. The wavelength-dependent complex refractive index, layer thicknesses and angle of incidence are taken as input. The TMM model outputs the electric field distribution in the stack. This is used to calculate the transmittance T(E), reflectivity R(E) and absorptivity A(E) in each layer. The short-circuit current of each sub-cell is then determined by assuming that the internal quantum efficiency is combined as:
[0570]
[0571] Here, φ AM1.5 (E) is the photon flux from the AM1.5 spectrum.
[0572] By modeling this J SC The JV curve of each sub-cell is obtained by combining the electrical characteristics of the single-junction cell of the prior art. To this end, we parameterize the JV curve of the single junction of the prior art according to the single diode equivalent model:
[0573]
[0574] Where n, V T , R S , J0 and R SH They are the electron charge, the thermal voltage at 300K, the series resistance, the dark current and the shunt resistance. By replacing J in the fitting equation sun Replaced by J calculated from the multijunction stack SC To model the JV curve of each multi-junction cell. sun The correlation between J and other fitting parameters is negligible, so we can be sure that we can change J without changing other parameters. sun The method of Jain et al. (see A. Jain, A. Kapoor, Sol. Energy Mater. Sol. Cells 2004, 81, 269) is used to solve the single diode model using the Lambert W function. After calculating the JV curves of all subcells, we combine them to obtain the multijunction JV curve (see A. Hadipour, B. de Boer, PWM Blom, Org. Electron. 2008, 9, 617). The highest point is calculated from the combined JV curve.
[0575] Inputs for optical and electrical models: ITO, FTO, PEDOT: PSS, PCBM, Spiro-OMeTAD, Ag, MA0.4 FA 0.6 Sn 0.6 Pb 0.4 I3 and MAPbI3 core integration specifications (default TAF PALedin.J.Kerszulis,MAMahmoud,MAEl-Sayed,JRReynolds,VVTsukruk,ACSNano 2014,8,6182,JMBall,SDStranks,MT S.Hüttner,W.Zhang,EJWCrossland,I.Ramirez,M.Riede,MBJohnston,RHFriend,HJSnaith,EnergyEnviron.Sci.2015,8,602D.Shi,V.Adinolfi,R.Comin ,M.Yuan,E.Alarousu,A.Buin,Y.Chen,S.Hoogland,A.Rothenberger,K.Katsiev,Y.Losovyj,X.Zhang,PADowben,OFMohammed,EHSargent,OMBakr,Science 2015,347,519;VSGevaerts,LJAKoster,MMWienk,RAJJanssen,ACS Appl.Mater.Interfaces 2011,3,3252;M. P.S. B.Niesen,S.De Wolf,J. C.Ballif,M. Opt.Express 2015,23,A263,PBJohnson,RWChristy,Phys.Rev.B 1972,6,4370,MT T.Leijtens,MEZiffer,GEEperon,MGChristoforo,MDMcGehee,HJSnaith,ACS EnergyLett.2017,2,2506,P. M.Stuckelberger,B.Niesen,J.Werner,M. S.-J.Moon,J.-H.Yum,M. S. De Wolf, C. Ballif, J. Phys. Chem. Lett. 2015, 6, 66). FA is obtained by measuring the transmittance T and reflectance R of a thin film with a thickness of t on glass and using the following relationship 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 extinction coefficient k:
[0576]
[0577]
[0578] Once k(λ) is obtained, we can parameterize it in terms of a Lorentz oscillator to obtain an analytical representation, which is converted to the refractive index n(λ) via the Kramers-Kronig transformation:
[0579]
[0580] MAPbI3 and MAPb 0.75 Sn 0.25 The electrical properties of I3 are extracted from the best reported batteries of the same or similar class in the literature (see SS Shin, EJ Yeom, W S Yang, S. Hur, MG Kim, J. Im, J. Seo, 2017, 6620; R. Prasanna, A. Gold-Parker, T. Leijtens, B. Conings, A. Babayigit, HG Boyen, MF Toney, MD Mc Gehee, J. Am. Chem. Soc. 2017, 139, 11117). 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 sub-batteries, we use the best FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 JV curve of a single junction cell (Figure 7). To account for the ITO nanoparticles embedded in PCBM, we modeled the refractive index as a Brugmann effective medium with 75% ITO and 25% PCBM. The refractive index of the effective medium is calculated by solving the following formula:
[0581]
[0582] Where n ITO 、n PCBM and f ITOare the complex refractive index of ITO, the complex refractive index of PCBM and the fraction of ITO in the effective medium.
[0583] String stack simulation
[0584] FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 simulation- Figure 4A , Figure 4B : The thickness used in the optical model is obtained from the SEM cross section of the stack. 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 The electrical characteristics of )3 and MAPbI3 are taken from our own single junction devices (Figure 7). The dashed JV line models the performance assuming that MAPbI3 performs as well as the best ACN-treated MAPbI3 cells in the literature.
[0585]
[0586] FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3(optimized)- Figure 4C , Figure 4D : We limited the thickness of the non-perovskite layer to 50nm. We added a MgF2 anti-reflection coating. We optimized the thickness of the perovskite layer and the anti-reflection coating using a differential evolution algorithm to maximize the limiting current. FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 The electrical characteristics of )3 are from our own devices (Fig. 7). The characteristics of MAPbI3 are from the best cell MAPbI3 in the literature (see SSS Shin, EJ Yeom, W.S Yang, S. Hur, M.G. Kim, J. Im, J. Seo, J.H. Noh, S. Il Seok, Science 2017, 356, 167). The dashed JV curve models the performance of the stack, assuming that the electrical performance of the top cell is as good as the state-of-the-art in perovskites. To do this, we use et al. (see MT T.Leijtens, M.E.Ziffer, G.E.E.peron, M.G.Christoforo, M.D.McGehee, H.J.Snaith, ACS Energy Lett. 2017, 2, 2506) and assuming EQE EL =0.01, R S =4·10 -2 Ω cm 2 , and R SH =10MΩ cm 2 .
[0587]
[0588]
[0589] FA 0.83 Cs 0.17 Pb(Br 0.7 I 0.3 )3 / MAPbI3 / MA 0.4 FA 0.6 Pb 0.4 Sn 0.6 I3 (optimized) simulation - Figure 4E , Figure 4F : The calculations for Figures E and F are performed exactly the same as those for Figures C and D. For the dashed triple junction JV curves, both the bottom cell and the top cell are modeled as state-of-the-art perovskite cells.
[0590]
Claims
1. A method for producing a multi-junction device comprising a layer of crystalline A / M / X material, wherein the crystalline A / M / X material comprises a compound of the formula, [A] a [M] b [X] c in: [A] comprises one or more A cations, wherein each A cation is selected from: alkali metal cations; formula [R1R2R3R4N] + wherein R1, R2, R3, and R4 are each independently selected from hydrogen, unsubstituted or substituted C 1-20 Alkyl and unsubstituted or substituted C 6-12 Aryl, and at least one of R1, R2, R3 and R4 is not hydrogen; Formula [R5R6N=CH-NR7R8] + wherein R5, R6, R7 and R8 are each independently selected from hydrogen, unsubstituted or substituted C1- 20 Alkyl and unsubstituted or substituted C 6-12 Aryl; and C 1-10 Alkyl ammonium ion, C 2-10 Alkenyl ammonium ion, C 1-10 Alkyl iminium ion, C 3-10 Cycloalkylammonium ions and C 3-10 Cycloalkyl iminium ions, each of which is unsubstituted or substituted with an amino group, a C 1-6 Alkylamino, imino, C 1-6 Alkyl imine, C 1-6 Alkyl, C 2-6 Alkenyl, C 3-6 Cycloalkyl and C 6-12 one or more substituents in the aryl group; [M] includes one or more M cations, wherein the M cations are metal or metalloid cations, wherein each M cation is selected from Ca 2+ , Sr 2+ 、Cd 2+ , Cu 2+ 、Ni 2+ , Mn 2+ , Fe 2+ 、Co 2+ , Pd 2+ ,Ge 2+ Sn 2+ , Pb 2+ , Yb 2+ and Eu 2+ ; [X] comprises one or more X anions, wherein each X anion is a halide anion; a is a number from 1 to 6; b is a number from 1 to 6; and c is a number from 1 to 18; and, The method comprises forming the crystalline A / M / X material layer by disposing a film-forming solution on a substrate, wherein the film-forming solution comprises: (a) one or more M cations; and (b) solvent; The photoactive material in the substrate is soluble in dimethylformamide, dimethyl sulfoxide, or a mixture thereof; or at least one component of the charge recombination layer in the substrate is soluble in dimethylformamide, dimethyl sulfoxide, or a mixture thereof; wherein the solvent comprises (i) an aprotic solvent; and (ii) organic amines; And, wherein the substrate comprises: a photoactive region comprising a photoactive material; and A charge recombination layer is disposed on the photoactive region by a solution deposition method, wherein the charge recombination layer comprises nanoparticles of a transparent conductive oxide disposed in an electron transporting organic matrix material, and wherein the charge recombination layer further comprises a conductive polymer.
2. The method according to claim 1, wherein: The aprotic solvent is a polar aprotic solvent; and / or The substrate further includes a layer of charge transport material disposed on the charge recombination layer.
3. The method according to claim 1, wherein: A charge transport material layer is disposed on the charge recombination layer.
4. The method according to claim 1, wherein: The photoactive material in the substrate and at least one component of the charge recombination layer in the substrate are both soluble in dimethylformamide, dimethyl sulfoxide, or a mixture thereof.
5. The method according to claim 1 or 2, wherein: The transparent conductive oxide includes indium tin oxide (ITO).
6. The method according to claim 1 or 2, wherein: The organic matrix material comprises [6,6]-phenyl-C61-butyric acid methyl ester PCBM.
7. The method according to claim 1 or 2, wherein: The conductive polymer includes poly(3,4-ethylenedioxythiophene) and polystyrene sulfonate PEDOT:PSS.
8. The method according to claim 1 or 2, wherein: Disposing the charge recombination layer on the photoactive region includes the step of disposing a solvent dispersion of nanoparticles of the transparent conductive oxide on the photoactive region.
9. The method according to claim 8, wherein: Disposing the charge recombination layer on the photoactive region includes disposing a conductive polymer on the photoactive region and disposing a solvent dispersion of nanoparticles of a transparent conductive oxide on the photoactive region.
10. The method according to claim 8, wherein: The solvent dispersion of the nanoparticles and / or the conductive polymer is disposed on the photoactive region by spin coating.
11. The method according to claim 1, wherein: The aprotic solvent does not include dimethylformamide, dimethyl sulfoxide, or a mixture thereof; and / or The aprotic solvent comprises a compound selected from the group consisting of chlorobenzene, acetone, butanone, methyl ethyl ketone, acetonitrile, propionitrile, toluene, or a mixture thereof; and / or, The organic amine is an unsubstituted or substituted alkylamine, or an unsubstituted or substituted arylamine.
12. The method according to claim 11, wherein: The aprotic solvent includes acetonitrile.
13. The method according to claim 11, wherein: The organic amine is unsubstituted or substituted (C 1-10 Alkyl)amine.
14. The method according to claim 13, wherein: The organic amine is methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, benzylamine or phenethylamine.
15. The method according to claim 13, wherein: The organic amine is methylamine.
16. The method according to claim 1 or 2, wherein: Formula [A] a [M] b [X] c The compound is of formula [A] a [M] b [X] A compound of 3, wherein [A], [M] and [X] are as defined in claim 1; and / or Wherein, [A] comprises the formula [R1NH3] + The cation, wherein R1 is an unsubstituted C 1-10 alkyl, and wherein the organic amine comprises an unsubstituted (C 1-10 Alkyl)amine.
17. The method according to claim 1, wherein: Each A cation is selected from Cs + , Rb + , methylammonium ion, dimethylammonium ion, trimethylammonium ion, ethylammonium ion, propylammonium ion, butylammonium ion, pentylammonium ion, hexylammonium ion, heptylammonium ion, octylammonium ion, tetramethylammonium ion, formamidine ion, 1-aminoethane-1-iminium ion and guanidine.
18. The method according to claim 1, wherein: Each M cation is selected from Sn 2+ and Pb 2+ .
19. The method according to claim 1, wherein: [X] comprises two or more different halide anions.
20. The method according to claim 1, wherein: Formula [R1NH3] + The C on the A cation 1-10 Alkyl and the unsubstituted (C 1-10 C on alkyl)amine 1-10 The alkyl groups are the same.
21. The method according to claim 1, wherein: The photoactive material in the photoactive region in the substrate comprises a crystalline A / M / X material comprising the formula [A] as defined in any one of claims 1 and 16 to 20: a [M] b [X] c and / or The substrate comprises two separate photoactive regions, wherein each photoactive region comprises a photoactive material; and / or The membrane-forming solution further comprises one or more A cations and one or more X anions; and / or The method further comprises the step of disposing a composition comprising one or more A cations and optionally one or more X anions on the substrate; and / or The method further comprises disposing a film-forming composition on the substrate, including the step of spin coating the film-forming solution on the substrate; and / or The method further includes removing the solvent to form a layer comprising a crystalline A / M / X material.
22. The method according to claim 21, wherein: The substrate comprises a first electrode, And the method further comprises: Arranging a second electrode on the crystalline A / M / X material layer arranged on the substrate, Alternatively, a charge transport material is disposed on the crystalline A / M / X material layer disposed on a substrate, and a second electrode is disposed on the charge transport material.
23. The method according to claim 22, wherein: The second electrode includes a single metal.
Citation Information
Patent Citations
Double perovskite
WO2017037448A1
Organic tandem photovoltaic device and methods
US20160005795A1
A / m / x material production process with alkylamine
WO2017153752A1